Adhesive sheet and its use
By designing a multi-layer structure in the adhesive layer, using the B layer of the photocrosslinkable polymer to improve deformation resistance, and improving surface shape follow-up through the design of the A layer, it is solved that it is difficult for existing adhesives to achieve this simultaneously. The two properties have achieved high stability and reliability bonding.
Patent Information
- Application Number
- CN202080052442.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-02
- Filing Date
- 2020-07-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-07-28
AI Technical Summary
It is difficult for existing adhesives to achieve high surface shape follow-up and deformation resistance at the same time, resulting in insufficient stability and reliability of bonding.
The adhesive layer with a multi-layer structure is adopted, in which the B layer containing the photocrosslinkable polymer improves deformation resistance through photocrosslinking, and improves surface shape following through the design of the A layer.
The adhesive layer is able to follow the shape of the adhesive layer on the surface of the adherend, and a bond with high deformation resistance is formed after adhesion, thereby improving the stability and reliability of the bonding.
Smart Images

Figure CN114127216B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet and a method for producing a laminate using the pressure-sensitive adhesive sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2019-143393 filed on August 2, 2019, the entire contents of which are incorporated herein by reference. Background Art
[0003] Generally, adhesives (also called pressure-sensitive adhesives, hereinafter the same) have the following properties: they are in a soft solid (viscoelastic) state in a temperature range near room temperature and are easily adhered to an adherend under pressure. Due to such properties, adhesives are widely used in various fields. Patent Document 1 can be cited as a technical document related to adhesives.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-140497 Summary of the invention
[0007] Problems to be solved by the invention
[0008] For adhesives, various properties are required according to the purpose. Among these properties, it is sometimes difficult to achieve them at a high level at the same time, for example, there is a tendency for another property to decrease when one property is desired to be improved. As an example of a property in such a relationship that is difficult to achieve at the same time, the property of deforming by following the surface shape of the adherend (hereinafter, also referred to as "surface shape following property") and the property of not being easy to deform relative to stress (hereinafter, also referred to as "deformation resistance").
[0009] Therefore, an object of the present invention is to provide an adhesive having good conformability to the surface shape of an adherend and capable of forming a bond having high deformation resistance, and an adhesive sheet using the adhesive.
[0010] Means for solving problems
[0011] According to this specification, an adhesive sheet with an adhesive layer can be provided. The above-mentioned adhesive layer is a multilayer structure including an A layer constituting one surface of the adhesive layer and a B layer disposed on the back side of the above-mentioned A layer. The above-mentioned B layer is a photo-crosslinkable adhesive layer containing a photo-crosslinkable polymer. The above-mentioned adhesive sheet can improve deformation resistance by photo-crosslinking the above-mentioned B layer. Thus, when attached to an adherend, the surface shape followability of the adhesive layer is good, and after attachment, by photo-crosslinking the above-mentioned B layer, a joint with high deformation resistance can be formed. For an adhesive layer with good surface shape followability, it can be appropriately adhered to the surface of the adherend by deforming (absorbing step difference) along the step difference that may exist on the surface of the adherend. In addition, since the above-mentioned adhesive layer is a multilayer structure and one of its surfaces is composed of the A layer, the A layer can be used to give a desired function to the above-mentioned one surface.
[0012] A preferred example of the photo-crosslinkable polymer is a polymer (PB) having a benzophenone structure in a side chain. The layer B including the polymer (PB) can be photo-crosslinked using the benzophenone structure.
[0013] Another preferred example of the photo-crosslinkable polymer is a polymer (PD) having a carbon-carbon double bond. The layer B including the polymer (PD) can be photo-crosslinked by reacting the carbon-carbon double bond.
[0014] In some embodiments of the technology disclosed herein (including an adhesive sheet having an adhesive layer, the adhesive layer, an adhesive composition for forming the adhesive layer, a method for manufacturing a laminate using the adhesive sheet, etc. The same below), in the above-mentioned layer B, the content of a multifunctional monomer having two or more ethylenically unsaturated groups (hereinafter, also referred to as "multifunctional monomer") is preferably 40 μmol / g or less. By limiting the content of the multifunctional monomer in the B layer as described above, the performance stability of the adhesive sheet relative to storage can be improved.
[0015] In some embodiments, the A layer may contain a water affinity agent. Thus, the water releasability of the adhesive surface on the A layer side of the adhesive layer can be improved. Even after the B layer is photocrosslinked, the adhesive sheet having a highly water releasable adhesive surface can be easily peeled off by using an aqueous liquid such as water. This is preferred from the viewpoint of reprocessing of the adhesive sheet.
[0016] In some preferred embodiments of the PSA sheet, the water peel strength reduction rate calculated from the peel strength N0 and the peel strength N2 measured by the following procedure is 40% or more.
[0017] Water peeling force reduction rate [%] = (1-(N2 / N0)) × 100;
[0018] A PSA sheet having a PSA surface with a high water peel strength reduction rate as described above is preferred because it can be easily peeled using an aqueous liquid such as water even after the layer B is photo-crosslinked.
[0019] [Measurement procedure of peel strength N0]
[0020] A 2 kg rubber roller was moved back and forth once to press the A layer side of the adhesive sheet onto the corona treated polarizing plate, and then the sheet was subjected to an autoclave treatment (50°C, 0.5 MPa, 15 minutes). The sheet was then irradiated with ultraviolet light using a high pressure mercury lamp. Then, the adhesive sheet was peeled off from the polarizing plate at a tension rate of 300 mm / min and a peeling angle of 180 degrees in an atmosphere of 25°C. The peel strength at this time was taken as the peel strength N0.
[0021] [Measurement procedure of peel strength N2]
[0022] In the measurement of the peel strength N0, 20 μL of distilled water was supplied to the portion where the pressure-sensitive adhesive sheet began to separate from the polarizing plate while the pressure-sensitive adhesive sheet was being peeled off from the polarizing plate, and the peel strength after supplying the distilled water was taken as the peel strength N2.
[0023] In some preferred embodiments of the adhesive sheet, the peel strength N0 measured by the above-mentioned step is 1.5 N / 10 mm or more. According to such an adhesive sheet, a highly reliable bond can be formed by using the photo-crosslinked adhesive layer.
[0024] In some embodiments, the thickness of the PSA layer may be 10 μm to 500 μm. A PSA sheet having a PSA layer having such a thickness is preferred from the viewpoints of surface shape conformability and handleability (eg, processability such as punching of the PSA sheet).
[0025] In some embodiments, the thickness of the layer A may be greater than 2 μm and less than 10 μm. According to the adhesive sheet having the layer A of such a thickness, the effect provided by the layer A (for example, improvement of water peelability) and the effect of improving deformation resistance obtained by photocrosslinking the layer B can be suitably achieved simultaneously.
[0026] According to the present specification, a method for manufacturing a laminated body can be provided, which sequentially includes the following steps: laminating the A layer side of any adhesive sheet disclosed herein on a component; and photo-crosslinking the B layer of the adhesive sheet. According to the method, when laminating the adhesive sheet on the component, the adhesive layer can well follow the surface shape of the component, and after lamination, the B layer is photo-crosslinked to improve deformation resistance, so that a laminated body in which the adhesive layer after photo-crosslinking is reliably bonded to the component can be obtained.
[0027] It should be noted that appropriate combinations of the above-mentioned elements may also be included in the scope of the invention claimed for patent protection in this international application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.
[0029] [ Figure 2 ] Figure 2 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.
[0030] [ Figure 3 ] Figure 3 This is a cross-sectional view schematically showing an optical member with a pressure-sensitive adhesive sheet in which a pressure-sensitive adhesive sheet according to one embodiment is attached to an optical member. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention are described below. It should be noted that matters necessary for implementing the present invention, except for those specifically mentioned in this specification, can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, components and parts that play the same role are sometimes marked with the same symbols for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are illustrated for the purpose of clearly explaining the present invention, and do not necessarily accurately represent the size or reduction ratio of the product actually provided.
[0032] In this specification, "acrylic polymer" refers to a polymer derived from a monomer component containing an acrylic monomer in an amount of more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight). The above-mentioned acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule. In addition, in this specification, "(meth)acryloyl" refers to both acryloyl and methacryloyl. Similarly, "(meth)acrylate" refers to both acrylate and methacrylate, and "(meth)acrylic-" refers to both acrylic- and methacrylic-, respectively.
[0033] In this specification, "ethylenically unsaturated compound" refers to a compound having at least one ethylenically unsaturated group in the molecule. Examples of ethylenically unsaturated groups include (meth)acryloyl, vinyl, allyl, etc. Hereinafter, a compound having one ethylenically unsaturated group is sometimes referred to as a "monofunctional monomer", and a compound having more than two ethylenically unsaturated groups is sometimes referred to as a "multifunctional monomer". In addition, a compound having X ethylenically unsaturated groups in a multifunctional monomer is sometimes described as "X-functional monomer".
[0034] In this specification, the adhesive layer of a multilayer structure refers to an adhesive layer composed of two or more sub-adhesive layers with different compositions stacked together. The number of sub-adhesive layers constituting the above-mentioned multilayer structure is, for example, less than 10, and from the viewpoint of the transparency of the adhesive layer, preferably less than 5, may be less than 4, or may be less than 3. An adhesive layer of a double-layer structure formed by layer A and layer B is a preferred example of the adhesive layer of a multilayer structure referred to herein. The sub-adhesive layers constituting the adhesive layer of a multilayer structure are stacked in a manner such that at least a portion thereof is in direct contact. For the adhesive layer of the above-mentioned multilayer structure, typically, there is no diaphragm layer (for example, a resin film such as a polyester film) between one surface and the other surface of the adhesive layer that completely separates the sub-adhesive layers adjacent to each other.
[0035] In this specification, the adhesive composition contains an ethylenically unsaturated compound, and unless otherwise specified, it means that the adhesive composition contains the ethylenically unsaturated compound in the form of a partial polymer. Such a partial polymer is usually a mixture of the ethylenically unsaturated compound (unreacted monomer) containing an ethylenically unsaturated group and the ethylenically unsaturated compound polymerized with the ethylenically unsaturated group.
[0036] In this specification, the so-called monomer components constituting the adhesive composition as a whole refers to the total amount of monomer components constituting the polymer contained in the adhesive composition and the monomer components contained in the adhesive composition in the form of unreacted monomers. The composition of the monomer components constituting the adhesive composition is generally consistent with the composition of the monomer components of the photocrosslinkable adhesive formed from the adhesive composition and the composition of the monomer components constituting the photocrosslinked product thereof.
[0037] In this specification, the concept of "active energy rays" includes light such as ultraviolet rays, visible rays, and infrared rays, α rays, β rays, γ rays, electron rays, neutron beams, and radiation such as X-rays.
[0038] <Configuration Example of Pressure-Sensitive Adhesive Sheet>
[0039] One configuration example of the PSA sheet disclosed herein is shown in Figure 1. The adhesive sheet 1 is constituted as a single-sided adhesive sheet including an adhesive layer 110 whose one surface 110A serves as an adhesive surface to be attached to an adherend, and a substrate 20 laminated on the other surface of the adhesive layer 110. The adhesive layer 110 is fixedly bonded to one surface 20A of the substrate 20. As the substrate 20, a plastic film such as a polyester film can be preferably used. The adhesive layer 110 has a double-layer structure formed by an A layer 112 constituting one surface (adhesive surface) 110A, and a B layer 114 laminated on the back side of the A layer 112. The B layer 114 is a photo-crosslinkable adhesive layer containing a photo-crosslinkable polymer.
[0040] The pressure-sensitive adhesive sheet 1 before use (before being attached to an adherend) can be, for example, Figure 1 As shown in the figure, the adhesive surface 110A is protected by a release liner 30 whose at least the adhesive layer side becomes a releasable surface (release surface), and the adhesive sheet with a release liner is stored, circulated, etc. Alternatively, it can also be in the following form: the second surface 20B (the surface on the opposite side to the first surface 20A, also referred to as the back side) of the substrate 20 becomes the release surface, and the adhesive surface 110A is abutted against the second surface 20B. The adhesive surface 110A is thus protected.
[0041] The release liner is not particularly limited, and for example, a release liner having a release treatment on the surface of a liner substrate such as a resin film or paper, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. In the above release treatment, for example, a release treatment agent such as a silicone-based or long-chain alkyl-based release agent can be used. In some embodiments, a release-treated resin film can be preferably used as the release liner.
[0042] The adhesive sheet disclosed herein may also be in the form of a double-sided adhesive sheet without a substrate formed by an adhesive layer. The double-sided adhesive sheet without a substrate may be, for example, Figure 2 As shown, due to Figure 1 The adhesive layer 110 of the adhesive sheet 1 shown (i.e., the adhesive layer 110 of the double-layer structure formed by the A layer 112 and the B layer 114 stacked in direct contact on its back side) is formed into an adhesive sheet 2. The double-sided adhesive sheet 2 without a substrate can be in a form in which the adhesive surface 110A as the surface of the A layer side and the adhesive surface 110B as the surface of the B layer side are protected by abutting the release surfaces of the release liners 30 and 31 respectively before use. Alternatively, it can also be in the following form: the back side of the release liner 30 (the surface on the opposite side to the adhesive side) becomes the release surface, and the adhesive surface 110B is wound or stacked in a manner that the adhesive surface 110B abuts against the back side of the release liner 30, thereby protecting the adhesive surfaces 110A and 110B. The double-sided adhesive sheet without a substrate can be used, for example, in a manner in which a substrate is bonded to any one surface of the adhesive layer.
[0043] The adhesive sheet disclosed herein may be a constituent element of an optical member with an adhesive sheet obtained by bonding an optical member to one surface of an adhesive layer. For example, Figure 1 The adhesive sheet 1 shown can be Figure 3 The components of the optical member 200 with a pressure-sensitive adhesive sheet are shown in FIG. 1 , wherein the optical member 70 is bonded to one surface 110A of the pressure-sensitive adhesive layer 110. The optical member may be, for example, a glass plate, a resin film, or a metal plate.
[0044]
[0045] The photocrosslinkable polymer contained in the B layer of the adhesive layer constituting the adhesive sheet disclosed herein is a polymer having a structural portion (hereinafter also referred to as a "photocrosslinkable portion") that can form a crosslinked structure using light such as ultraviolet rays, and is not particularly limited. The above-mentioned B layer can be, for example, a B layer formed by a photocrosslinkable adhesive containing a polymer (PB) having a benzophenone structure in the side chain as a photocrosslinkable polymer (hereinafter also referred to as a "B-type B layer"), a B layer formed by a photocrosslinkable adhesive containing a polymer (PD) having a carbon-carbon double bond as a photocrosslinkable polymer (hereinafter also referred to as a "D-type B layer"), etc. In the following description, when referred to as "B layer", its meaning includes B-type B layer, D-type B layer and other B layers.
[0046] (1) Layer B comprising polymer (PB)
[0047] As a preferred example of the B layer containing a photo-crosslinkable polymer, a B layer (B-type B layer) formed by a photo-crosslinkable adhesive containing a polymer (PB) having a benzophenone structure in a side chain as the photo-crosslinkable polymer can be cited. The polymer (PB) is preferably a polymer substantially free of ethylenically unsaturated groups. The polymer (PB) is preferably a rubbery polymer that exhibits rubber elasticity in a temperature range near room temperature. In some embodiments, the B-type B layer can be a photo-crosslinkable sub-adhesive layer containing a polymer (PB) as a base polymer.
[0048] It should be noted that the "base polymer" of the adhesive layer refers to the main component of the polymer contained in the adhesive layer. Similarly, the "base polymer" of layer A and layer B refers to the main component of the polymer contained in layer A and layer B, respectively. In addition, in this specification, the so-called "main component" refers to a component contained in an amount exceeding 50% by weight unless otherwise specified.
[0049] In this specification, the so-called "benzophenone structure" refers to the general formula: Ar 1 -(C=O)-Ar 2 -, or -Ar 3 -(C=O)-Ar2 Here, Ar in the above general formula is 1 is selected from phenyl groups which may have a substituent. 2 ,Ar 3 are each independently selected from a phenylene group which may have a substituent. 2 with Ar 3 The above-mentioned benzophenone structure-containing component refers to a compound having at least one such benzophenone structure in the molecule. The benzophenone structure can be excited by ultraviolet irradiation and can capture hydrogen free radicals from other molecules or other parts of the molecule in its excited state.
[0050] For the B-type B layer, by stimulating the benzophenone structure of the polymer (PB), a cross-linked structure can be formed by utilizing the hydrogen radical abstraction reaction. The polymer (PB) preferably has the general formula: Ar 1 -(C=O)-Ar 2 -Ar in 1 is a phenyl group which may have a substituent, Ar 2 It is a polymer of a benzophenone structure of a phenylene group which may have a substituent. 1 and Ar 2 When at least one of the substituents has one or more substituents, the substituents can be independently selected from the group consisting of an alkoxy group (for example, an alkoxy group having 1 to 3 carbon atoms, preferably a methoxy group), a halogen atom (for example, F, Cl, Br, etc., preferably Cl or Br), a hydroxyl group, an amino group and a carboxyl group, but are not limited to these.
[0051] The polymer (PB) in the technology disclosed herein may be a polymer having a benzophenone structure as described above directly bonded to a side chain of the main chain, or may be a polymer having a benzophenone structure as described above bonded to a side chain of the main chain via one or more of, for example, an ester bond, an oxyalkylene structure, etc. As a preferred example of the polymer (PB), a polymer comprising repeating units derived from a compound having an ethylenically unsaturated group and a benzophenone structure in the molecule (hereinafter also referred to as "ethylenically unsaturated BP") may be cited. The above-mentioned repeating unit may be a polymerized residue formed by reacting the ethylenically unsaturated group of the corresponding ethylenically unsaturated BP.
[0052] Examples of the ethylenically unsaturated BP include 4-acryloyloxybenzophenone, 4-acryloyloxy-4'-methoxybenzophenone, 4-acryloyloxyethoxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, and 2-hydroxy-4-acryloyloxybenzophenone, 4-[(2-acryloyloxy)ethoxy]benzophenone, 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone, and 4-methacryloyloxybenzophenone; 4-methacryloyloxybenzophenone, 4-methacryloyloxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, and 2-hydroxy-4-acryloyloxybenzophenone; 4-[(2-acryloyloxy)ethoxy]benzophenone, 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone, and 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone; and 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone. 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-bromobenzophenone, 2-hydroxy-4-methacryloyloxybenzophenone, etc., which may have substituted methacryloyloxybenzophenones; 4-[(2-methacryloyloxy)ethoxy]benzophenone, 4-[(2-methacryloyloxy)ethoxy]-4'-methoxybenzophenone, etc., which may have substituted methacryloyloxyalkoxybenzophenones; 4-vinylbenzophenone, 4'-bromo-3-vinylbenzophenone, 2-hydroxy-4-methoxy-4'-vinylbenzophenone, etc., which may have substituted vinylbenzophenones; etc., but are not limited to these. For ethylenically unsaturated BP, one alone or a combination of two or more can be used for the preparation of polymer (PB). Ethylenically unsaturated BP can use commercial products or can be synthesized by known methods. From the viewpoint of reactivity and the like, an ethylenically unsaturated BP having a (meth)acryloyl group, that is, an ethylenically unsaturated BP as an acrylic monomer can be preferably used.
[0053] The polymer (PB) may also be a copolymer having repeating units derived from ethylenically unsaturated BP and repeating units derived from ethylenically unsaturated compounds that are not ethylenically unsaturated BP (hereinafter, also referred to as "other monomers"). Such a polymer (PB) may be a copolymer of monomer components comprising the above-mentioned ethylenically unsaturated BP and the above-mentioned other monomers. In some embodiments, as the above-mentioned other monomers, one or more acrylic monomers may be preferably used. As a preferred example of the polymer (PB), an acrylic polymer (PB) in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the monomer components constituting the polymer (PB) are acrylic monomers can be cited.
[0054] In some embodiments, the monomer components constituting the polymer (PB) may include one or more selected from (meth)acrylic acid alkyl esters having an alkyl group at the ester terminal as the above-mentioned other monomers. Hereinafter, (meth)acrylic acid alkyl esters having a linear or branched alkyl group with a carbon number of not less than X and not more than Y at the ester terminal may be expressed as “(meth)acrylic acid C X-Y The monomer components constituting the polymer (PB) preferably contain at least (meth)acrylic acid C 1-20 As the other monomer, alkyl esters more preferably include (meth) acrylic acid C 4-20 As the other monomer, the alkyl ester further preferably contains (meth) acrylic acid C 4-18 Alkyl esters (e.g., acrylic acid C 4-9 Alkyl ester) as the above other monomer.
[0055] As (meth)acrylic acid C 1-20 Specific non-limiting examples of the alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like. As particularly preferred (meth) alkyl esters, n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isononyl acrylate, etc. can be cited. As other specific examples of (meth) alkyl esters that can be preferably used, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA), etc. can be cited. The (meth) alkyl ester can be used alone or in combination of two or more. The monomer components constituting the polymer (PB) can also contain one or more selected from the copolymerizable monomers described later as the above-mentioned other monomers.
[0056] The weight average molecular weight (Mw) of the polymer (PB) is not particularly limited, and may be, for example, 0.5×10 4 ~500×104 From the viewpoint of the cohesiveness of the photo-crosslinkable adhesive, the handleability of the adhesive sheet having the photo-crosslinkable adhesive, etc., in some embodiments, the Mw of the polymer (PB) is generally 1×10 4 The above is appropriate, preferably 5×10 4 Above, it can be 10×10 4 Above, it can be 15×10 4 Above, it can be 20×10 4 In addition, from the viewpoint of the surface shape conformability of the photo-crosslinkable adhesive to the adherend (for example, an optical member), the Mw of the polymer (PB) contained in the photo-crosslinkable adhesive is usually 200×10 4 The following are suitable, preferably 150×10 4 Below, it can be 100×10 4 Below, it can be 70×10 4 Below, it can be 50×10 4 the following.
[0057] It should be noted that, in this specification, the weight average molecular weight (Mw) of a polymer refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (column: TSKgelGMH-H (S), manufactured by TOSOH) can be used.
[0058] In the technology disclosed herein, the glass transition temperature (Tg) of the polymer (PB) is not particularly limited. The Tg of the polymer (PB) may be, for example, above -80°C and below 150°C, above -80°C and below 50°C, or above -80°C and below 10°C. From the viewpoint of the surface shape followability of the adhesive layer, in some embodiments, it is appropriate that the Tg of the polymer (PB) is lower than 0°C, preferably below -10°C, below -20°C, below -30°C, below -40°C, or below -50°C. In addition, from the viewpoint of the cohesion of the photo-crosslinkable adhesive and the deformation resistance after photo-crosslinking (for example, the durability of adhesion to the adherend), it is generally advantageous that the Tg of the polymer (PB) is above -75°C, and may be above -70°C. In some embodiments, the Tg of the polymer (PB) may be above -55°C, or may be above -45°C. The Tg of the polymer (PB) can be adjusted by the type and amount of the monomer components constituting the polymer (PB).
[0059] Here, in this specification, the glass transition temperature (Tg) of a polymer refers to the glass transition temperature obtained by the Fox formula based on the composition of the monomer components constituting the polymer. As shown below, the above Fox formula is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each monomer constituting the copolymer.
[0060] 1 / Tg=Σ(Wi / Tgi)
[0061] It should be noted that, in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).
[0062] As the glass transition temperature of the homopolymer used for calculation of Tg, the value described in the known document is used. For example, regarding the monomers listed below, as the glass transition temperature of the homopolymer of the monomer, the following value is used.
[0063]
[0064]
[0065] Regarding the glass transition temperature of homopolymers of monomers other than those exemplified above, the values recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. When multiple values are recorded in the document, the highest value is adopted. Regarding monomers whose homopolymer glass transition temperatures are not recorded in the above-mentioned Polymer Handbook, the values obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 are used. It should be noted that for polymers for which a nominal value of the glass transition temperature is provided by a manufacturer, the nominal value can be adopted.
[0066] For the polymer (PB) in the technology disclosed herein, it is preferred that the polymer contains, for example, about 0.5 mg or more of a benzophenone structure in terms of 4-benzoylphenyl acrylate per 1 g of the polymer. Hereinafter, the value obtained by converting the number of benzophenone structures contained in 1 g of the polymer (PB) into an amount converted in terms of 4-benzoylphenyl acrylate is sometimes referred to as the BP equivalent of the polymer (PB) (unit: mg / g). For example, when 40 μmol of a benzophenone structure is contained per 1 g, the BP equivalent of the polymer is calculated to be 10 mg / g.
[0067] From the perspective of obtaining a higher photocrosslinking effect (for example, the effect of improving deformation resistance by photocrosslinking), in some embodiments, the BP equivalent of the polymer (PB) is generally appropriate to be 1 mg / g or more, and can be 5 mg / g or more, 8 mg / g or more, 10 mg / g or more, 15 mg / g or more, or 20 mg / g or more. In addition, in some embodiments, from the perspective of improving the impact resistance and peel strength of the joint formed by the photocrosslinked product, the BP equivalent of the polymer (PB) is generally appropriate to be 100 mg / g or less, and can be 80 mg / g or less, 60 mg / g or less, 40 mg / g or less, 25 mg / g or less, or 15 mg / g or less. The BP equivalent of the polymer (PB) can be adjusted by the composition of the monomer components constituting the polymer (PB).
[0068] The weight ratio of the polymer (PB) in the B-type B layer, that is, the weight fraction of the polymer (PB) in the photo-crosslinkable adhesive constituting the B-type B layer is not particularly limited, and can be set in a manner that is ideally balanced between the surface shape followability of the photo-crosslinkable adhesive and the deformation resistance of its photo-crosslinked product. In some embodiments, the weight fraction of the above-mentioned polymer (PB) can be, for example, 1% by weight or more, and 5% by weight or more is usually appropriate, and can be 10% by weight or more, 15% by weight or more, 25% by weight or more, 35% by weight or more, 45% by weight or more, or 55% by weight or more. If the weight fraction of the polymer (PB) increases, there is a tendency for the ΔG' described later to increase. The technology disclosed herein can also be implemented in a manner in which the weight fraction of the polymer (PB) in the photo-crosslinkable adhesive is substantially 100% by weight (for example, 99.5% by weight or more). In addition, from the perspective of the adjustability of adhesive performance and the ease of VOC reduction, in some embodiments, the weight fraction of the polymer (PB) in the photo-crosslinkable adhesive can be, for example, lower than 99 weight %, lower than 95 weight %, lower than 85 weight %, lower than 70 weight %, lower than 50 weight %, or lower than 40 weight %.
[0069] For the photo-crosslinkable adhesive constituting the B-type B layer, it is preferred that the photo-crosslinkable adhesive contains, for example, about 0.1 mg or more of a benzophenone structure calculated as 4-benzoylphenyl acrylate per 1 g of the photo-crosslinkable adhesive. Hereinafter, the weight of the benzophenone structure contained in 1 g of the photo-crosslinkable adhesive calculated as 4-benzoylphenyl acrylate is sometimes referred to as the BP equivalent of the photo-crosslinkable adhesive (unit: mg / g). From the viewpoint of obtaining a higher photo-crosslinking effect (for example, the effect of improving deformation resistance by photo-crosslinking), in some embodiments, the BP equivalent of the photo-crosslinkable adhesive is generally appropriate to be 0.3 mg / g or more, and may be 0.5 mg / g or more, 1 mg / g or more, 5 mg / g or more, 8 mg / g or more, 10 mg / g or more, or 20 mg / g or more. In addition, in some embodiments, from the perspective of impact resistance of the joint formed by the photocrosslinked product and strain suppression within the photocrosslinked product, the BP equivalent of the photocrosslinkable adhesive is generally appropriate to be 100 mg / g or less, and can be 80 mg / g or less, 60 mg / g or less, 40 mg / g or less, 25 mg / g or less, or 15 mg / g or less.
[0070] The photo-crosslinkable adhesive constituting the type B layer may be a cured product of an adhesive composition containing a benzophenone structure component. The photo-crosslinkable adhesive may also be a cured product of an adhesive composition containing a benzophenone structure component and an ethylenically unsaturated compound not having a benzophenone structure.
[0071] For the above-mentioned adhesive composition, as the above-mentioned benzophenone-containing structural component, it can include one or more monomers selected from the above-mentioned ethylenically unsaturated BP, it can also include a pre-synthesized polymer (PB), and it can also include both. The polymer (PB) contained in the photo-crosslinkable adhesive constituting the B-type B layer can be, for example, the polymer (PB) contained in the above-mentioned adhesive composition or a modified product thereof, or it can be a polymer formed by copolymerizing the ethylenically unsaturated BP contained in the above-mentioned adhesive composition with other monomers.
[0072] The photocrosslinkable adhesive disclosed herein may be a photocrosslinkable adhesive comprising two or more polymers having different monomer compositions, and at least one of the two or more polymers is the polymer (PB). For the photocrosslinkable adhesive, as the two or more polymers, only two or more polymers (PB) may be included, or a polymer (hereinafter also referred to as "polymer (PNB)") and a polymer (PB) may be combined. The polymer (PNB) may be formed by using an adhesive composition comprising an ethylenically unsaturated compound that does not have a benzophenone structure and polymerizing the ethylenically unsaturated compound. From the viewpoint of compatibility, etc., the polymer (PB) and the polymer (PNB) are preferably both acrylic polymers.
[0073] The polymer (PNB) may be an acrylic oligomer described below. The photo-crosslinkable adhesive containing the acrylic oligomer may be, for example, a cured product of an adhesive composition containing the acrylic oligomer.
[0074] The two or more polymers may be chemically bonded or not. Some embodiments of the photo-crosslinkable adhesive may include at least one polymer (PB) in a form that is not chemically bonded to a polymer other than the polymer (PB). The photo-crosslinkable adhesive may form a photo-crosslinked product in which the polymer (PB) is chemically bonded to a polymer other than the polymer (PB) by photo-crosslinking the benzophenone structure of the polymer (PB).
[0075] The photo-crosslinkable adhesive disclosed herein may contain other components useful for an adhesive as needed. A photo-crosslinkable adhesive containing such optional components may be formed using an adhesive composition having a corresponding composition.
[0076] (VOC emission)
[0077] The VOC emission of the photocrosslinkable adhesive constituting the B-type B layer is not particularly limited. The above-mentioned VOC emission can be, for example, less than 5000 μg / g, less than 3000 μg / g, or less than 1000 μg / g. In some embodiments, the VOC emission of the photocrosslinkable adhesive is preferably less than 500 μg / g, more preferably less than 300 μg / g, and further preferably less than 100 μg / g. Photocrosslinkable adhesives with low VOC emission are low in odor and are preferred from the perspective of environmental hygiene. Low VOC emission of the photocrosslinkable adhesive is also preferred from the perspective of suppressing foaming caused by volatile organic compounds (VOCs) in the photocrosslinkable adhesive and low pollution. For the VOC emission of the photocrosslinkable adhesive, an appropriate amount of the photocrosslinkable adhesive (for example, about 1 mg to 2 mg) can be used as a measurement sample and measured by the following method. It should be noted that the thickness of the measurement sample is preferably less than 1 mm.
[0078] [VOC measurement test]
[0079] Place the measurement sample in a 20 mL vial and cover it tightly. Next, heat the vial at 80°C for 30 minutes, and use a headspace autosampler (HSS) to inject 1.0 mL of the heated gas (sample gas) into a gas chromatography (GC) measuring device. Based on the obtained gas chromatogram, the amount of gas generated by the measurement sample is calculated in the form of an amount converted to n-decane. The VOC emission amount (μg / g) per 1 g of the measurement sample is calculated from the obtained value. It should be noted that the amount converted to n-decane is calculated by treating the detection intensity of the generated gas obtained by GC Mass as the detection intensity of n-decane and applying a pre-made standard curve for n-decane. The settings of HSS and GC are as follows.
[0080] HSS: Model "7694" manufactured by Agilent Technologies
[0081] Heating time: 30 minutes
[0082] Pressurization time: 0.12 minutes
[0083] Loop filling time: 0.12 minutes
[0084] Ring equilibration time: 0.05 minutes
[0085] Injection time: 3 minutes
[0086] Sample ring temperature: 160°C
[0087] Transmission line temperature: 200°C
[0088] GC device: Model "6890" manufactured by Agilent Technologies
[0089] Column: J&W capillary column manufactured by GL Science, trade name "DB-WAP" (inner diameter 0.533 mm × length 30 m, film thickness 1.0 μm)
[0090] Column temperature: 250°C (increase temperature from 40°C to 90°C at 10°C / min, then continue to increase temperature to 250°C at 20°C / min and maintain for 5 minutes)
[0091] Column pressure: 24.3kPa (constant flow mode)
[0092] Carrier gas: Helium (5.0mL / min)
[0093] Inlet: split (split ratio is 12:1)
[0094] Inlet temperature: 250℃
[0095] Detector: FID
[0096] Detector temperature: 250°C
[0097] Unreacted products of ethylenically unsaturated compounds that may be present in the adhesive (e.g., unpolymerized acrylic monomers. Hereinafter, also referred to as "residual monomers") may be an important factor in increasing the VOC emission of the adhesive. The photocrosslinkable adhesive disclosed herein may be a photocrosslinkable adhesive in which the content of residual monomers is suppressed to a level that satisfies any of the above-mentioned VOC emission amounts. The photocrosslinkable adhesive disclosed herein has a structure in which the amount of residual monomers is limited as described above, and can utilize the benzophenone structure of the polymer (BP) to form new crosslinks in the system, thereby being able to improve the deformation resistance of the adhesive layer.
[0098] It should be noted that the VOC emission of the photo-crosslinkable adhesive disclosed in this article is preferably as low as possible in principle, but from practical viewpoints such as productivity and cost, in some embodiments, the above-mentioned VOC emission can be, for example, 10 μg / g or more, 30 μg / g or more, 80 μg / g or more, 150 μg / g or more, or 200 μg / g or more.
[0099] (Gel fraction)
[0100] The gel fraction of the photo-crosslinkable adhesive constituting the B-type B layer is not particularly limited, but from the viewpoints of the cohesiveness of the photo-crosslinkable adhesive, the operability of the adhesive sheet, etc., it is usually appropriate to be 5% or more, preferably 15% or more, 25% or more, or 35% or more. The gel fraction of the photo-crosslinkable adhesive is in principle 100% or less. In addition, from the viewpoint of the ability to follow the surface shape of the adherend, the gel fraction of the photo-crosslinkable adhesive is preferably less than 85%, less than 70%, less than 55%, or less than 40%.
[0101] The gel fraction can be measured by the following method. That is, about 0.5 g of the sample is accurately weighed and its weight is referred to as W1. The sample is wrapped in a porous PTFE (polytetrafluoroethylene) sheet, immersed in ethyl acetate at room temperature for 1 week, and then dried. The weight W2 of the component insoluble in ethyl acetate is measured, and W1 and W2 are substituted into the following formula to calculate the gel fraction.
[0102] Gel fraction (%) = W2 / W1×100
[0103] As the porous PTFE sheet, a product of Nitto Denko Corporation, trade name "NITOFLON NTF1122" or an equivalent product thereof can be used.
[0104] In some embodiments, a high pressure mercury lamp is used to irradiate the photo-crosslinkable adhesive constituting the type B layer with ultraviolet light (for example, at an illumination of 300 mW / cm 2 , cumulative light intensity is 10000mJ / cm 2 The gel fraction of the photocrosslinked product obtained by irradiating the photopolymer with ultraviolet light (e.g., ultraviolet light) can be, for example, 70% or more, preferably 90% or more, 95% or more, or 98% or more. The gel fraction of the photocrosslinked product is in principle 100% or less. The gel fraction can be measured by the above-mentioned method.
[0105] For the photo-crosslinkable adhesive containing the polymer (PB), for example, photo-crosslinking can be performed by irradiating ultraviolet rays containing a wavelength component that can excite the benzophenone structure. It is preferred to use a light source that can irradiate ultraviolet rays containing a component with a wavelength lower than 300nm. Examples of the light source include high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, and ultra-UV lamps, but are not limited to these. The light irradiated by the above light source may also contain a component with a wavelength of more than 300nm.
[0106] It should be noted that as a light source that can irradiate ultraviolet rays that do not contain a wavelength component (for example, a component with a wavelength lower than 300 nm) that can excite a benzophenone structure or a small amount of such a wavelength component, a black light lamp, a UV-LED lamp, etc. can be cited. These light sources can be preferably used as a light source for causing a reaction (polymerization reaction or curing reaction) of an ethylenically unsaturated group by light irradiation performed in the presence of a benzophenone structure. In the ultraviolet irradiation for causing an ethylenically unsaturated group to react, a photoinitiator described later can be used to promote the reaction.
[0107] The photo-crosslinkable adhesive constituting the B-type B layer may be a composition that is substantially free of a photoinitiator that generates free radicals by absorbing light with a wavelength of more than 300 nm, for example, it may be a composition that is substantially free of a photoinitiator that generates free radicals by absorbing visible light of more than 380 nm (especially more than 400 nm). This is advantageous from the perspective of the optical properties of the photo-crosslinkable adhesive. It should be noted that the so-called photoinitiator that does not generate free radicals by absorbing light with a wavelength of more than 300 nm refers to the photoinitiator that does not contain the above-mentioned form that can generate free radicals (the above-mentioned form with a site that is cleaved under the action of light), and the cleavage residue of the above-mentioned photoinitiator may be allowed. A preferred embodiment involves a photo-crosslinkable adhesive that is substantially free of a photoinitiator that contains a phosphorus element in the molecule. The photo-crosslinkable adhesive disclosed herein may be a photo-crosslinkable adhesive that is substantially free of a photoinitiator that contains a phosphorus element in the molecule and any substance in the cleavage residue of the photoinitiator.
[0108] (Adhesive composition for forming type B layer)
[0109] According to this specification, an adhesive composition containing a benzophenone-containing structural component can be provided. The adhesive composition can be preferably used for the formation of type B layer B. The adhesive composition can be an adhesive composition in various forms such as an active energy ray-curable adhesive composition, a solvent-based adhesive composition, an aqueous adhesive composition, and a hot melt adhesive composition. In some embodiments, an active energy ray-curable adhesive composition can be preferably used.
[0110] It should be noted that in this specification, the so-called water-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in a solvent (aqueous solvent) with water as the main component. The concept of the so-called water-based adhesive composition here may include a water-dispersible adhesive composition (a composition in the form of an adhesive dispersed in water) and a water-soluble adhesive composition (a composition in the form of an adhesive dissolved in water). In addition, the so-called solvent-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in an organic solvent. The so-called active energy ray-curable adhesive composition refers to an adhesive composition prepared in a manner of curing to form an adhesive (viscoelastic body) using active energy rays such as ultraviolet rays and radiation. The so-called hot-melt adhesive composition refers to an adhesive composition obtained by applying it in a heated molten state and adjusting it to form an adhesive if it is cooled to near room temperature.
[0111] The adhesive composition for forming the B-type B layer may contain a polymer (PB) as the benzophenone-containing structural component, an ethylenically unsaturated BP, or both. When a polymer (PB) is used as a constituent component of the adhesive composition, the same polymer (PB) as that contained in the photo-crosslinkable adhesive constituting the B layer may be used as the polymer (PB), and therefore repeated descriptions are omitted.
[0112] In some embodiments, the adhesive composition may be an acrylic adhesive composition in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the total monomer components constituting the adhesive composition are acrylic monomers. The acrylic adhesive composition may be, for example: an adhesive composition comprising a polymer (PB) and an ethylenically unsaturated compound (B) (preferably an active energy ray-curable adhesive composition); a solvent-based adhesive composition comprising a polymer (PB) (preferably an acrylic polymer) and an ethylenically unsaturated compound (B) in an organic solvent; a hot melt adhesive composition comprising a polymer (PB) as an acrylic polymer as a main component; and the like.
[0113] [Ethylenically unsaturated compound (B)]
[0114] Examples of compounds that can be used as the ethylenically unsaturated compound (B) include the above-mentioned alkyl (meth)acrylates and the above-mentioned ethylenically unsaturated BPs. Among these, it is preferred to use at least an alkyl (meth)acrylate (e.g., C (meth)acrylate). 1-20 Alkyl ester, more preferably (meth) acrylic acid C 4-18 Alkyl ester, more preferably acrylic acid C 4-9As particularly preferred (meth)acrylic acid alkyl esters, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) can be cited. As other specific examples of (meth)acrylic acid alkyl esters that can be preferably used, isononyl acrylate, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA) and the like can be cited. (Meth)acrylic acid alkyl esters can be used alone or in combination of two or more. In some embodiments, the ethylenically unsaturated compound (B) preferably includes any one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), and more preferably includes at least 2EHA.
[0115] In some embodiments, the ethylenically unsaturated compound (B) may contain acrylic acid C in a ratio of 40 wt % or more. 4-9 Alkyl esters. Acrylic acid C 4-9 The proportion of the alkyl ester in the ethylenically unsaturated compound (B) may be, for example, 50% by weight or more, 60% by weight or more, or 65% by weight or more. In addition, from the viewpoint of improving the cohesiveness of the photo-crosslinkable adhesive, the acrylic acid C 4-9 The proportion of the alkyl ester in the ethylenically unsaturated compound (B) is usually appropriately 99.5% by weight or less, and may be 95% by weight or less, 85% by weight or less, 70% by weight or less, or 60% by weight or less.
[0116] As other examples of compounds that can be used as ethylenically unsaturated compounds (B), ethylenically unsaturated compounds (copolymerizable monomers) that can copolymerize with (meth) alkyl acrylates can be cited. As copolymerizable monomers, monomers having polar groups (e.g., carboxyl groups, hydroxyl groups, rings containing nitrogen atoms, etc.) can be preferably used. Monomers having polar groups can help, for example, to introduce crosslinking points into a polymer containing repeating units derived from the monomer, or to improve the cohesive force of a photocrosslinkable adhesive. Copolymerizable monomers can be used alone or in combination of two or more.
[0117] Specific non-limiting examples of the copolymerizable monomer include the following monomers.
[0118] Monomers containing a carboxyl group: for example, acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like.
[0119] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.
[0120] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.
[0121] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.
[0122] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl (meth)acrylate ether, allyl glycidyl ether, and glycidyl (meth)acrylate ether.
[0123] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.
[0124] Monomers containing an isocyanate group: for example, 2-(meth)acryloyloxyethyl isocyanate, (meth)acryloyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and the like.
[0125] Monomers containing amide groups: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and other N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and other N-alkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; monomers having hydroxyl groups and amide groups, such as N-(2-hydroxyethyl) ( N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide and the like; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl(meth)acrylamide, such as N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide; and N,N-dimethylaminopropyl(meth)acrylamide, N-(meth)acrylamide and the like.
[0126] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.
[0127] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.
[0128] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-(meth)acryloylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam).
[0129] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.
[0130] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.
[0131] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.
[0132] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.
[0133] Alkoxy group-containing monomers: for example, alkoxyalkyl (meth)acrylates (alkoxyalkyl (meth)acrylates) such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; and alkoxyalkylene (meth)acrylates (for example, alkoxypolyalkylene glycol (meth)acrylate) such as methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.
[0134] Monomers containing alkoxysilyl groups: for example, (meth)acrylates containing alkoxysilyl groups such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and the like; and vinyl compounds containing alkoxysilyl groups such as vinyltrimethoxysilane and vinyltriethoxysilane.
[0135] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.
[0136] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.
[0137] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.
[0138] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.
[0139] (Meth)acrylates having an alicyclic hydrocarbon group: for example, (meth)acrylates having an alicyclic hydrocarbon group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, and adamantyl (meth)acrylate.
[0140] (Meth)acrylates having an aromatic hydrocarbon group: for example, (meth)acrylates having an aromatic hydrocarbon group, such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate.
[0141] In addition, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates containing halogen atoms such as (meth)acrylates containing vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as silicone (meth)acrylate, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.
[0142] When using such a copolymerizable monomer, its usage amount is not particularly limited, and it is usually appropriate to be more than 0.01% by weight of the overall monomer component constituting the adhesive composition. From the viewpoint of better exerting the use effect of the copolymerizable monomer, the usage amount of the copolymerizable monomer (that is, the weight fraction of the copolymerizable monomer in the above-mentioned overall monomer component) can be more than 0.1% by weight of the overall monomer component, and can be more than 0.5% by weight. In addition, from the viewpoint of easily obtaining the balance of adhesive properties, it is appropriate that the usage amount of the copolymerizable monomer is usually less than 50% by weight of the overall monomer component, preferably less than 40% by weight.
[0143] In some embodiments, the copolymerizable monomer may include a monomer having a nitrogen atom. By using a monomer having a nitrogen atom, the cohesive force of the photocrosslinkable adhesive can be increased, and the peel strength after photocrosslinking can be ideally increased. As a preferred example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a ring containing a nitrogen atom, the monomers exemplified above can be used, for example, N-vinyl cyclic amide represented by general formula (1) can be used.
[0144] [Chemical formula 1]
[0145]
[0146] Here, in the general formula (1), R 1 is a divalent organic group, specifically -(CH2) n-. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone can be preferably used. Another preferred example of the monomer having a nitrogen atom is (meth)acrylamide.
[0147] There is no particular restriction on the amount of monomers with nitrogen atoms (preferably monomers with rings containing nitrogen atoms such as N-vinyl cyclic amides, N-(methyl)acryloyl cyclic amides, etc.), for example, it can be more than 1% by weight of the entire monomer component, it can be more than 2% by weight, it can be more than 3% by weight, and further can be more than 5% by weight or more than 7% by weight. In one embodiment, the amount of monomers with nitrogen atoms can be more than 10% by weight of the entire monomer component, it can be more than 15% by weight, or it can be more than 20% by weight. In addition, it is appropriate that the amount of monomers with nitrogen atoms is less than 40% by weight of the entire monomer component, it can be less than 35% by weight, it can be less than 30% by weight, or it can be less than 25% by weight. In another embodiment, the amount of monomers with nitrogen atoms can be less than 20% by weight of the entire monomer component, for example, or less than 15% by weight.
[0148] In some ways, the copolymerizable monomer may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesive force of the photo-crosslinkable adhesive and the degree of crosslinking (for example, crosslinking based on an isocyanate crosslinking agent) can be appropriately adjusted. The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the entire monomer component, it can be more than 0.1% by weight, it can be more than 0.5% by weight, it can be more than 1% by weight, it can be more than 5% by weight or more than 10% by weight. In addition, from the viewpoint of suppressing the water absorption of the photo-crosslinkable adhesive or its photo-crosslinked product, in some ways, the amount of the monomer containing a hydroxyl group is appropriate for the overall monomer component, for example, less than 40% by weight, it can be less than 30% by weight, it can be less than 25% by weight, it can be less than 20% by weight. In another way, the amount of the monomer containing a hydroxyl group can be less than 15% by weight of the entire monomer component, it can be less than 10% by weight, it can be less than 5% by weight. Alternatively, as the copolymerizable monomer, a monomer containing a hydroxyl group may not be used.
[0149] In some embodiments, the proportion of carboxyl-containing monomers in the overall monomer composition can be, for example, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight (e.g., less than 0.1% by weight). The adhesive composition may not substantially contain carboxyl-containing monomers as its constituent monomer components. Here, the so-called substantially not containing carboxyl-containing monomers means that carboxyl-containing monomers are at least not intentionally used. This will become advantageous from the perspective of the metal corrosion resistance of the photocrosslinkable adhesive formed by the adhesive composition and its photocrosslinked product.
[0150] In some embodiments, the copolymerizable monomer may include a (meth)acrylate containing an alicyclic hydrocarbon group. Thus, the cohesive force of the adhesive can be increased, and the peel strength after photocrosslinking can be increased. As a (meth)acrylate containing an alicyclic hydrocarbon group, the (meth)acrylate containing an alicyclic hydrocarbon group exemplified above can be used, for example, cyclohexyl acrylate and isobornyl acrylate can be preferably used. The amount used when using a (meth)acrylate containing an alicyclic hydrocarbon group is not particularly limited, for example, it can be more than 1% by weight, more than 3% by weight, or more than 5% by weight of the entire monomer component. In one embodiment, the amount of (meth)acrylate containing an alicyclic hydrocarbon group can be more than 10% by weight of the entire monomer component, and can be more than 15% by weight. It is appropriate that the upper limit of the amount of (meth)acrylate containing an alicyclic hydrocarbon group is about 40% by weight or less, for example, it can be less than 30% by weight, and can be less than 25% by weight (for example, less than 15% by weight, and further less than 10% by weight).
[0151] In some embodiments, the copolymerizable monomer may include a monomer containing an alkoxysilyl group. The monomer containing an alkoxysilyl group is typically an ethylenically unsaturated compound having at least one (preferably more than two, for example, two or three) alkoxysilyl group in one molecule, and its specific example is as described above. The above-mentioned monomer containing an alkoxysilyl group can be used alone or in combination of two or more. By using a monomer containing an alkoxysilyl group, a cross-linked structure formed by a condensation reaction of a silanol group (silanol condensation) can be introduced into a photo-crosslinkable adhesive.
[0152] The amount used when using a monomer containing an alkoxysilyl group is not particularly limited. In some embodiments, the amount of the monomer containing an alkoxysilyl group can be, for example, 0.005% by weight or more of the overall monomer component constituting the adhesive composition, and it is usually appropriate to be 0.01% by weight or more, and it can be 0.03% by weight or more, and it can be 0.05% by weight or more. In addition, from the perspective of the surface shape followability of the photocrosslinkable adhesive, the amount of the monomer containing an alkoxysilyl group is usually appropriate to be less than 1.0% by weight of the overall monomer component, and it can be less than 0.5% by weight, and it can be less than 0.1% by weight.
[0153] As other examples of compounds that can be used as the ethylenically unsaturated compound (B), a multifunctional monomer can be cited. According to the adhesive composition containing the multifunctional monomer, by reacting the multifunctional monomer when curing the composition to produce a photo-crosslinkable adhesive, a photo-crosslinkable adhesive formed by crosslinking the multifunctional monomer can be obtained.
[0154] Examples of the polyfunctional monomer include bifunctional monomers such as 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, and divinylbenzene; polyfunctional monomers having three or more functionalities such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; and epoxy acrylates, polyester acrylates, and urethane acrylates. Among them, preferred examples include 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. The polyfunctional monomer may be used alone or in combination of two or more.
[0155] The amount used in the case of using a multifunctional monomer is not particularly limited, and can be set in a manner that forms a photo-crosslinkable adhesive that exerts ideal characteristics in a photo-crosslinkable adhesive. In some ways, the amount of the multifunctional monomer used can be less than 5.0% by weight of the overall monomer component constituting the adhesive composition. Thus, it is possible to avoid forming an excessive crosslinked structure during the formation of the photo-crosslinkable adhesive (i.e., in the stage before photo-crosslinking), thereby improving the surface shape followability of the photo-crosslinkable adhesive. The amount of the above-mentioned multifunctional monomer used, for example, can be less than 4.0% by weight of the overall monomer component, can be less than 3.0% by weight, can be less than 2.0% by weight, can be less than 1.0% by weight, can be less than 0.5% by weight, can be less than 0.3% by weight. It is also possible not to use a multifunctional monomer. In addition, in some ways, from the perspective of imparting appropriate agglomeration to the photo-crosslinkable adhesive, the amount of the multifunctional monomer used relative to the overall monomer component can be, for example, more than 0.001% by weight, can be more than 0.005% by weight, can be more than 0.01% by weight, can be more than 0.03% by weight.
[0156] From the viewpoint of the surface shape following property of the photo-crosslinkable adhesive, in some embodiments, a bifunctional monomer may be preferably used as the multifunctional monomer. The proportion of the bifunctional monomer in the overall multifunctional monomer used may be, for example, 50% by weight or more, 70% by weight or more, 90% by weight or more, or 100% by weight.
[0157] The weight ratio of the polymer (PB) contained in the adhesive composition in the total amount of the polymer (PB) and the ethylenically unsaturated compound (B) is not particularly limited, and can be set in a manner that is ideally balanced between the surface shape followability of the photo-crosslinkable adhesive formed by the adhesive composition and the deformation resistance of its photo-crosslinked product. In some embodiments, the weight fraction of the above-mentioned polymer (PB) can be, for example, 1% by weight or more, and it is usually appropriate to be 5% by weight or more. From the perspective of improving the effect of photo-crosslinking, it can be 10% by weight or more, 15% by weight or more, 25% by weight or more, 35% by weight or more, 45% by weight or more, or 55% by weight or more. In addition, from the perspective of ease of preparation and coating of the adhesive composition, in some embodiments, the weight ratio of the polymer (PB) in the above-mentioned total amount can be, for example, less than 99% by weight, less than 95% by weight, less than 85% by weight, less than 70% by weight, less than 50% by weight, or less than 40% by weight.
[0158] In the adhesive composition disclosed herein, the weight of the organic solvent in the overall weight of the adhesive composition can be, for example, less than 30% by weight, less than 20% by weight is advantageous, preferably less than 10% by weight, and more preferably less than 5% by weight. In some embodiments, the weight ratio of the above-mentioned organic solvent can be less than 3% by weight, less than 1% by weight, less than 0.5% by weight, less than 0.1% by weight, less than 0.05% by weight, or substantially free of organic solvent. From the perspective of reducing the VOC of the photo-crosslinkable adhesive formed by the adhesive composition, it is preferred to suppress the weight ratio of the organic solvent in the adhesive composition. The adhesive composition disclosed herein also includes an ethylenically unsaturated compound (B) in addition to the polymer (PB) (A), and therefore, the ethylenically unsaturated compound (B) can be used as a diluent for the polymer (PB) (A). Therefore, even in an adhesive composition that contains a polymer (PB) (A) having a certain Mw or more in an amount greater than a certain level, an organic solvent is not required to improve the coating properties of the adhesive composition in a normal temperature range (e.g., 20°C to 40°C), or the amount of the organic solvent used can be reduced.
[0159] In some embodiments of the adhesive composition disclosed herein, for the adhesive composition, from the viewpoint of the coating properties in the above-mentioned normal temperature range, the viscosity (BH type viscometer, No. 5 rotor, measured at 10 rpm and a measuring temperature of 30°C. The same below) is appropriately 1000 Pa·s or less, preferably 100 Pa·s or less, and more preferably 50 Pa·s or less. The viscosity of the above-mentioned adhesive composition can be, for example, 30 Pa·s or less, 20 Pa·s or less, 10 Pa·s or less, or 5 Pa·s or less. The lower limit of the viscosity of the adhesive composition is not particularly limited, but from the viewpoint of suppressing the depression of the adhesive composition within the coating range and the overflow of the adhesive composition at the outer edge of the coating range, it is generally appropriate to be 0.1 Pa·s or more, and can be 0.5 Pa·s or more, or 1 Pa·s or more.
[0160] The adhesive composition of some embodiments includes at least a compound having one ethylenically unsaturated group (i.e., a monofunctional monomer) (B1) as the ethylenically unsaturated compound (B). The monofunctional monomer (B1) can be selected from the examples of the ethylenically unsaturated compound (B) described above. The monofunctional monomer (B1) can be used alone or in combination of two or more.
[0161] In the total amount of the polymer (PB) and the ethylenically unsaturated compound (B), the weight proportion of the monofunctional monomer (B1) can be, for example, 1% by weight or more, 5% by weight or more, or 15% by weight or more. In some embodiments, from the perspective of the ease of preparation and coating of the adhesive composition, the weight proportion of the monofunctional monomer (B1) can be 25% by weight or more, 35% by weight or more, or 45% by weight or more. In addition, the weight proportion of the monofunctional monomer (B1) in the total amount can be, for example, 99% by weight or less, usually 95% by weight or less is appropriate, can be 85% by weight or less, can be 75% by weight or less, can be 65% by weight or less, can be 55% by weight or less, or can be 45% by weight or less.
[0162] In the embodiment in which the adhesive composition includes a monofunctional monomer (B1), the glass transition temperature (Tg) obtained by the Fox equation based on the composition of the monofunctional monomer (B1) is not particularly limited, and may be, for example, -80°C or higher and 250°C or lower. The Tg based on the composition of the monofunctional monomer (B1) is generally preferably 150°C or lower, 100°C or lower, 70°C or lower, 50°C or lower, or 30°C or lower, from the viewpoint of compatibility of the polymer derived from the monofunctional monomer (B1) with other components. In some embodiments, from the viewpoint of the surface shape followability of the photo-crosslinkable adhesive, the Tg based on the composition of the monofunctional monomer (B1) is preferably lower than 0°C, more preferably -10°C or lower, -20°C or lower, -30°C or lower, or -40°C or lower. In addition, from the viewpoint of the cohesion of the photo-crosslinkable adhesive and the deformation resistance after photo-crosslinking (for example, the durability of adhesion to the adherend), the Tg based on the composition of the monofunctional monomer (B1) is usually advantageously -60°C or higher, and may be -54°C or higher, -50°C or higher, -45°C or higher, -35°C or higher, or -25°C or higher. The above Tg can be adjusted by the compound used as the monofunctional monomer (B1) and their usage ratio.
[0163] In the adhesive composition comprising the polymer (PB) and the monofunctional monomer (B1), the photocrosslinkable adhesive formed from the adhesive composition, and the photocrosslinked product thereof, the Tg (hereinafter referred to as "Tg A ”) and the Tg (hereinafter, also referred to as Tg B1 ".) can be obtained by Tg B1 [℃]-Tg A[°C] The calculated Tg difference [°C] (hereinafter also referred to as ΔTg) is set in a range of, for example, -50°C or more and 70°C or less. It is advantageous from the perspective of compatibility in the photo-crosslinkable adhesive and its photo-crosslinked product if the absolute value of the above Tg difference is not too large. In some embodiments, ΔTg may be, for example, -10°C or more, preferably 0°C or more, 7°C or more, 10°C or more, 20°C or more, or 30°C or more.
[0164] The adhesive composition of some embodiments comprises at least a compound having two or more ethylenically unsaturated groups (i.e., a multifunctional monomer) (B2) as the above-mentioned ethylenically unsaturated compound (B). The multifunctional monomer (B2) can be used alone or in combination of two or more from the examples of the above-mentioned multifunctional monomers. The amount of the multifunctional monomer (B2) can be set in the same manner as the proportion of the multifunctional monomer in the overall monomer components constituting the adhesive composition.
[0165] In the method of using a monofunctional monomer (B1) and a polyfunctional monomer (B2) as an ethylenically unsaturated compound (B), the weight ratio of the monofunctional monomer (B1) in the ethylenically unsaturated compound (B) can be, for example, 1% by weight or more, and it is usually appropriate to be 25% by weight or more, and it can be 50% by weight or more, 75% by weight or more, 95% by weight or more, or 99% by weight or more. In addition, the weight ratio of the monofunctional monomer (B1) in the ethylenically unsaturated compound (B) can be, for example, 99.9% by weight or less, and can be 99.8% by weight or less.
[0166] In the adhesive composition disclosed herein, the ethylenically unsaturated compound (B) may be contained in the form of a partial polymer, or the entire amount thereof may be contained in the form of an unreacted monomer. A preferred embodiment relates to an adhesive composition that contains the ethylenically unsaturated compound (B) in the form of a partial polymer. There is no particular limitation on the polymerization method for partially polymerizing the ethylenically unsaturated compound (B), and various polymerization methods known in the past may be appropriately selected and used, such as: photopolymerization by irradiation with light such as ultraviolet rays; radiation polymerization by irradiation with radiation such as beta rays and gamma rays; thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization; and the like. From the viewpoint of efficiency and simplicity, photopolymerization may be preferably used. According to photopolymerization, the polymerization conversion rate (monomer conversion) can be easily controlled by polymerization conditions such as the amount of light irradiation (amount of light).
[0167] The polymerization conversion rate of the ethylenically unsaturated compound (B) in the above-mentioned partial polymer is not particularly limited. From the viewpoint of the ease of preparation and coating of the adhesive composition, the above-mentioned polymerization conversion rate is usually about 50% by weight or less, preferably about 40% by weight or less (for example, about 35% by weight or less). The lower limit of the polymerization conversion rate is not particularly limited, and is typically about 1% by weight or more, and is usually about 5% by weight or more.
[0168] The adhesive composition containing a partial polymer of an ethylenically unsaturated compound (B) can be obtained, for example, by the following method: using an appropriate polymerization method (e.g., photopolymerization method) to partially polymerize a monomer mixture containing the entire amount of the ethylenically unsaturated compound (B) used to prepare the adhesive composition. In addition, the adhesive composition containing a partial polymer of an ethylenically unsaturated compound (B) can be a mixture of a partial polymer of a monomer mixture containing a portion of the ethylenically unsaturated compound (B) used to prepare the adhesive composition and the remaining ethylenically unsaturated compound (B) or its partial polymer. It should be noted that in this specification, the so-called "complete polymer" refers to a polymerization conversion rate higher than 95% by weight.
[0169] The above-mentioned partial polymer can be prepared, for example, by irradiating ultraviolet light to an ethylenically unsaturated monomer. When the above-mentioned partial polymer is prepared in the presence of a polymer (PB), the ultraviolet light irradiation conditions can be set in such a way that the ethylenically unsaturated group reacts and the benzophenone structure is not excited by light, thereby obtaining an adhesive composition comprising a partial polymer of an ethylenically unsaturated monomer and a polymer (PB). As a light source, a light source such as the above-mentioned black light lamp, UV-LED lamp, etc. that can irradiate ultraviolet light that does not contain a component with a wavelength less than 300nm or has a small amount of such a wavelength component can be preferably used.
[0170] Alternatively, the adhesive composition may be prepared by preparing a partial polymer of the ethylenically unsaturated compound (B) in advance and then mixing the partial polymer with the polymer (PB). When the partial polymer is prepared by irradiating the ethylenically unsaturated monomer with ultraviolet light in the absence of a component containing a benzophenone structure, the ultraviolet light source may be a light source that does not excite the benzophenone structure or a light source that excites the benzophenone structure.
[0171] When preparing a partial polymer of an ethylenically unsaturated compound (B), the reaction of the ethylenically unsaturated group can be promoted by using a photoinitiator. As a photoinitiator, a ketal photoinitiator, an acetophenone photoinitiator, a benzoin ether photoinitiator, an acylphosphine oxide photoinitiator, an α-ketol photoinitiator, an aromatic sulfonyl chloride photoinitiator, a photoactive oxime photoinitiator, a benzoin photoinitiator, a benzyl photoinitiator, a benzophenone photoinitiator, an alkylphenone photoinitiator, a thioxanthone photoinitiator, etc. can be used. It is preferred to use a photoinitiator that absorbs light with a wavelength of more than 300nm (for example, light with a wavelength of more than 300nm and less than 500nm) to generate free radicals. The photoinitiator can be used alone or in combination of two or more.
[0172] 〔Photoinitiator (C)〕
[0173] In the adhesive composition for forming the B-type B layer, a photoinitiator (C) may be contained as needed for the purpose of improving or imparting photocurability. As the photoinitiator, a ketal photoinitiator, an acetophenone photoinitiator, a benzoin ether photoinitiator, an acylphosphine oxide photoinitiator, an α-ketol photoinitiator, an aromatic sulfonyl chloride photoinitiator, a photoactive oxime photoinitiator, a benzoin photoinitiator, a benzyl photoinitiator, a benzophenone photoinitiator, an alkylphenone photoinitiator, a thioxanthone photoinitiator, etc. may be used. One type of the photoinitiator may be used alone or two or more types may be used in appropriate combination.
[0174] Specific examples of the ketal-based photoinitiator include 2,2-dimethoxy-1,2-diphenylethane-1-one and the like.
[0175] Specific examples of acetophenone-based photoinitiators include 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, 4-tert-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, methoxyacetophenone, and the like.
[0176] Specific examples of the benzoin ether-based photoinitiator include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether.
[0177] Specific examples of the acylphosphine oxide-based photoinitiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the like.
[0178] Specific examples of α-ketol photoinitiators include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one, etc. Specific examples of aromatic sulfonyl chloride photoinitiators include 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime photoinitiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin photoinitiators include benzoin, etc. Specific examples of benzyl photoinitiators include benzyl, etc.
[0179] Specific examples of the benzophenone-based photoinitiator include benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenylketone.
[0180] Specific examples of the thioxanthone-based photoinitiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0181] As the photoinitiator (C) contained in the adhesive composition, a photoinitiator that generates free radicals by absorbing light with a wavelength of 300 nm or more (e.g., light with a wavelength of 300 nm or more and 500 nm or less) can be preferably used. One photoinitiator can be used alone or two or more photoinitiators can be used in appropriate combination. In some embodiments, a photoinitiator that does not contain a phosphorus element in the molecule can be preferably used. The adhesive composition disclosed herein can be an adhesive composition that does not substantially contain a photoinitiator that contains a phosphorus element in the molecule.
[0182] The content of the photoinitiator in the adhesive composition is not particularly limited and can be set in a manner that the desired effect is suitably exerted. In some embodiments, the content of the photoinitiator can be, for example, about 0.005 parts by weight or more, usually 0.01 parts by weight or more is appropriate, preferably 0.05 parts by weight or more, can be 0.10 parts by weight or more, can be 0.15 parts by weight or more, can be 0.20 parts by weight or more, relative to 100 parts by weight of the monomer component constituting the adhesive composition. By increasing the content of the photoinitiator, the photocurability of the adhesive composition is improved. In addition, the content of the photoinitiator relative to 100 parts by weight of the monomer component constituting the adhesive composition is usually 5 parts by weight or less, preferably 2 parts by weight or less, can be 1 part by weight or less, can be 0.7 parts by weight or less, can be 0.5 parts by weight or less. The situation where the content of the photoinitiator is not too much will become advantageous from the viewpoint of inhibiting the gelation of the adhesive composition.
[0183] 〔Cross-linking agent〕
[0184] In the adhesive composition, known crosslinking agents such as isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, hydrazine crosslinking agents, and amine crosslinking agents can be used as needed. Peroxides can also be used as crosslinking agents. These crosslinking agents can be used alone or in combination of two or more. The photo-crosslinkable adhesive formed by the adhesive composition containing the crosslinking agent preferably contains the crosslinking agent mainly in the form after the crosslinking reaction. By using a crosslinking agent, the cohesive force of the photo-crosslinkable adhesive can be appropriately adjusted.
[0185] Specific examples of the crosslinking agent that can be used in the adhesive composition for forming the type B B layer are substantially the same as specific examples of the crosslinking agent that can be used in the adhesive composition for forming the type D B layer described later, and therefore repeated descriptions are omitted.
[0186] The amount used when using a cross-linking agent (the total amount of the cross-linking agents when using more than two cross-linking agents) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as bonding force and cohesive force in a well-balanced manner, it is appropriate that the amount of the cross-linking agent used is usually about 5 parts by weight or less relative to 100 parts by weight of the monomer component constituting the adhesive composition, which can be less than 3 parts by weight, less than 1 part by weight, less than 0.50 parts by weight, less than 0.30 parts by weight, or less than 0.20 parts by weight. The lower limit of the amount of the cross-linking agent used is not particularly limited, and it is an amount greater than 0 parts by weight relative to 100 parts by weight of the monomer component constituting the adhesive composition. In some ways, the amount of the cross-linking agent used can be, for example, more than 0.001 parts by weight, more than 0.01 parts by weight, more than 0.05 parts by weight, or more than 0.10 parts by weight relative to 100 parts by weight of the monomer component constituting the adhesive composition.
[0187] 〔Chain transfer agent〕
[0188] The adhesive composition may contain various chain transfer agents known in the past. As the chain transfer agent, thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, thioglycolic acid, and α-thioglycerol can be used. Alternatively, a chain transfer agent that does not contain a sulfur atom (non-sulfur chain transfer agent) can also be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenes such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having benzylidene groups such as dibenzylideneacetone, cinnamyl alcohol, and cinnamaldehyde; hydroquinones such as hydroquinone and dihydroxynaphthalene; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; benzyl hydrogens such as diphenylbenzene and triphenylbenzene; and the like. The chain transfer agent can be used alone or in combination of two or more. When a chain transfer agent is used, the amount used may be, for example, about 0.01 to 1 part by weight based on 100 parts by weight of the monomer component. The technology disclosed herein may also be preferably implemented without using a chain transfer agent.
[0189] (Acrylic oligomer)
[0190] In the photo-crosslinkable adhesive constituting the B layer, an acrylic oligomer may be contained from the viewpoints of improving cohesive force, improving adhesion to an adjacent surface (which may be an adjacent sub-adhesive layer (e.g., A layer), a substrate surface in an adhesive sheet with a substrate, etc.). The B layer containing the acrylic oligomer may preferably be formed using an adhesive composition containing the acrylic oligomer. As the acrylic oligomer used in the B-type B layer, an acrylic oligomer having a higher Tg than the Tg of the above-mentioned polymer (PB) may preferably be used.
[0191] The Tg of the acrylic oligomer is not particularly limited, and may be, for example, above about 20°C and below 300°C. The Tg may be, for example, above about 30°C, above about 40°C, above about 60°C, above about 80°C, or above about 100°C. If the Tg of the acrylic oligomer becomes higher, the effect of improving the cohesive force tends to be generally better. In addition, from the viewpoint of compatibility, the Tg of the acrylic oligomer may be, for example, below about 250°C, below about 200°C, below about 180°C, or below about 150°C. It should be noted that the Tg of the acrylic oligomer is the same as the glass transition temperature of the above-mentioned polymer (PB), and is a value calculated based on the Fox formula.
[0192] The Mw of the acrylic acid oligomer is not particularly limited, and can be, for example, about 1000 or more, and generally about 1500 or more is appropriate, can be about 2000 or more, and can be about 3000 or more. In addition, the Mw of the acrylic acid oligomer can be, for example, less than about 30000, and generally less than about 10000 is appropriate, can be less than about 7000, and can be less than about 5000. If the Mw is within the above range, it is easy to appropriately exert the effect of improving the cohesion of the B layer and the adhesion to the adjacent surface. The Mw of the acrylic acid oligomer can be measured by gel permeation chromatography (GPC) and obtained as a value converted to standard polystyrene. Specifically, for example, it can be measured in HPLC8020 manufactured by TOSOH using TSKgelGMH-H (20) × 2 roots as columns in a tetrahydrofuran solvent at a flow rate of about 0.5 mL / min.
[0193] As the monomer components constituting the acrylic oligomer, the following (meth)acrylate monomers can be mentioned: the various (meth)acrylate monomers mentioned above; 1-20 Alkyl esters; the above-mentioned various alicyclic hydrocarbon group-containing (meth)acrylates; the above-mentioned various aromatic hydrocarbon group-containing (meth)acrylates; (meth)acrylates obtained from terpene compound derivative alcohols; etc. These can be used alone or in combination of two or more.
[0194] From the viewpoint of improving adhesiveness, the acrylic oligomer preferably contains, as monomer units, acrylic monomers having a relatively bulky structure, represented by (meth)acrylic acid alkyl esters having a branched alkyl group, such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; (meth)acrylic acid esters containing alicyclic hydrocarbon groups; (meth)acrylic acid esters containing aromatic hydrocarbon groups, etc. In addition, when ultraviolet rays are used when synthesizing acrylic oligomers or when preparing adhesive layers, monomers having a saturated hydrocarbon group at the ester terminal are preferred from the viewpoint of not easily causing polymerization inhibition, for example, (meth)acrylic acid alkyl esters having a branched alkyl group and (meth)acrylic acid esters containing saturated alicyclic hydrocarbon groups can be preferably used.
[0195] The proportion of the (meth)acrylate monomer in all monomer components constituting the acrylic oligomer is typically higher than 50% by weight, preferably 60% by weight or more, and more preferably 70% by weight or more (e.g. 80% by weight or more, and further 90% by weight or more). In a preferred embodiment, the acrylic oligomer has a monomer composition that substantially contains only one or more (meth)acrylate monomers. The monomer components contain (meth)acrylate containing an alicyclic hydrocarbon group and (meth)acrylic acid C 1-20In the case of alkyl esters, the weight ratio of these is not particularly limited. In some embodiments, the (meth)acrylate containing an alicyclic hydrocarbon group / (meth)acrylic acid C 1-20 The weight ratio of the alkyl ester may be, for example, 10 / 90 or more, 20 / 80 or more, or 30 / 70 or more, and may be 90 / 10 or less, 80 / 20 or less, or 70 / 30 or less.
[0196] As the monomer components constituting the acrylic oligomer, in addition to the above-mentioned (meth) acrylate monomers, monomers containing functional groups can also be used as needed. As monomers containing functional groups, monomers having heterocyclic rings containing nitrogen atoms such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine can be cited; monomers containing amino groups such as (meth) acrylic acid N,N-dimethylaminoethyl ester; monomers containing amide groups such as N,N-diethyl (meth)acrylamide; monomers containing carboxyl groups such as AA and MAA; monomers containing hydroxyl groups such as (meth) acrylic acid 2-hydroxyethyl ester. These monomers containing functional groups can be used alone or in combination of two or more. When using monomers containing functional groups, the proportion of monomers containing functional groups in all monomer components constituting the acrylic oligomer can be, for example, 1% by weight or more, 2% by weight or more, or 3% by weight or more, and can be, for example, 15% by weight or less, 10% by weight or less, or 7% by weight or less. The acrylic oligomer can also be an acrylic oligomer in which monomers containing functional groups are not used.
[0197] Preferred acrylic oligomers include, for example, homopolymers of dicyclopentanyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), dicyclopentanyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA), copolymers of DCPMA and MMA, copolymers of DCPMA and IBXMA, copolymers of ADA and methyl methacrylate (MMA), copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), and copolymers of CHMA and AA.
[0198] Acrylic acid oligomers can be formed by polymerizing the monomer components that constitute them. The polymerization method and polymerization mode are not particularly limited, and various polymerization methods known in the past (e.g., solution polymerization, emulsion polymerization, bulk polymerization, photopolymerization, radiation polymerization, etc.) can be used in an appropriate manner. The type of polymerization initiator (e.g., azo polymerization initiator) that can be used as required is as exemplified in the description of the polymer (PD) described later about the polymerization for obtaining acrylic acid primary polymers, and the amount of the polymerization initiator and the amount of the chain transfer agent (e.g., mercaptan) that can be used are appropriately set in a manner to obtain the desired molecular weight based on technical common sense, and therefore detailed description is omitted.
[0199] When the acrylic oligomer is contained in the B layer, its content is not particularly limited and can be set in a manner that can obtain the desired effect. In some embodiments, the amount of acrylic oligomer used can be, for example, 0.01% by weight or more of the total monomer components constituting the B layer. From the perspective of obtaining a higher effect, it can be 0.05% by weight or more, 0.1% by weight or more, or 0.2% by weight or more. In addition, from the perspective of the transparency of the adhesive layer, it is appropriate that the amount of acrylic oligomer used is usually less than 50% by weight of the total monomer components constituting the B layer, preferably less than 30% by weight, more preferably less than 25% by weight, less than 10% by weight, less than 5% by weight, less than 1% by weight, or less than 0.5% by weight. It is also possible not to use acrylic oligomers.
[0200] The adhesive composition for forming layer B may contain various common additives in the adhesive field such as tackifier resin (e.g., rosin-based, petroleum-based, terpene-based, phenol-based, ketone-based, etc.), viscosity modifier (e.g., thickener), leveling agent, plasticizer, filler, pigment, dye and other coloring agent, stabilizer, preservative, antioxidant, anti-aging agent as other optional components as needed. Regarding such various additives, conventionally known additives can be used by conventional methods.
[0201] From the perspective of transparency of the adhesive layer, the content of the tackifier resin in the layer B or the adhesive composition used to form the layer B may be, for example, less than 10 parts by weight, or further less than 5 parts by weight relative to 100 parts by weight of the monomer components constituting the layer B. The content of the tackifier resin may be less than 1 part by weight (e.g., less than 0.5 parts by weight), or less than 0.1 parts by weight (0 parts by weight or more and less than 0.1 parts by weight). The layer B or the adhesive composition used to form the layer B may be an adhesive composition that does not contain a tackifier resin.
[0202] The adhesive composition is formed in a manner that a photo-crosslinkable adhesive containing a polymer (PB) can be formed by curing the adhesive composition. For example, the adhesive composition can be imparted (e.g., applied) to an appropriate surface, and then appropriately subjected to curing treatments such as irradiation with active energy rays, drying (e.g., heat drying), crosslinking (e.g., crosslinking based on the reaction of the crosslinking agent), and cooling (e.g., cooling of the adhesive composition applied by hot melt), thereby forming an adhesive layer as a cured layer of the adhesive composition. When two or more curing treatments are performed, they can be performed simultaneously or in stages.
[0203] For the adhesive composition comprising a polymer (PB) and an ethylenically unsaturated compound (B), the curing is preferably carried out in a manner that the ethylenically unsaturated groups contained in the adhesive composition react and the benzophenone structure contained in the adhesive composition remains. The curing can preferably be carried out by irradiation with active energy rays. As a light source for curing the adhesive composition to form a photo-crosslinkable adhesive, it is preferred to use a light source such as the above-mentioned black light lamp, UV-LED lamp, etc. that can irradiate ultraviolet rays that do not contain a component with a wavelength lower than 300nm or a few components of the wavelength.
[0204] In some embodiments, the adhesive composition may be a composition in which the ethylenically unsaturated compound (B) does not contain an ethylenically unsaturated BP. According to the adhesive composition of such a composition, a photo-crosslinkable adhesive comprising a polymer (PB) and a polymer (E) derived from an ethylenically unsaturated compound (B), wherein the polymer (E) is a polymer (PNB) can be manufactured.
[0205] According to this specification, a method for manufacturing a photo-crosslinkable adhesive that can be photo-crosslinked using a benzophenone structure can be provided. Its manufacturing method includes the following steps: preparing an adhesive composition comprising an ethylenically unsaturated group and a benzophenone structure; and irradiating the above-mentioned adhesive composition with active energy rays (preferably ultraviolet rays). The above-mentioned adhesive composition may contain a photoinitiator. The irradiation of active energy rays for curing the adhesive composition is preferably carried out in a manner that allows the ethylenically unsaturated group to react and leaves the benzophenone structure residual. As the above-mentioned adhesive composition, an adhesive composition comprising a polymer (PB) and an ethylenically unsaturated compound (B) can be preferably used. The above-mentioned photo-crosslinkable adhesive manufacturing method can be preferably implemented using any adhesive composition disclosed herein. As a light source for curing the adhesive composition to form a photo-crosslinkable adhesive, it is preferred to use the above-mentioned black light lamp, UV-LED lamp, etc., which can irradiate ultraviolet rays that do not contain components with a wavelength less than 300nm or have less components of this wavelength.
[0206] (2) Layer B containing polymer (PD)
[0207] As another preferred example of the B layer containing a photo-crosslinkable polymer, a B layer (D-type B layer) formed by a photo-crosslinkable adhesive containing a polymer (PD) having a carbon-carbon double bond as the photo-crosslinkable polymer can be cited. The polymer (PD) is preferably a polymer substantially free of ethylenically unsaturated groups. The polymer (PD) is preferably a rubbery polymer that exhibits rubber elasticity in a temperature range near room temperature. In some embodiments, the D-type B layer can be a photo-crosslinkable sub-adhesive layer containing a polymer (PD) as a base polymer.
[0208] The carbon-carbon double bond does not react with moisture, acidity, etc. in the air in a common storage environment applicable in industry and is chemically stable. On the other hand, for example, by irradiating the D-type B layer with active energy rays, the carbon-carbon double bonds of the polymer (PD) can react to form a crosslinked structure. When ultraviolet rays are used as active energy rays, it is preferred that the D-type B layer contain a photoinitiator described later.
[0209] The form of the carbon-carbon double bond possessed by the polymer (PD) is not particularly limited. In some preferred embodiments, the polymer (PD) has a carbon-carbon double bond in the form of an ethylenically unsaturated group. The polymer (PD) may be a polymer having a carbon-carbon double bond in a side chain, or a polymer having a carbon-carbon double bond in a main chain. Here, the so-called carbon-carbon double bond in the main chain includes the case where a carbon-carbon double bond exists in the main chain skeleton of the polymer (PD) and the case where a carbon-carbon double bond exists at the end of the main chain. The method for making the polymer (PD) contain a carbon-carbon double bond is not particularly limited, and a suitable method can be selected from methods known to those skilled in the art. From the viewpoint of the reactivity of the carbon-carbon double bond, a polymer (PD) having a carbon-carbon double bond in the side chain can be preferably used.
[0210] It should be noted that, in this specification, the main chain of a polymer refers to the chain structure forming the backbone of the polymer. In addition, the side chain of a polymer refers to a group (side chain group (pendant), side group) bonded to the main chain, or a molecular chain that can be regarded as a side chain group.
[0211] The polymer (PD) is not particularly limited, and an appropriate polymer can be selected and used in consideration of the characteristics of the adhesive layer, etc. As the polymer (PD), a polymer (secondary polymer) obtained by introducing carbon-carbon double bonds into a polymer (primary polymer) that does not contain carbon-carbon double bonds or has a carbon-carbon double bond content less than the target by chemical modification or the like can be preferably used.
[0212] As a specific example of the method for introducing the carbon-carbon double bond into the primary polymer, the following method can be cited: a primary polymer obtained by copolymerizing a monomer having a functional group (hereinafter also referred to as "functional group A") is prepared, and a compound having a functional group (hereinafter also referred to as "functional group B") that can react with the functional group A and a carbon-carbon double bond is reacted with the primary polymer in a manner that the carbon-carbon double bond does not disappear. The reaction between the functional group A and the functional group B is preferably a reaction that is not accompanied by the generation of free radicals, such as a condensation reaction and an addition reaction.
[0213] As an example of the combination of functional group A and functional group B, a combination of carboxyl and epoxy, a combination of carboxyl and aziridine, a combination of hydroxyl and isocyanate, etc. can be cited. Among them, from the viewpoint of reaction tracking, a combination of hydroxyl and isocyanate is preferred. In addition, when the combination of the above-mentioned functional groups A and B is a combination that can obtain a polymer with a carbon-carbon double bond, one functional group in the above-mentioned combination can be functional group A, and the other can be functional group B, or one functional group can be functional group B, and the other can be functional group A. For example, if the combination of hydroxyl and isocyanate is used for explanation, functional group A can be hydroxyl (in this case, functional group B becomes isocyanate), or it can be isocyanate (in this case, functional group B becomes hydroxyl). Among them, it is preferred that a primary polymer has a hydroxyl and the above-mentioned compound has a combination of isocyanate. This combination is particularly preferred when the primary polymer is an acrylic polymer.
[0214] In addition, when the above-mentioned primary polymer is a vinyl alcohol polymer (typically polyvinyl alcohol), a method of reacting the vinyl alcohol polymer (typically a vinyl alcohol polymer not containing a carbon-carbon double bond) with a vinyl halide such as vinyl bromide or an allyl halide such as allyl bromide can also be cited as a preferred example. In this method, the above-mentioned reaction can be carried out under appropriate alkaline conditions, and through this reaction, a vinyl alcohol polymer containing a vinyl group in the side chain can be obtained. In addition, for example, the following method can also be adopted: a polymer having a carbon-carbon double bond is prepared using a microorganism that produces a polymer such as that disclosed in Japanese Patent Gazette No. 4502363. Various conditions in this method, such as the type of microorganism, microorganism culture conditions, etc., can be set by adopting the conditions described in the above-mentioned patent gazette, or by appropriately changing it within the scope of the technical common sense of those skilled in the art.
[0215] The molar mass (M) of the functional group A A ) and the molar mass of functional group B (M B ) molar ratio (M A / M B) can be, for example, 0.2 or more, 0.5 or more, 0.7 or more, or 1.0 or more. From the perspective of increasing the contact opportunity between the functional group B and the functional group A and thus improving the reactivity, it is usually preferred to make the molar ratio (M A / M B ) is greater than 1. In some embodiments, the molar ratio (M A / M B ) can be higher than 5, higher than 10, higher than 15, or higher than 20. A / M B ) is not particularly limited, and may be, for example, 100 or less, or 50 or less.
[0216] The amount of the compound having a functional group B and a carbon-carbon double bond (hereinafter also referred to as "unsaturated compound containing a functional group B") used is such that the above molar ratio (M A / M B ), for example, it can be 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, or 0.3 parts by weight or more, relative to 100 parts by weight of the primary polymer having the functional group A. By increasing the amount of the unsaturated compound containing the functional group B, there is a tendency for the deformation resistance improvement effect obtained by photocrosslinking the D-type B layer to become better. In addition, from the perspective of the optical properties of the B layer after photocrosslinking (improvement in transparency, suppression of optical strain, etc.), it is generally appropriate for the amount of the unsaturated compound containing the functional group B to be less than 20 parts by weight relative to 100 parts by weight of the primary polymer having the functional group A, and it is advantageous to be less than 15 parts by weight, preferably less than 10 parts by weight, and more preferably less than 7 parts by weight. In some preferred embodiments, the amount of the unsaturated compound containing the functional group B can be, for example, less than 5 parts by weight, less than 3 parts by weight, less than 2 parts by weight, or less than 1 part by weight. For example, in a configuration using an acrylic acid-based polymer described below as a primary polymer, the above-mentioned molar ratio (M A / M B ), the amount of unsaturated compound containing functional group B used.
[0217] In addition, the polymer having a carbon-carbon double bond may be, for example, a diene polymer (typically a conjugated diene polymer). A diene polymer (typically a conjugated diene polymer) is typically a polymer obtained by polymerizing or copolymerizing a diene (typically a conjugated diene). Examples of the diene polymer (typically a conjugated diene polymer) include butadiene polymers such as polybutadiene and styrene butadiene copolymers; isoprene polymers such as polyisoprene and styrene isoprene copolymers; chloroprene polymers such as polychloroprene; and the like.
[0218] The weight average molecular weight (Mw) of the polymer (PD) is not particularly limited. From the viewpoint of the cohesiveness of the photo-crosslinkable adhesive, the operability of the adhesive sheet having the photo-crosslinkable adhesive, etc., in some embodiments, the Mw of the polymer (PB) is about 10×10 4 The above is appropriate, preferably about 20×10 4 More preferably, about 30×10 4 On the other hand, from the viewpoint of the surface shape conformability of the adhesive layer constituting the adhesive sheet (i.e., the adhesive layer of the multilayer structure including the B layer before photocrosslinking), the Mw is set to about 500×10 4 The following is appropriate, preferably about 100×10 4 Below, more preferably about 70×10 4 the following.
[0219] In the technology disclosed herein, the glass transition temperature (Tg) of the polymer (PD) is not particularly limited. From the perspective of the surface shape followability of the adhesive layer, it is appropriate that the Tg of the polymer (PD) is generally lower than 0°C, preferably lower than -10°C, and preferably lower than -20°C. In some embodiments, the Tg of the polymer (PD) may be lower than -25°C, and may be lower than -30°C. In addition, the Tg of the polymer (PD) is typically above -80°C, for example, above -70°C, above -60°C, or above -55°C. In addition, from the perspective of the cohesion of the photocrosslinkable adhesive and the deformation resistance after photocrosslinking (for example, the durability of adhesion to the adherend), in some embodiments, the Tg of the polymer (PD) is preferably above -50°C, more preferably above -45°C, above -40°C, above -38°C, or above -35°C.
[0220] In addition, in the polymer (PD) obtained by introducing a carbon-carbon bond into a primary polymer, it is preferred that the primary polymer have the above-mentioned Tg.
[0221] The content of the polymer (PD) in the D-type B layer can be set in a manner that can exert the desired performance before and after photocrosslinking, and is not limited to a specific range. In some embodiments, the content of the polymer (PD) can be, for example, about 10% by weight or more in the D-type B layer, usually about 50% by weight or more is appropriate, can be about 70% by weight or more, can be about 90% by weight or more, preferably can be about 95% by weight or more, can be about 97% by weight or more, can be about 99% by weight or more (for example, 99 to 100% by weight).
[0222] (Acrylic polymer as polymer (PD))
[0223] In some embodiments, from the viewpoint of the increase in elastic modulus and optical properties of the B layer brought about by photocrosslinking, the polymer (PD) is preferably an acrylic polymer having a carbon-carbon double bond. As a preferred example of the polymer (PD), an acrylic polymer in which more than 50% by weight (preferably more than 65% by weight, for example more than 75% by weight) of the monomer components constituting the polymer (PD) are acrylic monomers can be cited. As a preferred example of the above-mentioned acrylic polymer, a polymer of a monomer raw material containing an alkyl (meth)acrylate and further containing other monomers (copolymerizable monomers) copolymerizable with the alkyl (meth)acrylate and its modified product (for example, a secondary polymer obtained by introducing a carbon-carbon double bond into the above-mentioned polymer as a primary polymer by a method such as chemical modification) can be cited.
[0224] The above-mentioned alkyl (meth)acrylate can be selected from the alkyl (meth)acrylates exemplified as components that can be used as monomer components constituting the polymer (PB). As particularly preferred alkyl (meth)acrylates, n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isononyl acrylate, etc. can be cited. As other specific examples of alkyl (meth)acrylates that can be preferably used, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA), etc. can be cited. The alkyl (meth)acrylate can be used alone or in combination of two or more.
[0225] The proportion of the alkyl (meth)acrylate in the entire monomer component constituting the polymer (PD) is preferably about 40% by weight or more. In some embodiments, the proportion of the alkyl (meth)acrylate may be, for example, 50% by weight or more, 55% by weight or more, or 60% by weight or more. In addition, from the viewpoint of improving the cohesion of the B layer, the proportion of the alkyl (meth)acrylate in the monomer component is usually appropriate to be 99.5% by weight or less, 95% by weight or less, 85% by weight or less, 75% by weight or less, or 70% by weight or less.
[0226] The monomer components constituting the polymer (PD) may include an alkyl (meth)acrylate and other monomers copolymerizable with the alkyl (meth)acrylate (copolymerizable monomers). As copolymerizable monomers, one or more selected from the components exemplified as the monomer components constituting the polymer (PB) may be used.
[0227] When using such a copolymerizable monomer, its usage amount is not particularly limited, and it is usually appropriate to be more than 0.01% by weight of the overall monomer component constituting the adhesive composition. From the viewpoint of better exerting the use effect of the copolymerizable monomer, the usage amount of the copolymerizable monomer (that is, the weight fraction of the copolymerizable monomer in the above-mentioned overall monomer component) can be more than 0.1% by weight of the overall monomer component, and can be more than 0.5% by weight. In some ways, the usage amount of the copolymerizable monomer can be, for example, more than 5% by weight of the overall monomer component, can be more than 10% by weight, can be more than 15% by weight, can be more than 20% by weight, can be more than 25% by weight, and can be more than 30% by weight. In addition, from the viewpoint of easily obtaining the balance of adhesive properties, it is appropriate that the usage amount of the copolymerizable monomer is usually less than 60% by weight of the overall monomer component, preferably less than 50% by weight, and can be less than 45% by weight.
[0228] In some embodiments, the monomer component used to prepare the polymer (PD) may include a monomer having a nitrogen atom as the above-mentioned copolymerizable monomer. As a preferred example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a ring containing a nitrogen atom, the monomers exemplified above as materials that can be used to prepare the polymer (PB) can be used, for example, the N-vinyl cyclic amide represented by the above-mentioned general formula (1) can be used. Among them, N-vinyl-2-pyrrolidone is preferred.
[0229] There is no particular restriction on the amount used when using a monomer having a nitrogen atom, for example, it can be more than 1% by weight of the total monomer component used to prepare the polymer (PD), it can be more than 2% by weight, it can be more than 3% by weight, and further can be more than 5% by weight or more than 7% by weight. In one embodiment, the amount of the monomer having a nitrogen atom can be more than 10% by weight of the total monomer component, it can be more than 15% by weight, or it can be more than 20% by weight. In addition, it is appropriate that the amount of the monomer having a nitrogen atom is, for example, less than 40% by weight of the total monomer component, it can be less than 35% by weight, it can be less than 30% by weight, or it can be less than 25% by weight. In another embodiment, the amount of the monomer having a nitrogen atom can be, for example, less than 20% by weight of the total monomer component, or it can be less than 15% by weight.
[0230] In some embodiments, the monomer component used to prepare the polymer (PD) may include a monomer containing a hydroxyl group as the above-mentioned copolymerizable monomer. By using a monomer containing a hydroxyl group, the cohesive force and the degree of crosslinking (for example, crosslinking based on an isocyanate crosslinking agent) of the photocrosslinkable adhesive constituting the B layer can be appropriately adjusted. The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the overall monomer component used to prepare the polymer (PD), it can be more than 0.1% by weight, it can be more than 0.5% by weight, it can be more than 1% by weight, it can be more than 5% by weight or more than 10% by weight. In addition, from the perspective of suppressing the water absorption of the photocrosslinkable adhesive or its photocrosslinked product, in some embodiments, the amount of the monomer containing a hydroxyl group is appropriate for the above-mentioned monomer component as a whole, for example, less than 40% by weight, it can be less than 30% by weight, it can be less than 25% by weight, it can be less than 20% by weight. In another embodiment, the amount of the monomer containing a hydroxyl group can be less than 15% by weight of the above-mentioned monomer component as a whole, for example, less than 10% by weight, or less than 5% by weight. Alternatively, the hydroxyl group-containing monomer may not be used as the copolymerizable monomer.
[0231] In some embodiments, the proportion of carboxyl-containing monomers in the overall monomer components used to prepare the polymer (PD) may be, for example, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight (e.g., less than 0.1% by weight). The above-mentioned monomer components may substantially not contain carboxyl-containing monomers. Here, the so-called substantially not containing carboxyl-containing monomers means that carboxyl-containing monomers are at least not intentionally used. This will be advantageous from the perspective of the metal corrosion resistance of the photocrosslinkable adhesive formed by the adhesive composition and its photocrosslinked product.
[0232] In some embodiments, the monomer component used to prepare the polymer (PD) may include a (meth) acrylate containing an alicyclic hydrocarbon group as the above-mentioned copolymerizable monomer. As a result, the cohesive force of the adhesive can be increased, and the peel strength after photocrosslinking can be increased. As the (meth) acrylate containing an alicyclic hydrocarbon group, the monomers exemplified above as materials that can be used to prepare the polymer (PB) can be used, for example, cyclohexyl acrylate and isobornyl acrylate can be preferably used. The amount used when using a (meth) acrylate containing an alicyclic hydrocarbon group is not particularly limited, for example, it can be 1% by weight or more, 3% by weight or more, or 5% by weight or more of the total monomer component used to prepare the polymer (PD). In one embodiment, the amount of (meth) acrylate containing an alicyclic hydrocarbon group can be 10% by weight or more of the total monomer component, and can be 15% by weight or more. It is appropriate that the upper limit of the amount of (meth) acrylate containing an alicyclic hydrocarbon group is about 40% by weight or less, for example, it can be 30% by weight or less, and it can be 25% by weight or less (for example, 15% by weight or less, and then 10% by weight or less).
[0233] In some embodiments, the monomer component used to prepare the polymer (PD) may include a monomer containing an alkoxysilyl group as the above-mentioned copolymerizable monomer. The monomer containing an alkoxysilyl group is typically an ethylenically unsaturated compound having at least one (preferably two or more, for example, two or three) alkoxysilyl group in one molecule, and its specific example is as described above. The above-mentioned monomer containing an alkoxysilyl group can be used alone or in combination of two or more. By using a monomer containing an alkoxysilyl group, a cross-linked structure formed by a condensation reaction of a silanol group (silanol condensation) can be introduced into a photo-crosslinkable adhesive.
[0234] The amount used in the case of using a monomer containing an alkoxysilyl group is not particularly limited. In some ways, the amount of the monomer containing an alkoxysilyl group can be, for example, more than 0.005% by weight of the overall monomer component for preparing a polymer (PD), usually more than 0.01% by weight is appropriate, can be more than 0.03% by weight, can be more than 0.05% by weight. In addition, from the viewpoint of the surface shape followability of the adhesive sheet disclosed herein, the amount of the monomer containing an alkoxysilyl group is usually less than 1.0% by weight of the overall monomer component, can be less than 0.5% by weight, can be less than 0.1% by weight.
[0235] The monomer component for preparing the polymer (PD) may also include a multifunctional monomer. As the multifunctional monomer, the multifunctional monomers exemplified above as materials for preparing the polymer (PB) may be used. From the viewpoint of the surface shape followability of the adhesive layer constituting the adhesive sheet, in some embodiments, a 2-functional monomer may be preferably used as the multifunctional monomer. The proportion of the 2-functional monomer in the overall multifunctional monomer used may be, for example, more than 50% by weight, more than 70% by weight, more than 90% by weight, or 100% by weight.
[0236] The amount used when using a multifunctional monomer is not particularly limited, and for example, it can be 0.001% by weight or more of the total monomer components used to prepare the polymer (PD). From the viewpoint of the ease of manufacture of the adhesive composition for forming the D-type B layer, it is appropriate that the amount of the multifunctional monomer used is usually less than 1% by weight of the total monomer components used to prepare the polymer (PD), preferably less than 0.5% by weight. It is also possible not to use a multifunctional monomer.
[0237] (Acrylic primary polymer)
[0238] The acrylic polymer having a carbon-carbon double bond may be a secondary polymer obtained by introducing a carbon-carbon double bond into an acrylic primary polymer obtained by polymerizing monomer components having the above composition.
[0239] The method for obtaining an acrylic acid-based primary polymer having the above-mentioned monomer composition is not particularly limited, and various polymerization methods known as synthetic methods for acrylic acid-based polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method during solution polymerization, a method of supplying all monomer raw materials at once, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. As a solvent used in solution polymerization, it can be appropriately selected from known or commonly used organic solvents such as toluene and ethyl acetate. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, about 20°C to 120°C (typically 40°C to 80°C).
[0240] During polymerization, known or commonly used polymerization initiators can be used according to the polymerization method, polymerization mode, etc. Such polymerization initiators can be used alone or in combination of two or more. As thermal polymerization initiators, there are no particular limitations, for example, azo polymerization initiators, peroxide initiators, redox initiators formed by a combination of peroxides and reducing agents, substituted ethane initiators, etc. can be used. More specifically, examples include azo initiators such as 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate; persulfates such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, tert-butyl hydroperoxide, and hydrogen peroxide; substituted ethane initiators such as phenyl-substituted ethane; redox initiators such as a combination of a persulfate and sodium bisulfite, and a combination of a peroxide and sodium ascorbate; and the like, but the present invention is not limited to these. As a preferred example of the polymerization initiator, an azo polymerization initiator is mentioned.
[0241] The amount of the polymerization initiator used may be a normal amount, and can be selected from a range of, for example, about 0.005 to 1 part by weight (typically 0.01 to 1 part by weight) based on 100 parts by weight of all monomer components.
[0242] During polymerization, various chain transfer agents known in the past can be used as needed. For example, one or more chain transfer agents selected from the various chain transfer agents exemplified as optional components of the adhesive composition for obtaining the B-type B layer can be used. When a chain transfer agent is used, its usage amount can be set in a manner that a resultant having a desired Mw can be obtained, and is not particularly limited. Generally, for example, about 0.01 to 1 part by weight is appropriate relative to 100 parts by weight of the monomer component provided for polymerization, and preferably about 0.01 to 0.2 parts by weight. It is also possible not to use a chain transfer agent.
[0243] The glass transition temperature (Tg) of the acrylic primary polymer is not particularly limited. From the viewpoint of the surface shape followability of the adhesive layer, it is appropriate that the Tg of the acrylic primary polymer is generally lower than 30°C, preferably lower than 20°C, may be lower than 10°C, and may be lower than 5°C. In some embodiments, the Tg of the acrylic primary polymer may be lower than 0°C, lower than -10°C, lower than -20°C, lower than -25°C, and lower than -30°C. In addition, the Tg of the acrylic primary polymer is typically above -80°C, for example, above -70°C, above -60°C, and above -55°C. In addition, from the viewpoint of the cohesion of the photo-crosslinkable adhesive and the deformation resistance after photo-crosslinking (for example, the durability of adhesion to the adherend), in some embodiments, the Tg of the acrylic primary polymer is preferably above -50°C, more preferably above -45°C, above -40°C, above -38°C, and above -35°C.
[0244] The method for introducing carbon-carbon double bonds into acrylic primary polymers is not particularly limited. For example, the following method can be preferably adopted: reacting an acrylic primary polymer into which functional group A is introduced by copolymerization with a compound having a functional group (functional group B) capable of reacting with the functional group A and a carbon-carbon double bond (an unsaturated compound containing functional group B) in a manner that the carbon-carbon double bond does not disappear. Examples of combinations of functional group A and functional group B include a combination of a carboxyl group and an epoxy group, a combination of a carboxyl group and an aziridine group, a combination of a hydroxyl group and an isocyanate group, and the like. Among them, from the viewpoint of reaction traceability, a combination of a hydroxyl group and an isocyanate group is preferred. From the viewpoint of polymer design, etc., a combination in which an acrylic primary polymer has a hydroxyl group and the above-mentioned compound has an isocyanate group is particularly preferred.
[0245] The compound having a carbon-carbon double bond may have a functional group B that can react with the functional group A as described above. As a preferred example of such a compound, for example, a monomer containing an isocyanate group (a compound containing an isocyanate group) exemplified as a copolymerizable monomer that can be used for the polymerization of an acrylic polymer can be cited. Among them, 2-(methyl)acryloyloxyethyl isocyanate is more preferred. By reacting the isocyanate group of the compound containing an isocyanate group having a carbon-carbon double bond with the hydroxyl group of the acrylic primary polymer to form a bond (typically a carbamate bond), an acrylic polymer having a carbon-carbon double bond can be suitably achieved.
[0246] From the viewpoint of reactivity with the hydroxyl group as the functional group A, the amount of the isocyanate group-containing monomer used may be such that the above-mentioned molar ratio (M) is satisfied. A / M B) is appropriately set within the range of . For example, the amount of the monomer containing an isocyanate group used relative to 100 parts by weight of the acrylic primary polymer can be, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, or 0.3 parts by weight or more. By increasing the amount of the monomer containing an isocyanate group used, there is a tendency to improve the deformation resistance obtained by photocrosslinking the D-type B layer. In addition, from the perspective of the optical properties of the B layer after photocrosslinking (improvement in transparency, suppression of optical strain, etc.), it is generally appropriate to use less than 20 parts by weight of the monomer containing an isocyanate group relative to 100 parts by weight of the acrylic primary polymer, and it is advantageous to use less than 15 parts by weight, preferably less than 10 parts by weight, and more preferably less than 7 parts by weight. In some preferred embodiments, the amount of the monomer containing an isocyanate group used can be, for example, less than 5 parts by weight, less than 3 parts by weight, less than 2 parts by weight, or less than 1 part by weight.
[0247] In addition, the amount of the monomer containing an isocyanate group can be about 0.01% by weight or more of the total monomer components constituting the D-type B layer, can be 0.05% by weight or more, can be 0.1% by weight or more, can be 0.2% by weight or more, can be 0.3% by weight or more. It is appropriate that the amount of the monomer containing an isocyanate group is less than 20% by weight of the total monomer components constituting the D-type B layer, it is advantageous to be less than 15% by weight, preferably less than 10% by weight, and more preferably less than 7% by weight. In some preferred embodiments, the amount of the monomer containing an isocyanate group can be, for example, less than 5% by weight, less than 3% by weight, less than 2% by weight, or less than 1% by weight.
[0248] (Crosslinking agent)
[0249] In the adhesive composition, known crosslinking agents such as isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, hydrazine crosslinking agents, and amine crosslinking agents can be used as needed. Peroxides can also be used as crosslinking agents. These crosslinking agents can be used alone or in combination of two or more. The photo-crosslinkable adhesive formed by the adhesive composition containing the crosslinking agent preferably contains the crosslinking agent mainly in the form after the crosslinking reaction. By using a crosslinking agent, the cohesive force of the photo-crosslinkable adhesive can be appropriately adjusted. In the water-dispersible adhesive composition, a crosslinking agent that can be dissolved or dispersed in water is preferably used.
[0250] As the isocyanate crosslinking agent, a polyfunctional isocyanate compound having two or more functions can be used. For example, aromatic isocyanates such as toluene diisocyanate, xylylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatephenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as hexamethylene diisocyanate; and the like can be cited. As commercially available products, isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by TOSOH, trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by TOSOH, trade name "Coronate HL"), isocyanurate of hexamethylene diisocyanate (manufactured by TOSOH, trade name "Coronate HX"), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, trade name "Takenate D-110N") can be exemplified. In a water-dispersible adhesive composition, an isocyanate crosslinking agent that can be dissolved or dispersed in water is preferably used. For example, a water-soluble, water-dispersible or self-emulsifying isocyanate crosslinking agent can be preferably used. An isocyanate crosslinking agent of the so-called blocked isocyanate type in which the isocyanate group is blocked can be preferably used.
[0251] As the epoxy crosslinking agent, a crosslinking agent having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl meta-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical, trade name "EPICLON CR-5L" manufactured by DIC, trade name "Denacol EX-512" manufactured by Nagase Chemtex, trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd., and the like.
[0252] As the oxazoline crosslinking agent, any crosslinking agent having one or more oxazoline groups in one molecule can be used without particular limitation.
[0253] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(1-(2-methyl)aziridinyl propionate)].
[0254] As the carbodiimide-based crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.
[0255] In some ways, peroxide can also be used as a crosslinking agent. As peroxide, peroxydicarbonate di (2-ethylhexyl) ester, peroxydicarbonate di (4-tert-butyl cyclohexyl) ester, peroxydicarbonate di-sec-butyl ester, peroxyneodecanoic acid tert-butyl ester, peroxypivalate tert-hexyl ester, peroxypivalate tert-butyl ester, peroxydilauroyl, peroxide di-n-octanoyl, peroxyisobutyric acid 1,1,3,3-tetramethylbutyl ester, dibenzoyl peroxide, etc. can be enumerated. Among these, as the particularly excellent peroxide of crosslinking reaction efficiency, peroxydicarbonate di (4-tert-butyl cyclohexyl) ester, peroxide dilauroyl, dibenzoyl peroxide, etc. can be enumerated. It should be noted that, when using peroxide as the above-mentioned polymerization initiator, the peroxide that is not used and remains in the polymerization reaction can also be used in the crosslinking reaction. In this case, the residual amount of peroxide is quantitatively measured, and when the ratio of peroxide does not meet the prescribed amount, peroxide can be added as required in the mode of becoming the prescribed amount. The quantitative determination of peroxide can be performed by the method described in Japanese Patent No. 4971517.
[0256] The amount used when using a cross-linking agent (the total amount of the cross-linking agents when using more than two cross-linking agents) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as bonding force and cohesive force in a well-balanced manner, it is appropriate that the amount of the cross-linking agent used is usually about 5 parts by weight or less relative to 100 parts by weight of the monomer component constituting the adhesive composition, which can be less than 3 parts by weight, less than 1 part by weight, less than 0.50 parts by weight, less than 0.30 parts by weight, or less than 0.20 parts by weight. The lower limit of the amount of the cross-linking agent used is not particularly limited, and it is an amount greater than 0 parts by weight relative to 100 parts by weight of the monomer component constituting the adhesive composition. In some ways, the amount of the cross-linking agent used can be, for example, more than 0.001 parts by weight, more than 0.01 parts by weight, more than 0.05 parts by weight, or more than 0.10 parts by weight relative to 100 parts by weight of the monomer component constituting the adhesive composition.
[0257] (Photoinitiator)
[0258] In the D-type B layer, a photoinitiator may be contained for the purpose of efficiently forming a cross-linked structure based on a carbon-carbon double bond by ultraviolet irradiation. As the photoinitiator, a ketal photoinitiator, an acetophenone photoinitiator, a benzoin ether photoinitiator, an acylphosphine oxide photoinitiator, an α-ketol photoinitiator, an aromatic sulfonyl chloride photoinitiator, a photoactive oxime photoinitiator, a benzoin photoinitiator, a benzyl photoinitiator, a benzophenone photoinitiator, an alkylphenone photoinitiator, a thioxanthone photoinitiator, etc. may be used. One type of the photoinitiator may be used alone or two or more types may be used in combination as appropriate.
[0259] In some embodiments, as the photoinitiator contained in the D-type B layer, a photoinitiator having a hydroxyl group in the molecule can be preferably used. As such a photoinitiator containing a hydroxyl group, a photoinitiator having a hydroxyl group can be preferably used from the above-mentioned photoinitiators. For example, benzophenone derivatives, alkylphenone derivatives, and acetophenone derivatives can be cited as preferred examples.
[0260] As benzophenone derivatives, for example, o-acryloxybenzophenone, p-acryloxybenzophenone, o-methacryloxybenzophenone, p-methacryloxybenzophenone, and p-(meth)acryloxyethoxybenzophenone can be mentioned. In addition, benzophenone-4-carboxylic acid esters of acrylates such as 1,4-butanediol mono(meth)acrylate, 1,2-ethylene glycol mono(meth)acrylate, and 1,8-octanediol mono(meth)acrylate can also be used. As alkyl phenone derivatives, for example, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one can be mentioned. As acetophenone derivatives, 1-hydroxycyclohexyl phenyl ketone can be mentioned. The above-mentioned photoinitiator can be used alone or in combination of two or more. Among them, 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one are preferred because of their excellent curing speed and thick film curability.
[0261] As for the alkylphenone-based photoinitiator which can be cited as a preferred example, benzyl ketal-based photoinitiator, hydroxyalkylphenone-based photoinitiator (typically α-hydroxyalkylphenyl ketone), hydroxyacetophenone-based photoinitiator (typically α-hydroxyacetophenone), and aminoalkylphenone-based photoinitiator (typically α-aminoalkylphenyl ketone) can be exemplified. One of them can be used alone or two or more can be used in combination. Among them, hydroxyalkylphenone-based photoinitiator and aminoalkylphenone-based photoinitiator are preferred. As a specific example of the hydroxyalkylphenone-based photoinitiator, the above-mentioned 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one can be cited, and as a specific example of the aminoalkylphenone-based photoinitiator, 2-benzyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone can be cited.
[0262] Other preferred examples include acylphosphine oxide-based photoinitiators such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0263] In addition, oxime ester photoinitiators such as 1,2-octanedione-1-[4-(phenylthio)phenyl]-2-(o-benzoyl oxime) and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(o-acetyl oxime) can also be preferably used.
[0264] When the D-type B layer contains a photoinitiator, the content of the photoinitiator in the D-type B layer is not particularly limited and can be set in a manner that the desired effect is appropriately exerted. In some embodiments, the content of the photoinitiator can be, for example, about 0.005 parts by weight or more, usually 0.01 parts by weight or more is appropriate, preferably 0.05 parts by weight or more, can be 0.10 parts by weight or more, can be 0.15 parts by weight or more, can be 0.20 parts by weight or more, relative to 100 parts by weight of the monomer components constituting the D-type B layer. By increasing the content of the photoinitiator, the photocurability of the D-type B layer is improved. In addition, the content of the photoinitiator relative to 100 parts by weight of the monomer components constituting the D-type B layer is usually 5 parts by weight or less, preferably 2 parts by weight or less, can be 1 part by weight or less, can be 0.7 parts by weight or less, can be 0.5 parts by weight or less. From the perspective of the storage stability of the adhesive sheet having the D-type B layer (for example, the performance of suppressing the performance change caused by the storage of the adhesive sheet before use), it is preferred that the content of the photoinitiator is not too much.
[0265] (Free Radical Scavenger)
[0266] From the viewpoint of storage stability, a free radical scavenger such as an antioxidant can be included in the D-type B layer. The free radical scavenger is a reagent that performs the function of capturing free radicals in the adhesive layer as shown in the text, and therefore, in the state before ultraviolet irradiation treatment, it is possible to hinder the addition of free radicals on the carbon-carbon double bonds present in the D-type B layer. The concept of the free radical scavenger disclosed herein may include an antioxidant and a light stabilizer, but a typical example thereof is an antioxidant. As the above-mentioned antioxidant, various antioxidants known in the past such as phenolic antioxidants, phosphorus-based (phosphite-based) antioxidants, sulfur-based antioxidants, and amine-based antioxidants can be cited. One antioxidant can be used alone or in combination of two or more.
[0267] The technology disclosed herein can be implemented in a manner that the D-type B layer includes a polymer (PD) having a carbon-carbon double bond and a photoinitiator. In this manner, from the viewpoint of smoothly achieving the improvement in deformation resistance brought about by photocrosslinking, it is preferred to limit the content of the free radical scavenger in the D-type B layer. It is appropriate that the content of the free radical scavenger (typically an antioxidant) in the D-type B layer is about 3 weight % or less, preferably about 1 weight % or less, more preferably about 0.5 weight % or less, and further preferably about 0.3 weight % or less (typically 0.1 weight % or less). The D-type B layer may also be free of a free radical scavenger (typically an antioxidant).
[0268] (Other optional ingredients)
[0269] The pressure-sensitive adhesive composition for forming the type D B layer may contain the above-mentioned acrylic oligomer as necessary.
[0270] In addition, the adhesive composition for forming the D-type B layer may contain various common additives in the adhesive field such as tackifying resins, viscosity modifiers (e.g., thickeners), leveling agents, plasticizers, fillers, pigments, dyes and other colorants as other optional components. Regarding such various additives, conventionally known additives can be used by conventional methods.
[0271] (3) Shear storage elastic modulus
[0272] In the adhesive sheet disclosed herein, the shear storage elastic modulus Ga' [kPa] at 30°C of the photocrosslinkable adhesive constituting the B layer of the adhesive layer is preferably higher than 1 kPa. Hereinafter, the above-mentioned shear storage elastic modulus Ga' is sometimes referred to as "room temperature elastic modulus Ga' before photocrosslinking" or simply as "room temperature elastic modulus Ga'". From the viewpoints of the cohesiveness of the photocrosslinkable adhesive, the operability (e.g., processability) of the adhesive sheet having an adhesive layer formed by the photocrosslinkable adhesive, etc., the room temperature elastic modulus Ga' is preferably higher than 5 kPa, more preferably higher than 10 kPa, and may be higher than 15 kPa. In addition, from the viewpoint of the ability to follow the surface shape of the adherend, it is appropriate that the room temperature elastic modulus Ga' is generally 500 kPa or less, preferably 200 kPa or less, and may be 100 kPa or less. In some embodiments, the room temperature elastic modulus Ga' may be lower than 50 kPa, and may be lower than 30 kPa.
[0273] The room temperature elastic modulus Ga' of the photo-crosslinkable adhesive constituting the B layer can be determined by measuring the dynamic viscoelasticity under the same conditions as the elastic modulus Gb' before photo-crosslinking described in the examples described later. The room temperature elastic modulus Ga' can be adjusted by the composition of the photo-crosslinkable adhesive (for example, in the case of a B-type B layer, the BP equivalent of the polymer (PB), the Mw, the composition of the monomer components constituting the polymer (PB), the weight fraction of the polymer (PB)), etc.
[0274] The shear storage elastic modulus of the photo-crosslinkable adhesive constituting the B layer of the adhesive layer at 80°C (i.e., the elastic modulus Gb' before photo-crosslinking) is not particularly limited. From the viewpoints of the cohesiveness of the photo-crosslinkable adhesive, the operability of the adhesive sheet having the photo-crosslinkable adhesive (e.g., the storage property of the adhesive sheet), etc., it is appropriate that the elastic modulus Gb' is generally higher than 3kPa, preferably higher than 5kPa, more preferably higher than 10kPa, and may be higher than 15kPa. In some embodiments, from the viewpoints of the processability of the adhesive sheet having the photo-crosslinkable adhesive, the elastic modulus Gb' may be higher than 30kPa, higher than 40kPa, higher than 50kPa, and higher than 52kPa. A photo-crosslinkable adhesive having such an elastic modulus Gb' can be preferably used as a constituent element of an adhesive layer having a thickness greater than 50μm, greater than 70μm, or greater than 90μm formed by the photo-crosslinkable adhesive, or an adhesive sheet having the adhesive layer.
[0275] The elastic modulus Gb' can be measured by the method described in the examples described later. The elastic modulus Gb' can be adjusted by the composition of the photocrosslinkable adhesive (for example, in the case of type B layer B, the BP equivalent of the polymer (PB), Mw, the composition of the monomer components constituting the polymer (PB), the weight fraction of the polymer (PB)), etc.
[0276] The shear storage elastic modulus Gc' [kPa] at 80°C of the photocrosslinked product obtained by irradiating the photocrosslinkable adhesive with ultraviolet rays using a high-pressure mercury lamp (i.e., the elastic modulus Gc' after photocrosslinking) is not particularly limited. From the viewpoint of suppressing the cohesive failure of the joint formed by the photocrosslinked product, it is generally advantageous for the elastic modulus Gc' to be above 15 kPa, preferably above 25 kPa. From the viewpoint of improving the durability of the close fit to the adherend (especially the adherend that is prone to outgassing, such as a polarizing plate), it is advantageous for the elastic modulus Gc' to be above 30 kPa, preferably above 35 kPa, and more preferably above 40 kPa. In some embodiments, the elastic modulus Gc' may be above 45 kPa, may be above 50 kPa, may be above 55 kPa, or may be above 60 kPa. In addition, the elastic modulus Gc' may be, for example, below 200 kPa, may be below 150 kPa, or may be below 120 kPa. From the perspective of achieving good balance between adhesion durability and other properties (such as peel strength) to the adherend, it is advantageous for the elastic modulus Gc' to be less than 100 kPa, preferably less than 80 kPa, less than 70 kPa, or less than 65 kPa. If the elastic modulus Gc' is lowered, there is a tendency that the peel strength of the photo-crosslinked product formed by laminating the photo-crosslinkable adhesive on the adherend and photo-crosslinking the photo-crosslinked adhesive from the adherend is substantially improved. In some embodiments, the elastic modulus Gc' may be less than 60 kPa, less than 55 kPa, less than 50 kPa, or less than 45 kPa.
[0277] More specifically, the elastic modulus Gc' can be measured by the method described in the examples described later. The elastic modulus Gc' can be adjusted by the composition of the photocrosslinkable adhesive (for example, in the case of type B layer B, the BP equivalent of the polymer (PB), Mw, the composition of the monomer components constituting the polymer (PB), the weight fraction of the polymer (PB)), etc.
[0278] The relationship between the elastic modulus Gb' of the photo-crosslinkable adhesive constituting the B layer and the elastic modulus Gc' of its photo-crosslinked product is not particularly limited, but typically satisfies Gc'[kPa]-Gb'[kPa]>0[kPa]. ΔG' may be, for example, 3 kPa or more, preferably 5 kPa or more, and more preferably 8 kPa or more. According to the photo-crosslinkable adhesive with ΔG' of 8 kPa or more, it is easy to appropriately exert the effect of improving the deformation resistance brought about by photo-crosslinking. From the viewpoint of obtaining a higher photo-crosslinking effect, in some embodiments, ΔG' may be 10 kPa or more, 15 kPa or more, 20 kPa or more, 25 kPa or more, or 30 kPa or more. The upper limit of ΔG' is not particularly limited, but from the viewpoint of achieving both the surface shape tracking property when attached to the adherend and the deformation resistance after photo-crosslinking with good balance, it is generally appropriate to be 150 kPa or less, preferably 100 kPa or less, 80 kPa or less, 65 kPa or less, 50 kPa or less, or 40 kPa or less.
[0279] (4) Multifunctional monomer content
[0280] In some aspects of the technology disclosed herein, the content of the polyfunctional monomer having two or more ethylenically unsaturated groups (for example, a polyfunctional monomer having a molecular weight (formula weight) in the range of 150 to 1000, preferably 200 to 700 based on the chemical formula) in the above-mentioned layer B is preferably about 40 μmol or less per 1 g of the layer B. That is, the content of the polyfunctional monomer in the layer B is preferably 40 μmol / g or less.
[0281] Generally, multifunctional monomers have higher mobility than photo-crosslinkable polymers. Therefore, in a multi-layered adhesive layer including layers A and B, when the B layer includes a multifunctional monomer, a portion of the multifunctional monomer will move from the B layer to the outside (e.g., the inside of the A layer, or further through the A layer to the surface of the A layer) during the period from the formation of the multi-layered adhesive layer to the photo-crosslinking of the B layer. This will become an important factor that reduces the storage stability of the adhesive sheet.
[0282] In the technology disclosed herein, the B layer contains a photo-crosslinkable polymer, so even if the content of the multifunctional monomer in the B layer is limited, the effect obtained by photo-crosslinking the B layer (for example, the effect of improving deformation resistance) can be appropriately exerted. The case where the content of the multifunctional monomer in the B layer is limited is also preferred from the viewpoint of reducing the odor of the adhesive layer containing the B layer (and then the adhesive sheet containing the adhesive layer).
[0283] It should be noted that the so-called multifunctional monomer content of layer B refers to the amount of multifunctional monomers contained in layer B in an unreacted form (typically, a form that is not chemically bonded to other components of layer B). Therefore, multifunctional monomers after the ethylenically unsaturated groups have reacted (multifunctional monomer residues that have formed a cross-linked structure) are excluded from the multifunctional monomer content of layer B here.
[0284] In some embodiments, the content of the multifunctional monomer in layer B is preferably 30 μmol / g or less, more preferably 20 μmol / g or less, further preferably 10 μmol / g or less, and may be 5 μmol / g or less. A preferred embodiment relates to layer B that does not contain a multifunctional monomer. The layer B that does not contain the above-mentioned multifunctional monomer is a layer that does not contain a multifunctional monomer with unreacted ethylenically unsaturated groups, and the layer B may contain a multifunctional monomer residue that has formed a cross-linked structure.
[0285] (5) Ratio of hydrophilic monomer
[0286] In some embodiments, the ratio of the hydrophilic monomer is preferably set within an appropriate range for the monomer components constituting layer B. Here, the "hydrophilic monomer" in this specification refers to a carboxyl group-containing monomer, an acid anhydride group-containing monomer, a hydroxyl group-containing monomer, a nitrogen atom-containing monomer (typically, an amide group-containing monomer such as (meth)acrylamide, a nitrogen atom-containing ring monomer such as N-vinyl-2-pyrrolidone) and an alkoxy group-containing monomer (typically, an alkoxyalkyl (meth)acrylate and an alkoxypolyalkylene glycol (meth)acrylate).
[0287] The proportion of the hydrophilic monomer in the total monomer components constituting layer B may be, for example, 45% by weight or less, usually preferably 40% by weight or less, and may be 35% by weight or less. From the viewpoint of reducing the water absorption of the adhesive layer and improving the water resistance, it is preferred that the amount of the hydrophilic monomer used in layer B is not too large.
[0288] On the other hand, the case where the B layer contains a certain degree of hydrophilic monomers will become advantageous from the perspective of adhesion to the layer adjacent to the B layer (e.g., the A layer). In addition, the proportion of the above-mentioned hydrophilic monomer in the overall monomer components constituting the B layer can be, for example, less than 1% by weight. In some embodiments, the proportion of the above-mentioned hydrophilic monomer is preferably 2% by weight or more, more preferably 5% by weight or more, can be 10% by weight or more, and can be 15% by weight or more. In the structure in which the A layer formed by the aqueous adhesive composition (e.g., a water-dispersible adhesive composition) is directly contacted with the above-mentioned B layer, from the perspective of improving the coating property when the aqueous adhesive composition used to form the A layer is directly coated on the surface of the B layer (e.g., suppressing uneven coating such as depressions and baldness of the above-mentioned aqueous adhesive composition), it is preferred that the B layer contains a certain degree of hydrophilic monomers. In particular, in the embodiment in which the thickness of the A layer is small (e.g., the thickness of the A layer is less than 10 μm), it is preferred that the B layer contains a certain degree (e.g., more than 2% by weight) of hydrophilic monomers.
[0289] <Level A>
[0290] In the technology disclosed herein, the A layer constituting one surface of the adhesive layer may be, for example, an adhesive layer composed of one or more adhesives selected from various adhesives such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, and mixed systems thereof), silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, and fluorine adhesives. Here, the so-called acrylic adhesive refers to an adhesive with an acrylic polymer as the main component. The same meaning applies to rubber adhesives and other adhesives.
[0291] (Acrylic adhesive)
[0292] From the viewpoint of transparency, weather resistance, etc., in some embodiments, an acrylic adhesive can be preferably used as the constituent material of the A layer.
[0293] As the acrylic adhesive, for example, it is preferable to include a (meth)acrylic acid alkyl ester (preferably (meth)acrylic acid C) containing more than 50% by weight. 1-20 The acrylic adhesive is an acrylic adhesive having an acrylic polymer composed of a monomer component of (meth)acrylic acid C alkyl ester as a base polymer. From the perspective of easily achieving a balance of properties, the (meth)acrylic acid C alkyl ester in the entire monomer component is preferably 1-20 The proportion of the alkyl ester may be, for example, 55% by weight or more, 60% by weight or more, or 70% by weight or more. 1-20 The proportion of the alkyl ester may be, for example, 99.9% by weight or less, 99.5% by weight or less, or 99% by weight or less.
[0294] The above-mentioned alkyl (meth)acrylate can be selected from the alkyl (meth)acrylates exemplified as components that can be used as monomer components constituting the polymer (PB). As particularly preferred alkyl (meth)acrylates, n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isononyl acrylate, etc. can be cited. As other specific examples of alkyl (meth)acrylates that can be preferably used, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA), etc. can be cited. The alkyl (meth)acrylate can be used alone or in combination of two or more.
[0295] In some embodiments, the monomer components constituting the A layer may contain (meth)acrylic acid C in a ratio of 40 wt % or more. 4-18 Alkyl ester. The monomer component containing a large amount of (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms at the ester terminal tends to form an acrylic polymer with high lipophilicity. The acrylic polymer with high lipophilicity tends to suppress water absorption of the A layer. (Meth)acrylic acid C 4-18 The proportion of the alkyl ester in the above monomer components may be, for example, 60% by weight or more, 70% by weight or more, 75% by weight or more, or 80% by weight or more. The (meth)acrylic acid C may be contained in a proportion greater than any of the above lower limits. 6-18 The monomer component of the alkyl ester.
[0296] In addition, from the viewpoint of improving the cohesiveness of the A layer and preventing cohesive failure, the (meth)acrylic acid C 4-18 The proportion of the alkyl ester in the above monomer components is suitably 99.5% by weight or less, and can be 99% by weight or less, 98% by weight or less, or 97% by weight or less. From the viewpoint of improving the cohesiveness of the A layer, in some embodiments, the (meth)acrylic acid C 4-18 The proportion of the alkyl ester in the above monomer components is preferably 95% by weight or less, for example, 90% by weight or less. In some other embodiments, (meth)acrylic acid C 4-18 The proportion of the alkyl ester in the monomer components may be 85% by weight or less, or 75% by weight or less. The (meth)acrylic acid C may be contained in a proportion below any of the above upper limits. 6-18 The monomer component of the alkyl ester.
[0297] The monomer components constituting the A layer may contain other monomers (copolymerizable monomers) copolymerizable with the (meth) alkyl ester as required, together with the (meth) alkyl ester. One or more components selected from the components exemplified as monomer components constituting the polymer (PB) may be used.
[0298] When such a copolymerizable monomer is used, its usage amount is not particularly limited, but it is appropriate to be 0.01% by weight or more of the overall monomer components constituting layer A. From the viewpoint of better exerting the use effect of the copolymerizable monomer, the usage amount of the copolymerizable monomer can be 0.1% by weight or more of the overall monomer components, and can be 0.5% by weight or more. In addition, from the viewpoint of easily obtaining a balanced adhesive property, it is appropriate to use a copolymerizable monomer in an amount of less than 50% by weight of the overall monomer components, preferably less than 40% by weight.
[0299] In some embodiments, the monomer components constituting layer A may include monomers having nitrogen atoms. By using monomers having nitrogen atoms, the cohesive force of the adhesive can be increased, and the peel strength after photocrosslinking can be ideally increased. As a preferred example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a ring containing a nitrogen atom, the monomers exemplified above as materials that can be used to prepare a polymer (PB) can be used, for example, the N-vinyl cyclic amide represented by the above general formula (1) can be used. Among them, N-vinyl-2-pyrrolidone is preferred.
[0300] The amount of monomers with nitrogen atoms (preferably monomers with rings containing nitrogen atoms) used is not particularly limited, for example, it can be more than 1% by weight of the overall monomer components constituting layer A, it can be more than 3% by weight, and further can be more than 5% by weight or more than 7% by weight. In some embodiments, from the viewpoint of improving adhesion, the amount of monomers with nitrogen atoms used can be more than 10% by weight of the overall monomer components, it can be more than 15% by weight, or it can be more than 20% by weight. In addition, it is appropriate that the amount of monomers with nitrogen atoms used is, for example, less than 40% by weight of the overall monomer components, it can be less than 35% by weight, it can be less than 30% by weight, or it can be less than 25% by weight. In some other embodiments, the amount of monomers with nitrogen atoms used can be, for example, less than 20% by weight of the overall monomer components, or it can be less than 15% by weight.
[0301] In some embodiments, the monomer component preferably includes a monomer containing a carboxyl group. Preferred examples of monomers containing a carboxyl group include acrylic acid (AA) and methacrylic acid (MAA). AA and MAA may also be used in combination. When AA and MAA are used in combination, their weight ratio (AA / MAA) is not particularly limited, and may be, for example, in the range of about 0.1 to 10. In some embodiments, the weight ratio (AA / MAA) may be, for example, greater than about 0.3, and may be greater than about 0.5. In addition, the weight ratio (AA / MAA) may be, for example, less than about 4, and may be less than about 3.
[0302] By using a monomer containing a carboxyl group, an aqueous liquid such as water can be quickly fused with the surface of the A layer. This can contribute to the reduction of the peel strength N2. The amount of the monomer containing a carboxyl group used can be, for example, more than 0.05% by weight of the total monomer component, more than 0.1% by weight, more than 0.3% by weight, more than 0.5% by weight, or more than 0.8% by weight. In addition, the proportion of the above-mentioned monomer containing a carboxyl group can be, for example, less than 15% by weight, less than 10% by weight, less than 5% by weight, less than 4.5% by weight, less than 3.5% by weight, less than 3.0% by weight, or less than 2.5% by weight. From the viewpoint of preventing the water used to measure the peel strength N2 from being absorbed by the A layer and causing insufficient water during peeling, it is preferred that the amount of the monomer containing a carboxyl group used is not too much.
[0303] In some embodiments, the above-mentioned monomer component may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesion and crosslinking density of the A layer can be adjusted to improve the peel strength N0. There is no particular restriction on the amount used when using a monomer containing a hydroxyl group, for example, it can be more than 0.01% by weight of the above-mentioned monomer component as a whole, it can be more than 0.1% by weight, it can be more than 0.5% by weight, it can be more than 1% by weight, it can be more than 5% by weight or more than 10% by weight. In addition, from the perspective of inhibiting excessive diffusion of water to the main body of the A layer, in some embodiments, the amount of the monomer containing a hydroxyl group is appropriate to be less than 40% by weight of the above-mentioned monomer component as a whole, it can be less than 30% by weight, it can be less than 20% by weight, it can be less than 10% by weight, less than 5% by weight or less than 3% by weight. The technology disclosed herein can also be appropriately implemented in a manner that substantially does not use a monomer containing a hydroxyl group as a monomer component of the A layer.
[0304] In some embodiments, the above-mentioned monomer component may include a monomer containing an alkoxysilyl group. The monomer containing an alkoxysilyl group is typically an ethylenically unsaturated compound having at least one (preferably more than two, for example, two or three) alkoxysilyl group in one molecule, and its specific example is as described above. The above-mentioned monomer containing an alkoxysilyl group can be used alone or in combination of two or more. By using a monomer containing an alkoxysilyl group, a cross-linked structure formed by a condensation reaction of a silanol group (silanol condensation) can be introduced into the adhesive layer (layer A). It should be noted that the monomer containing an alkoxysilyl group can also be considered as a silane coupling agent described later.
[0305] In the case where the monomer components constituting the A layer include monomers containing alkoxysilyl groups, the proportion of the monomers containing alkoxysilyl groups in the entire monomer components may be, for example, 0.005% by weight or more, and 0.01% by weight or more is appropriate. In addition, from the viewpoint of improving the adhesion to the adherend, the proportion of the monomers containing alkoxysilyl groups may be, for example, 0.5% by weight or less, 0.1% by weight or less, or 0.05% by weight or less.
[0306] In some preferred embodiments, the total ratio of alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate in the monomer components constituting layer A is limited to less than 20% by weight from the viewpoint of suppressing gelation. The total ratio of the alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate is more preferably less than 10% by weight, further preferably less than 3% by weight, and particularly preferably less than 1% by weight. In some embodiments, the monomer components do not substantially contain alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate (the content is 0 to 0.3% by weight).
[0307] Similarly, the monomer component constituting the acrylic polymer contained in layer A may be a monomer component containing an alkoxy group-containing monomer at a ratio of less than 20% by weight, or a monomer component not containing an alkoxy group-containing monomer. The amount of the alkoxy group-containing monomer in the above-mentioned monomer component is preferably less than 10% by weight, more preferably less than 3% by weight, and further preferably less than 1% by weight. In a particularly preferred embodiment, the monomer component constituting the above-mentioned acrylic polymer does not substantially contain an alkoxy group-containing monomer (the content is 0 to 0.3% by weight).
[0308] In addition, in some preferred embodiments, for the monomer components constituting layer A, the proportion of hydrophilic monomers (i.e., monomers containing carboxyl groups, monomers containing acid anhydride groups, monomers containing hydroxyl groups, monomers having nitrogen atoms, and monomers containing alkoxy groups) is set within a suitable range. Thus, water stripping properties can be ideally exerted. In this embodiment, it is appropriate that the proportion of the above-mentioned hydrophilic monomers in the monomer components of the acrylic polymer is less than 40% by weight (for example, less than 35% by weight), preferably less than 32% by weight, for example, less than 30% by weight, or less than 28% by weight. Although not particularly limited, the proportion of the above-mentioned hydrophilic monomers in the monomer components constituting layer A can be more than 1% by weight, can be more than 10% by weight, or can be more than 20% by weight.
[0309] In some embodiments, the monomer components constituting the A layer may include (meth)acrylates containing alicyclic hydrocarbon groups. Thus, the cohesive force of the adhesive can be increased, and the peel strength after photocuring can be increased. As (meth)acrylates containing alicyclic hydrocarbon groups, the (meth)acrylates containing alicyclic hydrocarbon groups exemplified above can be used, for example, cyclohexyl acrylate and isobornyl acrylate can be preferably used. There is no particular restriction on the amount used when using (meth)acrylates containing alicyclic hydrocarbon groups, for example, it can be more than 1% by weight, more than 3% by weight or more than 5% by weight of the above-mentioned monomer components as a whole. In some embodiments, the amount of (meth)acrylates containing alicyclic hydrocarbon groups used can be more than 10% by weight of the above-mentioned monomer components as a whole, and can be more than 15% by weight. It is appropriate that the upper limit of the amount of (meth)acrylates containing alicyclic hydrocarbon groups used is about 40% by weight or less, for example, it can be less than 30% by weight, and can be less than 25% by weight (for example, less than 15% by weight, and further less than 10% by weight).
[0310] The composition of the monomer component constituting the A layer can be set in such a manner that the glass transition temperature (Tg) obtained by the above-mentioned Fox formula based on the composition of the monomer component, that is, the Tg of the polymer corresponding to the monomer component becomes about -75°C or more and -10°C or less. In some embodiments, it is appropriate that the Tg of the above-mentioned polymer (for example, an acrylic polymer, typically an acrylic polymer) is below -20°C, preferably below -30°C, more preferably below -40°C, and further preferably below -50°C, for example, below -55°C. If the Tg of the above-mentioned polymer becomes lower, there is a tendency that the adhesion of the A layer to the substrate layer and the adhesion to the adherend are generally improved. According to the A layer with high adhesion to the substrate layer, it is easy to suppress the infiltration of water into the interface between the substrate layer and the A layer when the peeling of the adhesive layer is not desired. This will become advantageous from the viewpoint of improving the water resistance of the adhesive sheet. In addition, from the viewpoint of easily improving the peel strength N0, the Tg of the polymer can be, for example, above -70°C, and can be above -65°C. In some other embodiments, the Tg may be, for example, above -60°C, above -50°C, above -45°C, or above -40°C.
[0311] The polymer (for example, an acrylic polymer, typically an acrylic polymer) contained in the A layer of the PSA sheet disclosed herein is not particularly limited, but preferably has an SP value of 23.0 (MJ / m 3 ) 1 / 2 For an adhesive containing a polymer having such an SP value, by including a water affinity agent, for example, as described below, it is possible to achieve an adhesive having sufficient adhesive strength and excellent water removability. The above SP value is more preferably 21.0 (MJ / m 3 ) 1 / 2 Below (for example, 20.0 (MJ / m 3 ) 1 / 2 The lower limit of the SP value is not particularly limited, but is, for example, about 10.0 (MJ / m 3 ) 1 / 2 In addition, about 15.0 (MJ / m 3 ) 1 / 2 The above is appropriate, preferably 18.0 (MJ / m 3 ) 1 / 2 above.
[0312] The SP value of the above polymer can be calculated according to the Fedors calculation method [see "POLYMER ENG. & SCI. (Polymer Engineering and Science), Vol. 14, No. 2 (1974), pp. 148-154], that is, the following formula.
[0313] SP value δ=(Σ△e / Σ△v) 1 / 2
[0314] (In the above formula, Δe is the evaporation energy Δe of each atom or atomic group at 25°C, and Δv is the molar volume of each atom or atomic group at the same temperature.)
[0315] The polymer having the above-mentioned SP value can be obtained by appropriately determining the monomer composition based on the technical common sense of those skilled in the art.
[0316] The A layer of the adhesive sheet disclosed herein can be formed using an adhesive composition (hereinafter also referred to as "adhesive composition A") containing the monomer components of the composition as described above in the form of a polymer, an unpolymer (i.e., a form in which the polymerizable functional groups are not reacted), or a mixture thereof. The above-mentioned adhesive composition A can be in various forms such as a water-dispersible adhesive composition, a solvent-based adhesive composition, an active energy ray-curable adhesive composition, and a hot-melt adhesive composition.
[0317] In the polymerization, a known or commonly used thermal polymerization initiator or photopolymerization initiator can be used according to the polymerization method, polymerization form, etc. Such polymerization initiators can be used alone or in combination of two or more.
[0318] As the thermal polymerization initiator, an azo polymerization initiator, a peroxide initiator, a redox initiator formed by a combination of a peroxide and a reducing agent, a substituted ethane initiator, etc., which are exemplified as polymerization initiators that can be used in the polymerization of an acrylic primary polymer with respect to the polymer (PD), can be used. Among them, an azo polymerization initiator is preferred. It should be noted that the thermal polymerization can be preferably carried out at a temperature of, for example, about 20 to 100° C. (typically, 40 to 80° C.).
[0319] The photopolymerization initiator is not particularly limited, and ketal photoinitiators, acetophenone photoinitiators, benzoin ether photoinitiators, acylphosphine oxide photoinitiators, α-ketol photoinitiators, aromatic sulfonyl chloride photoinitiators, photoactive oxime photoinitiators, benzoin photoinitiators, benzyl photoinitiators, benzophenone photoinitiators, alkylphenone photoinitiators, thioxanthone photoinitiators, etc., which are exemplified as photoinitiators that can be contained in the D-type B layer, can be used.
[0320] The amount of such a thermal polymerization initiator or photopolymerization initiator used may be a normal amount used in accordance with the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example about 0.01 to 1 part by weight) of the polymerization initiator may be used relative to 100 parts by weight of the monomer to be polymerized.
[0321] In the above-mentioned polymerization, various chain transfer agents known in the past (which may also be considered as molecular weight regulators or polymerization degree regulators) may be used as needed. For example, one or more chain transfer agents selected from the various chain transfer agents exemplified as optional components of the adhesive composition that can be used to form the B-type B layer may be used. When a chain transfer agent is used, its amount used can be set in a manner that a resultant having a desired Mw can be obtained, and is not particularly limited. Generally, for example, about 0.01 to 1 part by weight is appropriate, preferably about 0.01 to 0.2 parts by weight, relative to 100 parts by weight of the monomer component supplied to the polymerization. The chain transfer agent may not be used.
[0322] The molecular weight of the polymer (e.g., acrylic polymer, typically acrylic polymer) obtained by appropriately using the above-mentioned various polymerization methods is not particularly limited and can be set within an appropriate range according to the required performance, etc. The weight average molecular weight (Mw) of the above-mentioned polymer is about 10×10 4 The above is suitable, for example, it can be about 15×10 4 From the viewpoint of achieving both cohesive force and adhesive force in a good balance, it is preferably higher than 30×10 4 In order to obtain good bonding reliability even in a high temperature environment, the polymer in some embodiments preferably has a 4 More than (typically about 50×10 4 Above, for example, about 55×10 4 The upper limit of the Mw of the above polymer may be about 500×10 4 Below (for example, about 150×10 4 The above Mw can be about 75×10 4 the following.
[0323] Some embodiments of the PSA sheet include a layer A formed of a water-dispersible PSA composition. A representative example of a water-dispersible PSA composition is an emulsion PSA composition. Typically, an emulsion PSA composition contains a polymer of a monomer component and, if necessary, an additive.
[0324] The emulsion polymerization of the monomer components is usually carried out in the presence of an emulsifier. There are no particular restrictions on the emulsifier used for emulsion polymerization, and known anionic emulsifiers, nonionic emulsifiers, etc. can be used. The emulsifier can be used alone or in combination of two or more.
[0325] As non-limiting examples of anionic emulsifiers, sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium polyoxyethylene lauryl sulfate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene alkylphenyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, sodium polyoxyethylene alkyl sulfosuccinate, etc. can be cited. As non-limiting examples of nonionic emulsifiers, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, polyoxyethylene polyoxypropylene block polymers, etc. can be cited. Emulsifiers with reactive functional groups (reactive emulsifiers) can also be used. As examples of reactive emulsifiers, free radical polymerizable emulsifiers of structures formed by introducing free radical polymerizable functional groups such as propylene groups and allyl ether groups into the above-mentioned anionic emulsifiers or nonionic emulsifiers can be cited.
[0326] The amount of the emulsifier used in the emulsion polymerization can be, for example, 0.2 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, or 1.5 parts by weight or more relative to 100 parts by weight of the monomer component. In addition, from the viewpoint of improving water resistance or transparency of the adhesive layer (layer A), in some embodiments, it is appropriate that the amount of the emulsifier used is 10 parts by weight or less relative to 100 parts by weight of the monomer component, preferably 5 parts by weight or less, and can be 3 parts by weight or less. It should be noted that the emulsifier used for emulsion polymerization here can also function as a water affinity agent for layer A.
[0327] According to the emulsion polymerization, a polymerization reaction solution in the form of an emulsion in which a polymer of a monomer component is dispersed in water can be obtained. The water-dispersible pressure-sensitive adhesive composition for forming the layer A can be preferably produced using the above-mentioned polymerization reaction solution.
[0328] In some preferred embodiments, layer A may be a layer formed of a solvent-based adhesive composition. This is advantageous from the viewpoint of water resistance and optical properties of the adhesive layer. Typically, a solvent-based adhesive composition contains a solution polymer of a monomer component and additives used as needed. The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from conventionally known organic solvents. For example, aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc., or a mixed solvent of two or more can be used. According to solution polymerization, a polymerization reaction liquid in the form of a polymer of a monomer component dissolved in a polymerization solvent can be obtained. The solvent-based adhesive composition for forming layer A can preferably be manufactured using the above-mentioned polymerization reaction liquid.
[0329] In some preferred embodiments, layer A may be a layer formed by an active energy ray-curable adhesive composition. As a preferred example of an active energy ray-curable adhesive composition, a photocurable adhesive composition may be cited. A photocurable adhesive composition has the advantage that even a thick adhesive layer can be easily formed. Among them, an ultraviolet-curable adhesive composition is preferred. The use of a photocurable adhesive is also advantageous from the perspective of optical properties.
[0330] Typically, the photocurable adhesive composition includes at least a portion of the monomer components of the composition (which may be a portion of the monomer type or a portion of the amount) in the form of a polymer. The polymerization method for forming the above-mentioned polymer is not particularly limited, and various polymerization methods known in the past can be appropriately adopted. For example, thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization (typically, carried out in the presence of a thermal polymerization initiator); photopolymerization by irradiation with light such as ultraviolet rays (typically, carried out in the presence of a photoinitiator); radiation polymerization by irradiation with radiation such as β rays and γ rays; and the like. Among them, photopolymerization is preferred.
[0331] Some preferred embodiments involve photocurable adhesive compositions comprising partial polymers of monomer components. Such partial polymers are typically mixtures of polymers derived from monomer components and unreacted monomers, preferably in the form of a slurry (a viscous liquid). Hereinafter, partial polymers of this nature are sometimes referred to as "monomer slurry" or simply "slurry". There are no particular restrictions on the polymerization method for partially polymerizing the monomer components, and various polymerization methods as described above can be appropriately selected and used. From the viewpoint of efficiency and simplicity, photopolymerization can be preferably used. According to photopolymerization, the polymerization conversion rate (monomer conversion) of the monomer components can be easily controlled by polymerization conditions such as the amount of light irradiation (light intensity).
[0332] The polymerization conversion rate of the monomer mixture in the above-mentioned partial polymer is not particularly limited. The above-mentioned polymerization conversion rate can be, for example, about 70 weight % or less, preferably about 60 weight % or less. From the viewpoint of the ease of preparation, coating properties, etc. of the adhesive composition containing the above-mentioned partial polymer, the above-mentioned polymerization conversion rate is appropriately about 50 weight % or less, preferably about 40 weight % or less (for example, about 35 weight % or less). The lower limit of the polymerization conversion rate is not particularly limited, and is typically about 1 weight % or more, and about 5 weight % or more is appropriately.
[0333] The adhesive composition containing the partial polymer of the monomer component can be obtained, for example, by the following method: using an appropriate polymerization method (such as photopolymerization method), partially polymerizing a monomer mixture containing the entire amount of the monomer components used to prepare the adhesive composition. In addition, the adhesive composition containing the partial polymer of the monomer component can be a mixture of a partial polymer or a complete polymer of a monomer mixture containing a part of the monomer components used to prepare the adhesive composition, and the remaining monomer components or their partial polymers. It should be noted that in this specification, the so-called "complete polymer" refers to a polymerization conversion rate higher than 95% by weight.
[0334] In the adhesive composition containing the above-mentioned partial polymer, other components (for example, photoinitiator, multifunctional monomer, crosslinking agent, hydrophilic agent, etc.) used as needed can be mixed. The method of mixing such other components is not particularly limited, for example, they can be included in the above-mentioned monomer mixture in advance, or can be added to the above-mentioned partial polymer.
[0335] (Crosslinking agent)
[0336] In layer A, a crosslinking agent may be used as needed. In other words, the adhesive composition for forming layer A may contain a crosslinking agent as needed. The crosslinking agent is typically contained in layer A in the form after the crosslinking reaction. Layer A formed by an adhesive composition containing a crosslinking agent typically contains a polymer (e.g., an acrylic polymer) formed by crosslinking the crosslinking agent. For example, layer A may be an adhesive layer containing an acrylic polymer formed by crosslinking the crosslinking agent. By using a crosslinking agent, the cohesive force of layer A can be appropriately adjusted.
[0337] The kind of crosslinking agent is not particularly limited, and can be selected from the crosslinking agent known in the past in the mode that the crosslinking agent plays a suitable crosslinking function in the adhesive layer according to the composition of the adhesive composition, for example. As usable crosslinking agent, isocyanate crosslinking agent, epoxy crosslinking agent, oxazoline crosslinking agent, aziridine crosslinking agent, carbodiimide crosslinking agent, melamine crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal chelate crosslinking agent, metal salt crosslinking agent, hydrazine crosslinking agent, amine crosslinking agent etc. can be exemplified. Peroxide can also be used as crosslinking agent. These crosslinking agents can be used alone or in combination of more than two.
[0338] The specific examples of the crosslinking agent that can be used in the adhesive composition for forming the A layer are substantially the same as the specific examples of the crosslinking agent that can be used in the adhesive composition for forming the D-type B layer described above, so repeated descriptions are omitted. In the water-dispersible adhesive composition, it is preferred to use a crosslinking agent that can be dissolved or dispersed in water.
[0339] In order to make the cross-linking reaction more effectively, a cross-linking catalyst can be used. As a cross-linking catalyst, metal cross-linking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, ferric acetylacetonate, butyl tin oxide, dioctyltin dilaurate, etc. can be exemplified. Among them, tin-based cross-linking catalysts such as dioctyltin dilaurate are preferably used. The amount of the cross-linking catalyst used is not particularly limited. Relative to 100 parts by weight of the monomer component (such as the monomer component of the acrylic polymer) contained in the adhesive composition A, the amount of the cross-linking catalyst used can be, for example, about 0.0001 parts by weight or more, about 0.001 parts by weight or more, about 0.005 parts by weight or more, and in addition, it can be about 1 part by weight or less, about 0.1 parts by weight or less, about 0.05 parts by weight or less, etc.
[0340] In the adhesive composition for forming the A layer, a compound that produces keto-enol tautomerism may be contained as a crosslinking retarder as desired. For example, in an adhesive composition containing an isocyanate crosslinking agent or an adhesive composition that can be used in combination with an isocyanate crosslinking agent, a compound that produces keto-enol tautomerism may be preferably used. Thus, the effect of extending the pot life of the adhesive composition can be exerted.
[0341] As compounds that produce keto-enol tautomerism, various β-dicarbonyl compounds can be used. As specific examples, β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetic acid esters such as methyl acetoacetate and ethyl acetoacetate; propionylacetic acid esters such as ethyl propionylacetate; isobutyrylacetic acid esters such as ethyl isobutyrylacetate; malonates such as methyl malonate and ethyl malonate; and the like. Among them, acetylacetone and acetoacetic acid esters can be mentioned as preferred compounds. The compound that produces keto-enol tautomerism can be used alone or in combination of two or more.
[0342] The amount of the compound that produces keto-enol tautomerism used can be, for example, more than 0.1 part by weight and less than 20 parts by weight, and is appropriately more than 0.5 part by weight and less than 15 parts by weight, relative to 100 parts by weight of the monomer component (for example, the monomer component of the acrylic polymer) contained in the adhesive composition, for example, more than 1 part by weight and less than 10 parts by weight, or more than 1 part by weight and less than 5 parts by weight.
[0343] (Water affinity agent)
[0344] The A layer in the technology disclosed herein may contain a hydrophilic agent as desired. By containing a hydrophilic agent in the A layer, it is possible to effectively reduce the peeling force by using an aqueous liquid such as water. The reason for this is not particularly limited, but it can be considered as follows: the hydrophilic agent generally has a hydrophilic region, and thus tends to be localized on the surface of the A layer, thereby playing a role in efficiently improving the water affinity of the surface of the A layer, and effectively reducing the peeling force when the A layer comes into contact with water.
[0345] As the hydrophilic agent, a hydrophilic agent that is liquid at room temperature (about 25° C.) is preferably used from the viewpoint of ease of preparation of the pressure-sensitive adhesive composition. The hydrophilic agent may be used alone or in combination of two or more.
[0346] In some embodiments, at least one compound A selected from a surfactant and a compound having a polyoxyalkylene skeleton can be used as a water affinity agent. As the surfactant and the compound having a polyoxyalkylene skeleton, one or more of the known surfactants and compounds having a polyoxyalkylene skeleton can be used without particular limitation. It should be noted that, among the above-mentioned surfactants, there are compounds having a polyoxyalkylene skeleton, and vice versa.
[0347] As the surfactant that can be used as compound A, known nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, nonionic surfactants are preferred. The surfactant can be used alone or in combination of two or more.
[0348] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan trioleate; polyoxyethylene glycerol ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like. These nonionic surfactants can be used alone or in combination of two or more.
[0349] Examples of the anionic surfactant include alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate (e.g., sodium dodecylbenzene sulfonate); alkyl sulfates such as lauryl sulfate (e.g., sodium lauryl sulfate, ammonium lauryl sulfate) and octadecyl sulfate; fatty acid salts; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate (e.g., sodium polyoxyethylene alkyl ether sulfate); polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate (e.g., Polyoxyethylene alkyl phenyl ether ammonium sulfate, polyoxyethylene alkyl phenyl ether sodium sulfate, etc.), polyoxyethylene styrenated phenyl ether sulfate and other polyoxyethylene alkyl ether phosphates; polyoxyethylene stearyl ether phosphate, polyoxyethylene lauryl ether phosphate and other polyoxyethylene alkyl ether phosphate esters; polyoxyethylene alkyl ether phosphate salts such as sodium salts and potassium salts of the above polyoxyethylene alkyl ether phosphates; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate (for example, sodium polyoxyethylene alkyl sulfosuccinate); polyoxyethylene alkyl ether acetate; and the like. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt), ammonium salt, amine salt, etc. The anionic surfactant may be used alone or in combination of two or more.
[0350] In some embodiments, for example, an anionic surfactant having at least one of a -POH group, a -COH group, and a -SOH group can be preferably used. Among them, a surfactant having a -POH group is preferred. Such a surfactant typically contains a phosphate structure, for example, a monoester of phosphoric acid (ROP(=O)(OH)2; wherein R is a univalent organic group), a diester ((RO)2P(=O)OH; wherein R is the same or different univalent organic group), a mixture of both a monoester and a diester, etc. As a preferred example of a surfactant having a -POH group, polyoxyethylene alkyl ether phosphate can be cited. The number of carbon atoms of the alkyl group in the polyoxyethylene alkyl ether phosphate can be, for example, 6 to 20, 8 to 20, 10 to 20, 12 to 20, or 14 to 20.
[0351] Examples of the cationic surfactant include polyetheramines such as polyoxyethylene laurylamine and polyoxyethylene stearylamine. The cationic surfactant may be used alone or in combination of two or more.
[0352] As compounds having a polyoxyalkylene skeleton that can be used as compound A, polyalkylene glycols such as polyethylene glycol (PEG) and polypropylene glycol (PPG) can be used; polyethers containing polyoxyethylene units, polyethers containing polyoxypropylene units, compounds containing oxyethylene units and oxypropylene units (the arrangement of these units can be random or block-shaped); their derivatives; and the like. In addition, compounds having a polyoxyalkylene skeleton in the above-mentioned surfactants can also be used. They can be used alone or in combination of two or more. Among them, it is preferred to use a compound containing a polyoxyethylene skeleton (also called a polyoxyethylene segment), and PEG is more preferred.
[0353] The molecular weight (chemical formula weight) of the compound having a polyoxyalkylene skeleton (e.g., polyethylene glycol) is not particularly limited, and for example, it is appropriate to be less than 1000. From the perspective of the preparation of the adhesive composition, it is preferably about 600 or less (e.g., 500 or less). The lower limit of the molecular weight of the compound having a polyoxyalkylene skeleton (e.g., polyethylene glycol) is not particularly limited, and a compound having a polyoxyalkylene skeleton having a molecular weight of about 100 or more (e.g., about 200 or more, and further about 300 or more) can be preferably used.
[0354] Other examples of water affinity agents include water-soluble polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, and polyacrylic acid. One water-soluble polymer may be used alone or in combination of two or more. In the technology disclosed herein, as the water affinity agent, one or more of compound A may be used, one or more of water-soluble polymers may be used, or they may be used in combination.
[0355] The HLB of the hydrophilic agent is not particularly limited, for example, it is 3 or more, about 6 or more is appropriate, and it can be 8 or more (for example, 9 or more). In some preferred embodiments, the HLB of the hydrophilic agent is 10 or more. As a result, there is a tendency to exhibit water stripping properties ideally. The above HLB is more preferably 11 or more, further preferably 12 or more, and particularly preferably 13 or more (for example, 14 or more). By including a hydrophilic agent (typically a surfactant) having an HLB in the above range in layer A, water stripping properties can be more effectively exhibited. The upper limit of the above HLB is 20 or less, for example, it can be 18 or less, it can be 16 or less, or it can be 15 or less.
[0356] It should be noted that the HLB in this specification is a hydrophile-lipophile balance value proposed by Griffin, which is a value indicating the degree of affinity between a surfactant and water and oil, and a numerical value between 0 and 20 indicating the ratio of hydrophilicity to lipophilicity. The definition of HLB is as described in WC Griffin: J. Soc. Cosmetic Chemists, 1, 311 (1949); Takahashi Kotomi, Nanba Yoshiro, Koike Motoo, Kobayashi Masao, "Surfactant Handbook", 3rd edition, published by Gongxue Book Co., Ltd., November 25, 1972, p179-182, etc. The water affinity agent having the above HLB can be selected based on the technical common sense of those skilled in the art with reference to the above references, etc. as needed.
[0357] Such a hydrophilic agent is preferably contained in a free form in layer A. As the hydrophilic agent, a hydrophilic agent that is liquid at room temperature (about 25° C.) can be preferably used from the viewpoint of the productivity of the pressure-sensitive adhesive composition.
[0358] The A layer containing a water affinity agent is typically formed of an adhesive composition A containing a water affinity agent. The adhesive composition A may be any of the above-mentioned water-dispersible adhesive composition, solvent-based adhesive composition, active energy ray-curable adhesive composition, hot melt adhesive composition, etc. In some preferred embodiments, the A layer containing a water affinity agent may be an adhesive layer formed of a photocurable or solvent-based adhesive composition A. In such an A layer, the effect of adding the water affinity agent can be ideally exerted. The A layer may also be photocurable.
[0359] The content of the hydrophilic agent in the A layer is not particularly limited and can be set in a manner that can appropriately exert the use effect of the hydrophilic agent. In some embodiments, the content of the hydrophilic agent can be, for example, 0.001 parts by weight or more, 0.01 parts by weight or more is appropriate, 0.03 parts by weight or more, 0.07 parts by weight or more, or 0.1 parts by weight or more, relative to 100 parts by weight of the monomer component (e.g., acrylic polymer) contained in the A layer. In some preferred embodiments, the content of the hydrophilic agent can be, for example, 0.2 parts by weight or more, from the perspective of obtaining a higher effect, it can be 0.5 parts by weight or more, 1.0 parts by weight or more, or 1.5 parts by weight or more. In addition, from the perspective of inhibiting excessive diffusion of water to the A layer body, in some embodiments, the amount of the hydrophilic agent used can be, for example, 20 parts by weight or less, 10 parts by weight or less is appropriate, preferably 5 parts by weight or less, or 3 parts by weight or less, relative to 100 parts by weight of the monomer component. From the viewpoint of improving the transparency of layer A, it is also preferred that the content of the hydrophilic agent is not too high. For example, in some embodiments, the content of the hydrophilic agent relative to 100 parts by weight of the monomer component may be less than 2 parts by weight, less than 1 part by weight, less than 0.7 parts by weight, less than 0.3 parts by weight, or less than 0.2 parts by weight. A hydrophilic agent having an HLB of 10 or more tends to exhibit good water-stripping properties even when used in small amounts.
[0360] (Tackifying resin)
[0361] Layer A may contain a tackifier resin. Examples of the tackifier resin include rosin-based tackifier resins (including rosin derivative tackifier resins), petroleum-based tackifier resins, terpene-based tackifier resins, phenol-based tackifier resins, ketone-based tackifier resins, etc. These may be used alone or in combination of two or more.
[0362] Examples of the rosin-based tackifier resin include gum rosin, wood rosin, tall oil rosin and the like, stabilized rosin (for example, stabilized rosin obtained by subjecting the above rosin to disproportionation or hydrogenation treatment), polymerized rosin (for example, a polymer of the above rosin, typically a dimer), and modified rosin (for example, unsaturated acid-modified rosin modified with an unsaturated acid such as maleic acid, fumaric acid, or (meth)acrylic acid).
[0363] Examples of the rosin derivative tackifier resin include esters of the rosin-based tackifier resin (e.g., rosin esters such as stabilized rosin ester and polymerized rosin ester), phenol-modified products of the rosin-based resin (phenol-modified rosin), and esters thereof (phenol-modified rosin ester).
[0364] Examples of the petroleum-based tackifying resin include aliphatic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins, alicyclic petroleum resins, and hydrogenated products thereof.
[0365] Examples of the terpene-based tackifier resin include α-pinene resin, β-pinene resin, aromatic modified terpene-based resin, and terpene phenol resin.
[0366] Examples of the ketone-based tackifier resin include ketone-based resins obtained by condensation of ketones (for example, aliphatic ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetophenone; alicyclic ketones such as cyclohexanone and methylcyclohexanone) and formaldehyde; and the like.
[0367] In some embodiments, as the tackifying resin, one or more selected from rosin-based tackifying resins, rosin derivative tackifying resins, and terpene phenol resins can be preferably used. Among them, rosin derivative tackifying resins are preferred, and preferred examples include rosin esters such as stabilized rosin esters and polymerized rosin esters.
[0368] In the water-dispersible adhesive composition, it is preferred to use a water-dispersible tackifying resin in the form of a tackifying resin as described above dispersed in an aqueous solvent. For example, by mixing an aqueous dispersion of an acrylic polymer with a water-dispersible tackifying resin, it is possible to easily prepare an adhesive composition containing these components in a desired ratio. In some embodiments, as a water-dispersible tackifying resin, from the perspective of environmental hygiene, it is preferred to use a water-dispersible tackifying resin that is at least substantially free of aromatic hydrocarbon solvents. It is more preferred to use a water-dispersible tackifying resin that is substantially free of aromatic hydrocarbon solvents and other organic solvents.
[0369] As commercially available products of water-dispersible tackifier resins containing rosin esters, for example, trade names "SUPER ESTER E-720", "SUPER ESTER E-730-55", "SUPER ESTER E-865NT" manufactured by Arakawa Chemical Industries, Ltd., and trade names "HARIESTER SK-90D", "HARIESTER SK-70D", "HARIESTER SK-70E", "NEOTALL 115E" manufactured by HARIMA CHEMICALS, INC., etc. In addition, as commercially available products of terpene-phenol resins (which may be in the form of water-dispersible terpene-phenol resins), trade names "TAMANOL E-100", "TAMANOLE-200", "TAMANOL E-200NT" manufactured by Arakawa Chemical Industries, Ltd., etc. may be mentioned.
[0370] The softening point of the tackifier resin is not particularly limited. From the viewpoint of suppressing the reduction of the cohesive force of the adhesive layer (A layer), it is preferred to use a tackifier resin with a softening point of 80°C or more. The softening point of the tackifier resin can be above 90°C, above 100°C, above 110°C, or above 120°C. A tackifier resin with a softening point of 130°C or above or 140°C can be used. In addition, from the viewpoints of transparency, adhesion to the substrate layer, adhesion to the adherend, etc., it is preferred to use a tackifier resin with a softening point of 200°C or below or 180°C or below. It should be noted that the softening point of the so-called tackifier resin here can be a nominal value recorded in a document, a catalogue, etc. In the absence of a nominal value, the softening point of the tackifier resin can be determined based on the softening point test method (ring and ball method) specified in JIS K5902 or JIS K2207.
[0371] Regarding the amount of tackifying resin used, from the viewpoint of suitably exerting its use effect, it is appropriate to use 1 part by weight or more relative to 100 parts by weight of the monomer components constituting the A layer, and it can be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more. In addition, from the viewpoint of realizing the adhesion and cohesion of the adherend in a well-balanced manner, the amount of tackifying resin used relative to 100 parts by weight of the monomer components can be, for example, 70 parts by weight or less, 50 parts by weight or less, or 40 parts by weight or less. Alternatively, it can also be a layer A that does not substantially contain a tackifying resin.
[0372] (Silane coupling agent)
[0373] In some embodiments, a silane coupling agent can be contained in layer A. By using a silane coupling agent, the peel strength of the adhesive sheet from an adherend (e.g., a glass plate) can be increased. Silane coupling agents can be used alone or in combination of two or more. Layer A containing a silane coupling agent can be suitably formed using an adhesive composition containing a silane coupling agent. In the adhesive composition, from the viewpoint of inhibiting gelation, the silane coupling agent is preferably contained in the above-mentioned adhesive composition in a free form. In addition, in some embodiments, the silane coupling agent can be contained in layer A in a free form. The silane coupling agent contained in layer A in such a form can effectively contribute to improving the peeling force. It should be noted that the so-called "free form" here refers to that the silane coupling agent is not chemically bonded to layer A or other components contained in the adhesive composition used to form the layer A.
[0374] Examples of the silane coupling agent include silicon compounds having an epoxy structure such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; silicon compounds containing an amino group such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane; 3-chloropropyltrimethoxysilane; trimethoxysilane containing an acetoacetyl group; silane coupling agents containing a (meth) acrylic group such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and silane coupling agents containing an isocyanate group such as 3-isocyanatepropyltriethoxysilane. Among them, 3-glycidoxypropyltrimethoxysilane and acetoacetyl group-containing trimethoxysilane are mentioned as preferable examples.
[0375] The amount of the silane coupling agent used can be set in a manner that the desired effect can be obtained, and there is no particular limitation. In some embodiments, the amount of the silane coupling agent used can be, for example, 0.001 parts by weight or more relative to 100 parts by weight of the monomer component of the polymer contained in the A layer. From the perspective of obtaining a higher effect, it can be 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.015 parts by weight or more. In addition, from the perspective of improving the adhesion to the substrate layer, in some embodiments, the amount of the silane coupling agent used can be, for example, 3 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less relative to 100 parts by weight of the monomer component constituting the A layer.
[0376] In addition, in the embodiment in which the monomer component contains an alkoxysilyl group-containing monomer, the alkoxysilyl group-containing monomer can be used as a part or all of the silane coupling agent contained in the A layer.
[0377] In addition, in some ways, the A layer may contain a compound T having an alkoxysilyl group and a hydrophobic part in the molecule as a compound other than the silane coupling agent as described above. Here, the alkoxysilyl group is selected from the group consisting of dimethoxysilyl, trimethoxysilyl, diethoxysilyl and triethoxysilyl. The alkoxysilyl group generates a silanol group that reacts with the hydroxyl group on the surface of the adherend by hydrolysis. Therefore, the alkoxysilyl group is a precursor of a group that reacts with the hydroxyl group. By making the A layer contain compound T, the peeling force of the adhesive sheet from the adherend can be increased by the reaction or interaction of the hydroxyl group on the adherend with the silanol group. In addition, the hydrophobic part of compound T is generally higher than the alkoxysilyl group in affinity with the base polymer (e.g., acrylic polymer) of the A layer. By selecting the hydrophobic part, the distribution and mobility of the A layer of compound T can be adjusted to control the rising property of water peeling force. Therefore, the compound T can function as a release regulator that affects the adhesiveness between the layer A and the adherend and the water-peelable property.
[0378] The hydrophobic part may be, for example, a hydrocarbon group, a hydrocarbon group having a chain ether bond, a hydrocarbon group having a carbonyl group, a hydrocarbon group having an ester bond, or a fluoride of these groups. The hydrocarbon group in these examples may be, for example, an alkyl group, a cycloalkyl group, an aryl group, an alkylcycloalkyl group, an aralkyl group, or the like. When the hydrocarbon group is an alkyl group, the number of carbon atoms of the alkyl group is preferably 6 or more, and more preferably 8 or more. The number of carbon atoms of the alkyl group may be, for example, 32 or less, 28 or less, 24 or less, or 20 or less. For example, C 8-18 Alkyltrialkoxysilane as compound T. As C 8-18 Non-limiting specific examples of alkyltrialkoxysilane include octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, hexadecyltrimethoxysilane and hexadecyltriethoxysilane. In addition, the carbon number of the cycloalkyl group, aryl group, alkylcycloalkyl group and aralkyl group can be about 6 to 20, for example.
[0379] The compound T may be used alone or in combination of two or more. A silane coupling agent and the compound T may also be used in combination.
[0380] (Acrylic oligomer)
[0381] The layer A may contain an acrylic oligomer. The acrylic oligomer contained in the layer A may be appropriately selected from the same components as those exemplified above as the components that may be contained in the layer B.
[0382] When the A layer contains an acrylic oligomer, its content is not particularly limited and can be set in a manner that can obtain the desired effect. In some embodiments, the amount of acrylic oligomer used can be, for example, 0.01% by weight or more of the total monomer components constituting the A layer. From the perspective of obtaining a higher effect, it can be 0.05% by weight or more, 0.1% by weight or more, or 0.2% by weight or more. In addition, from the perspective of the transparency of the adhesive layer, it is appropriate that the amount of acrylic oligomer used is usually less than 50% by weight of the total monomer components constituting the A layer, preferably less than 30% by weight, more preferably less than 25% by weight, less than 10% by weight, less than 5% by weight, less than 1% by weight, or less than 0.5% by weight. It is also possible not to use acrylic oligomers.
[0383] The adhesive composition A for forming the A layer can be an adhesive composition containing an acid or alkali (ammonia etc.) used for the purpose of pH adjustment etc. as required. As other optional components that can be contained in the composition, various common additives in the adhesive composition field such as colorants such as viscosity modifiers (such as thickeners), leveling agents, plasticizers, fillers, pigments, dyes, stabilizers, preservatives, anti-aging agents, etc. can be exemplified. Regarding such various additives, conventionally known additives can be used by conventional methods, and since the present invention is not particularly characterized, detailed description is omitted.
[0384] <Adhesive Sheet>
[0385] The adhesive layer constituting the adhesive sheet disclosed herein has a multilayer structure including an A layer and a B layer. The adhesive layer of the multilayer structure can be produced by laminating each preformed sub-adhesive layer. Alternatively, an adhesive composition for forming a second sub-adhesive layer (e.g., A layer) can be applied to a preformed first sub-adhesive layer (e.g., B layer), and the adhesive composition is cured to form a second adhesive layer.
[0386] The coating of the adhesive composition can be carried out using a commonly used coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, etc. For an adhesive sheet having a substrate, as a method of providing an adhesive layer on the substrate, a direct method of directly applying the adhesive composition to the substrate to form the adhesive layer can be used, and a transfer method of transferring the adhesive layer formed on the release surface to the substrate can also be used.
[0387] In the adhesive sheet disclosed herein, the thickness of the adhesive layer is not particularly limited, for example, it can be about 3μm to 2000μm. From the viewpoint of surface shape tracking (for example, step tracking) and the adhesion of the adherend, in some ways, the thickness of the adhesive layer can be, for example, 5μm or more, 10μm or more is appropriate, preferably 20μm or more, and more preferably 30μm or more. The thickness of the adhesive layer can be 50μm or more, can be greater than 50μm, can be 70μm or more, can be 100μm or more, can be 120μm or more. In addition, from the viewpoint of preventing the occurrence of slurry residue caused by the cohesive failure of the adhesive layer, in some ways, the thickness of the adhesive layer can be, for example, less than 1000μm, can be less than 700μm, can be less than 500μm, can be less than 300μm, and can be less than 200μm or less than 170μm. The technology disclosed herein can also be suitably implemented in the form of an adhesive sheet having an adhesive layer thickness of 130 μm or less, 90 μm or less, 60 μm or less, or 40 μm or less. In a preferred embodiment, the adhesive layer thickness can be, for example, 10 μm or more and 500 μm or less.
[0388] It should be noted that the thickness of the adhesive layer refers to the thickness from one surface of the adhesive layer (i.e., the surface on the A layer side) to the surface on the opposite side of the adhesive layer. From the viewpoint of surface conformability, the adhesive layer disclosed herein is preferably a multilayer structure that does not contain a layer other than the adhesive layer (e.g., a resin film).
[0389] The thickness of the A layer constituting the adhesive layer can be, for example, 50 μm or less, 45 μm or less, 35 μm or less, 25 μm or less, or 20 μm or less. From the perspective of easily and appropriately exerting the effect of the B layer formed on the back side of the A layer having photocrosslinking properties (for example, the simultaneous realization of the surface shape tracking property before photocrosslinking and the bonding reliability after photocrosslinking), in some embodiments, it is advantageous for the thickness of the A layer to be 15 μm or less, preferably 10 μm or less, more preferably less than 10 μm, for example, 7 μm or less. In particular, for the mode in which the A layer is formed by the water-dispersible adhesive component and the mode in which the A layer contains a hydrophilic agent, it is also preferred that the thickness of the A layer is not too large from the perspective of improving the water resistance reliability of the adhesive layer and improving the transparency of the adhesive layer. In addition, from the perspective of the ease of forming the A layer and the ease of appropriately exerting the effect obtained by the A layer (for example, the imparting of water peeling properties or its improvement), the thickness of the A layer is usually appropriate to be 0.5 μm or more, and can be 1 μm or more, 2 μm or more, or 3 μm or more.
[0390] The thickness of the B layer constituting the adhesive layer may be, for example, 5 μm or more, 10 μm or more, or 20 μm or more. From the viewpoint of the surface shape followability (for example, step followability) of the adhesive layer before the photocrosslinking of the B layer, in some embodiments, it is advantageous for the thickness of the B layer to be 30 μm or more, preferably 50 μm or more, 70 μm or more, or 100 μm or more. In addition, from the viewpoint of the ease of formation, cohesion, and photocrosslinking of the B layer, the thickness of the B layer may be, for example, 700 μm or less, 500 μm or less, 300 μm or less, 200 μm or less, or 170 μm or less.
[0391] In some embodiments, from the viewpoint of easily and appropriately exerting the effect obtained by the A layer, the thickness of the A layer in the overall thickness of the adhesive layer can be, for example, 0.1% or more, 0.5% or more, 1% or more, or 2% or more. In addition, from the viewpoint of the surface shape followability of the adhesive layer before the photo-crosslinking of the B layer, in some embodiments, the thickness of the A layer in the overall thickness of the adhesive layer is appropriately 90% or less, preferably 70% or less, more preferably 50% or less, 25% or less, 10% or less, or 5% or less.
[0392] (Photo-crosslinking treatment)
[0393] The adhesive sheet disclosed herein is configured in a manner that can improve deformation resistance by crosslinking the photocrosslinkable polymer contained in the B layer constituting the adhesive layer. The photocrosslinking of the B layer can be performed by irradiating active energy rays. The irradiation conditions of the active energy rays can be set in a manner that enables the photocrosslinking of the B layer to be appropriately performed. For an adhesive sheet having an adhesive layer comprising a B-type B layer, it is preferably irradiated with ultraviolet rays containing a wavelength component that can excite a benzophenone structure (for example, ultraviolet rays containing a component having a wavelength lower than 300nm).
[0394] In the technology disclosed herein, as a light source for ultraviolet irradiation treatment (photocrosslinking treatment) performed in the evaluation of characteristics or performance such as peel strength N0, N2, shear storage elastic modulus, gel fraction, and durability, a high-pressure mercury lamp (for example, an illuminance of 300 mW / cm 2 The ultraviolet irradiation time is set so that the photo-crosslinking reaction proceeds sufficiently. For example, the accumulated light intensity can be set to about 1000 mJ / cm 2 ~20000mJ / cm 2 The ultraviolet irradiation treatment is performed in a left-right manner.
[0395] When evaluating the characteristics or performance of a pressure-sensitive adhesive sheet having a type B layer, the ultraviolet irradiation treatment may be performed at an illuminance of 300 mW / cm 2 The high-pressure mercury lamp (industrial UV tester manufactured by TOPCON, trade name: UVR-T1, measured using the light receiving unit model UD-T25) was used to achieve a cumulative light intensity of 10,000 mJ / cm 2 way.
[0396] In addition, the ultraviolet irradiation treatment performed in the characteristic evaluation or performance evaluation of the adhesive sheet having the D-type B layer can be performed using an illuminance of 300 mW / cm 2 The high-pressure mercury lamp (industrial UV tester manufactured by TOPCON, trade name: UVR-T1, measured using the light receiving unit model UD-T36) was used to achieve a cumulative light intensity of 3000 mJ / cm 2 way.
[0397] (Peel strength N0)
[0398] In some embodiments of the adhesive sheet disclosed herein, the peel strength N0 measured by the above-mentioned measurement step (more specifically, the peel strength N0 measured by the method described in the embodiment described later) can be, for example, about 1.5N / 10mm or more, preferably about 2.0N / 10mm or more. From the viewpoint of improving the bonding reliability, the above-mentioned peel strength is, for example, preferably about 2.2N / 10mm or more, and more preferably about 2.5N / 10mm or more. In the adhesive sheet involved in one embodiment, the above-mentioned peel strength can be about 3.0N / 10mm or more, about 4.0N / 10mm or more, about 5.0N / 10mm or more, and about 6.0N / 10mm or more. The upper limit of the peel strength is not particularly limited, for example, it can be less than 25N / 10mm, less than 20N / 10mm, less than 15N / 10mm or less than 10N / 10mm.
[0399] (Peel strength N2)
[0400] In some embodiments of the adhesive sheet disclosed herein, the peel strength N2 measured by the above-mentioned measurement step (more specifically, the peel strength N2 measured by the method described in the examples described later) can be, for example, less than about 1.5 N / 10 mm. From the perspective of reprocessability by water peeling, the above-mentioned peel strength N2 can be, for example, less than about 1.2 N / 10 mm, can be less than 1.0 N / 10 mm, can be less than 0.8 N / 10 mm, can be less than 0.5 N / 10 mm.
[0401] (Water peeling force reduction rate)
[0402] In some aspects of the PSA sheet disclosed herein, the water peel strength reduction rate of the PSA sheet calculated from the peel strength N0 and the peel strength N2 by the following formula may be, for example, about 40% or more.
[0403] Water peeling force reduction rate [%] = (1-(N2 / N0)) × 100
[0404] For adhesive sheets with a high water peeling force reduction rate, the load applied to the adherend during peeling can be significantly reduced by using an aqueous liquid such as water for peeling. For example, by introducing a small amount of aqueous liquid into the interface between the adhesive sheet and the adherend, the peel strength of the adhesive sheet from the adherend can be greatly reduced. Utilizing this property, it is possible to simultaneously achieve the performance of suppressing the positional offset, floating, and good reprocessability of the adhesive sheet attached to the adherend. In some embodiments, it is appropriate for the water peeling force reduction rate to be 50% or more, preferably 60% or more, for example, 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more. The water peeling force reduction rate is in principle less than 100%, typically less than 100%.
[0405] (Haze value)
[0406] In the technology disclosed herein, the haze value of the adhesive sheet (which may be an adhesive sheet formed by an adhesive layer) is appropriately about 10% or less, and may be about 5% or less (for example, about 3% or less). In some embodiments, the haze value of the adhesive sheet is preferably 1.0% or less. Such a highly transparent adhesive sheet is suitable for optical applications requiring high light transmittance. The haze value of the adhesive sheet may be lower than 1.0%, lower than 0.7%, and may be lower than 0.5% (for example, 0 to 0.5%).
[0407] Here, the so-called "haze value" refers to the ratio of diffused transmitted light to the total transmitted light when the object to be measured is irradiated with visible light. It is also called haze value. The haze value can be expressed by the following formula.
[0408] Th[%]=Td / Tt×100
[0409] In the above formula, Th is the haze value [%], Td is the scattered light transmittance, and Tt is the total light transmittance.
[0410] The haze value can be measured using a haze meter (for example, "MR-100" manufactured by Murakami Color Research Laboratory). The haze value can be adjusted by, for example, selecting the composition and thickness of the pressure-sensitive adhesive layer.
[0411] <Base material>
[0412] The adhesive sheet involved in some methods can be a form of an adhesive sheet with a substrate including a substrate bonded to an adhesive layer. The material of the substrate is not particularly limited and can be appropriately selected according to the purpose of use, the method of use, etc. of the adhesive sheet. As non-limiting examples of usable substrates, there can be cited plastic films (resin films) such as polyolefin films with polyolefins such as polypropylene and ethylene-propylene copolymer as the main component, polyester films with polyesters such as polyethylene terephthalate and polybutylene terephthalate as the main component, and polyvinyl chloride films with polyvinyl chloride as the main component; foam sheets formed by foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; fabrics and non-woven fabrics formed by various fibrous substances (which can be natural fibers such as hemp and cotton, synthetic fibers such as polyester and vinylon, and semi-synthetic fibers such as acetate, etc.) alone or in a blend; paper such as Japanese paper, high-quality paper, kraft paper, and crepe paper; metal foils such as aluminum foil and copper foil; and so on. It can be a substrate composed of them. Examples of such a composite structure substrate include a substrate having a structure in which a metal foil and the above-mentioned plastic film are laminated, and a plastic sheet reinforced with inorganic fibers such as glass cloth.
[0413] As the substrate of the adhesive sheet disclosed herein, various films (hereinafter, also referred to as support films) can be preferably used. The above-mentioned support film can be a porous film such as a foam film, a non-woven fabric sheet, etc., or a non-porous film, or a film having a structure in which a porous layer and a non-porous layer are stacked. In some embodiments, as the above-mentioned support film, a film containing a (self-supporting or non-dependent) resin film that can independently maintain a shape as a base film can be preferably used. The so-called "resin film" here is a non-porous structure, typically referring to a resin film that is substantially free of bubbles (non-porous). Therefore, the above-mentioned resin film is a concept distinguished from a foam film and a non-woven fabric. The above-mentioned resin film can be a single-layer structure, or a multilayer structure (such as a three-layer structure) of more than two layers.
[0414] As the resin material constituting the resin film, for example, polyester, polyolefin, polycycloolefin derived from a monomer having an aliphatic ring structure such as a norbornene structure, polyamide (PA) such as nylon 6, nylon 66, partially aromatic polyamide, polyimide (PI) such as transparent polyimide (CPI), polyamideimide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), polystyrene, ABS resin, polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene (PTFE) and other fluororesins, acrylic resins such as polymethyl methacrylate, cellulose diacetate, cellulose triacetate (TAC) and other cellulose polymers, vinyl butyral polymers, arylate polymers, polyoxymethylene polymers, epoxy polymers and the like resins can be used. The above-mentioned resin film can be a resin film formed using a resin material containing only one such resin, or a resin film formed using a resin material obtained by blending two or more of them. The resin film may be unstretched or stretched (for example, uniaxially stretched or biaxially stretched).
[0415] Preferred examples of the resin material constituting the resin film include polyester resins, PPS resins, polyolefin resins, and polyimide resins. Here, polyester resins refer to resins containing polyester at a ratio higher than 50% by weight. Similarly, PPS resins refer to resins containing PPS at a ratio higher than 50% by weight, polyolefin resins refer to resins containing polyolefins at a ratio higher than 50% by weight, and polyimide resins refer to resins containing polyimides at a ratio higher than 50% by weight.
[0416] As the polyester resin, typically, a polyester resin containing a polyester obtained by polycondensing a dicarboxylic acid and a diol as a main component can be used. Specific examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate, etc.
[0417] As the polyolefin resin, one polyolefin can be used alone, or two or more polyolefins can be used in combination. The polyolefin can be, for example, a homopolymer of an α-olefin, a copolymer of two or more α-olefins, a copolymer of one or more α-olefins and other vinyl monomers, etc. As specific examples, ethylene-propylene copolymers such as polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, ethylene-ethyl acrylate copolymers, etc. can be cited. Low-density (LD) polyolefins and high-density (HD) polyolefins can both be used. Examples of polyolefin resin films include unstretched polypropylene (CPP) films, biaxially stretched polypropylene (OPP) films, low-density polyethylene (LDPE) films, linear low-density polyethylene (LLDPE) films, medium-density polyethylene (MDPE) films, high-density polyethylene (HDPE) films, polyethylene (PE) films obtained by blending two or more polyethylene (PE), and PP / PE blended films obtained by blending polypropylene (PP) and polyethylene (PE).
[0418] As a specific example of a resin film that can be preferably used as a substrate, PET film, PEN film, PPS film, PEEK film, CPI film, CPP film and OPP film can be mentioned. From the perspective of strength, as a preferred example, PET film, PEN film, PPS film, PEEK film, CPI film can be mentioned. From the perspective of ease of acquisition, dimensional stability, optical properties, etc., as a preferred example, PET film, CPI film, TAC film can be mentioned.
[0419] In the resin film, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, anti-blocking agents, etc. can be added as needed. The amount of the additives is not particularly limited and can be appropriately set according to the use of the adhesive sheet, etc.
[0420] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.
[0421] The substrate may be substantially composed of such a resin film. Alternatively, the substrate may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printed layer for giving a desired appearance to the substrate or adhesive sheet, a laminated layer, an antistatic layer, a primer layer, a peeling layer and other surface treatment layers. In addition, the substrate may be an optical component (e.g., an optical film) described later.
[0422] The thickness of the substrate is not particularly limited and can be selected according to the purpose of use and the method of use of the adhesive sheet. The thickness of the substrate can be, for example, less than 1000 μm, less than 500 μm, less than 100 μm, less than 70 μm, less than 50 μm, less than 25 μm, less than 10 μm, or less than 5 μm. If the thickness of the substrate becomes smaller, the softness of the adhesive sheet and the tendency to follow the surface shape of the adherend are improved. In addition, from the viewpoint of operability, processability, etc., the thickness of the substrate can be, for example, more than 2 μm, greater than 5 μm or greater than 10 μm. In some ways, the thickness of the substrate can be, for example, more than 20 μm, more than 35 μm, or more than 55 μm.
[0423] For the surface of one side bonded to the adhesive layer in the substrate, corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, coating of primer (primer), antistatic treatment and other previously known surface treatments can be implemented as needed. Such surface treatment can be a treatment for improving the adhesion between the substrate and the adhesive layer, in other words, the anchoring of the adhesive layer to the substrate. The composition of the primer is not particularly limited and can be appropriately selected from known primer compositions. The thickness of the primer layer is not particularly limited, and is usually about 0.01 μm to 1 μm, preferably about 0.1 μm to 1 μm.
[0424] For the surface of the substrate that is opposite to the side joined to the adhesive layer (hereinafter, also referred to as the back side), a peeling treatment, a treatment to improve adhesion or cohesion, an antistatic treatment, or other surface treatments known in the past may be applied as needed. For example, by surface treating the back side of the substrate with a peeling agent, the unwinding force of the adhesive sheet wound into a roll can be reduced. As the peeling agent, a silicone peeling agent, a long-chain alkyl peeling agent, an olefin peeling agent, a fluorine peeling agent, a fatty acid amide peeling agent, molybdenum sulfide, silica powder, etc. can be used.
[0425] <Laminate Manufacturing Method>
[0426] The adhesive sheet disclosed herein can be preferably used in a manner that the adhesive layer (typically the A layer side of the adhesive layer) is laminated on a member as an adherend and the B layer of the adhesive layer is photocrosslinked. Thus, a laminate formed by bonding the adhesive layer to the adherend with good reliability can be manufactured. Therefore, according to this specification, a laminate manufacturing method can be provided that sequentially includes the following steps: attaching any adhesive sheet disclosed herein to an adherend; and irradiating the adhesive sheet with active energy rays to photocrosslink the B layer of the adhesive layer.
[0427] The photo-crosslinking of the B layer can be performed by irradiating active energy rays. The irradiation conditions of the active energy rays can be set in a manner that allows the photo-crosslinking of the B layer to be appropriately performed. For an adhesive sheet having an adhesive layer including a type B layer, it is preferably irradiated with ultraviolet rays containing a wavelength component that can excite a benzophenone structure (for example, ultraviolet rays containing a component with a wavelength of less than 300 nm).
[0428] The adhesive sheet disclosed herein can be used in a manner in which its adhesive layer (typically the A layer side of the adhesive layer) is laminated on a surface having a step difference. The adhesive layer possessed by the above-mentioned adhesive sheet can exhibit good surface shape tracking (step difference tracking) to the surface of the adherend having a step difference before the B layer is photocrosslinked. After laminating the adhesive layer, by photocrosslinking the B layer of the adhesive layer, a highly reliable joint can be formed. The above-mentioned step difference can be, for example, a printed layer provided on the surface of the above-mentioned adherend. The height of the above-mentioned step difference can be, for example, more than 5 μm, more than 10 μm, more than 20 μm, or more than 30 μm. The height of the above-mentioned step difference can be, for example, less than 100 μm, preferably less than 70 μm.
[0429] <Water contact angle>
[0430] The adhesive sheet disclosed herein can be preferably used in a manner of being attached to a hydrophilic surface showing a contact angle with distilled water of, for example, less than 60 degrees, preferably less than 50 degrees. In some ways, the contact angle of the above-mentioned bonding surface can be, for example, less than 45 degrees, less than 40 degrees, less than 35 degrees, or less than 30 degrees. If the contact angle of the above-mentioned bonding surface becomes smaller, water easily wets and diffuses along the bonding surface, and there is a tendency for the water peelability of the adhesive sheet to be improved. This is preferred from the viewpoint of improving the reprocessability when the above-mentioned bonding surface is bonded to the above-mentioned adhesive sheet and a component with an adhesive sheet is made. In addition, for such a surface with high hydrophilicity, for example, in the manner of using compound S as a peeling force enhancer, the effect of improving bonding reliability (for example, water-resistant reliability) brought by the compound S can be ideally exerted.
[0431] It should be noted that the contact angle of the above-mentioned bonding surface is less than the above-mentioned arbitrary angle at least during the period of laminating the adhesive sheet (for example, 30 minutes before laminating), and the reprocessability improvement effect brought about by the contact angle being less than the prescribed value can be exerted. The lower limit of the contact angle is 0 degrees in principle. In some embodiments, the contact angle of the above-mentioned bonding surface can be greater than 0 degrees, can be more than 1 degree, can be more than 3 degrees, and can be more than 5 degrees.
[0432] The contact angle between the bonding surface of the component and distilled water was measured as follows. That is, the contact angle was measured by the drop method using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., trade name "DMo-501 model", control box "DMC-2", control and analysis software "FAMAS (version 5.0.30)") under an atmosphere of 23°C and 50% RH. The amount of distilled water added was 2 μL, and the contact angle was calculated by the θ / 2 method based on the image after 5 seconds of dropping (implemented with N5).
[0433] In order to reduce the contact angle with distilled water, the bonding surface of the component can be subjected to a hydrophilic treatment. As the hydrophilic treatment, for example, a treatment that helps to improve the hydrophilicity, such as a corona treatment, a plasma treatment, a treatment to form a hydrophilic layer, etc., can be cited. The apparatus and treatment conditions used in the corona treatment and the plasma treatment can be set based on the previously known technology in a manner that a bonding surface showing a desired contact angle can be obtained.
[0434] The hydrophilic layer formation process may be a process for forming a hydrophilic coating layer. For the formation of the hydrophilic coating layer, a coating agent that can obtain a bonding surface showing a desired contact angle can be appropriately selected from known coating agents and used by conventional methods. The thickness of the hydrophilic coating layer may be, for example, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, and, for example, 10 μm or less, 5 μm or less, or 2 μm or less.
[0435] The above-mentioned hydrophilic layer formation treatment can be a treatment for forming a hydrophilic layer containing an inorganic material. By making the hydrophilic layer contain an inorganic material, it is easy to obtain good water stripping properties. As an inorganic material, a material that can form a hydrophilic surface can be used from various metal materials, inorganic oxides and other inorganic compounds containing transition metal elements, metalloid elements, simple substances, alloys. The above-mentioned inorganic material can be used alone or in combination with more than two kinds. As a preferred example of an inorganic material, titanium oxide, zinc oxide, magnesium oxide, aluminum oxide, silicon oxide, cerium oxide, chromium oxide, zirconium oxide, manganese oxide, zinc oxide, iron oxide, tin oxide, niobium oxide and other oxides (inorganic oxides, typically metal oxides) can be cited. Among them, as a preferred inorganic material, inorganic oxides such as silicon oxide can be used. In the hydrophilic layer, in addition to inorganic materials, various organic materials including organic polymer compounds that can be used as coating agents and binders may be included or not included.
[0436] The amount of inorganic material (e.g., inorganic oxide such as silicon oxide) in the hydrophilic layer may be an appropriate amount to obtain the target hydrophilic surface, and is not limited to a specific range. For example, the content of inorganic material in the hydrophilic layer may be about 30% by weight or more, about 50% by weight or more (e.g., higher than 50% by weight) is appropriate, and may be about 70% by weight or more. In some preferred embodiments, the content of inorganic material in the hydrophilic layer is about 90 to 100% by weight (e.g., about 95% by weight or more).
[0437] In some preferred embodiments, silicon oxide (typically SiO X The proportion of the inorganic oxide (typically silicon oxide) in the above-mentioned inorganic material can be an appropriate amount to obtain the target hydrophilic surface, and is not limited to a specific range. For example, it can be about 30% by weight or more, about 50% by weight or more (for example, higher than 50% by weight) is appropriate, and it can be about 70% by weight or more. In some preferred embodiments, the proportion of the inorganic oxide (typically silicon oxide) in the above-mentioned inorganic material is about 90-100% by weight (for example, about 95% by weight or more).
[0438] The formation method of the above-mentioned hydrophilic layer is not particularly limited, and can be formed by a suitable method according to the target thickness, etc. For example, an inorganic material formed in a layer by a known film forming method such as vacuum evaporation, sputtering, or plating can be used as a hydrophilic layer. In the case of using an inorganic compound as an inorganic material, various evaporation methods can be used, for example, physical evaporation methods (PVD) such as vacuum evaporation, sputtering, and ion plating, chemical evaporation methods (CVD) such as atomic layer deposition layers, etc. can be used. For the formation of a coating layer comprising an inorganic polymer such as polysiloxane, a coating agent that can be appropriately selected from known coating agents to obtain a surface showing a desired water contact angle, and used using a conventional method.
[0439] <Peeling method>
[0440] According to the present description, a method for peeling a PSA sheet attached to an adherend is provided. This peeling method is suitable as a method for peeling any PSA sheet disclosed herein.
[0441] The above-mentioned stripping method includes a water stripping process, in which, at the peeling front of the above-mentioned adhesive sheet from the above-mentioned adherend, in the state where there is an aqueous liquid at the interface of the above-mentioned adherend and the above-mentioned adhesive sheet, the above-mentioned aqueous liquid is allowed to enter the above-mentioned interface to follow the movement of the above-mentioned peeling front, while the above-mentioned adhesive sheet is peeled off from the above-mentioned adherend. The so-called peeling front here refers to the part where the above-mentioned adhesive sheet begins to separate from the above-mentioned adherend when the adhesive sheet is peeled off from the adherend. According to the above-mentioned water stripping process, the above-mentioned aqueous liquid can be effectively used to peel the adhesive sheet from the adherend. As an aqueous liquid, a liquid containing a small amount of additives as required in water or a mixed solvent with water as the main component can be used. As a solvent other than water constituting the above-mentioned mixed solvent, a lower alcohol (such as ethanol), a lower ketone (such as acetone), etc. that can be uniformly mixed with water can be used. As the above-mentioned additive, a known surfactant can be used. From the viewpoint of avoiding contamination of the adherend, in some ways, it is preferred to use an aqueous liquid that does not substantially contain additives. From the viewpoint of environmental hygiene, it is particularly preferred to use water as the aqueous liquid. The water is not particularly limited, and in consideration of the purity required for the application, availability, etc., for example, distilled water, ion-exchanged water, tap water, etc. can be used.
[0442] In some embodiments, the stripping method may be preferably performed in the following manner: supplying an aqueous liquid to an adherend near the outer edge of an adhesive sheet attached to an adherend, so that the aqueous liquid enters one end of the interface between the adhesive sheet and the adherend from the outer edge of the adhesive sheet, and then, without supplying new water (i.e., only using the aqueous liquid supplied to the adherend before the start of stripping), the adhesive sheet is stripped. In some other embodiments, the stripping method may be preferably performed in the following manner: supplying an aqueous liquid to the portion where the remaining adhesive sheet begins to separate from the adherend when a portion of the adhesive sheet attached to the adherend (typically a portion connected to the outer edge of the adhesive sheet) floats from the adherend, and the adhesive sheet is stripped without supplying new water. It should be noted that if the water entering the interface between the adhesive sheet and the adherend following the movement of the stripping front dries up midway during the water stripping process, additional water may be supplied intermittently or continuously after the start of the water stripping process. For example, when the adherend is water-absorbent or when aqueous liquid is likely to remain on the adherend surface or adhesive surface after peeling, it is preferable to additionally supply water after the water peeling step is started.
[0443] The amount of the aqueous liquid supplied before the start of stripping is not particularly limited as long as it is an amount that can introduce the above-mentioned aqueous liquid to the interface between the adhesive sheet and the adherend. The amount of the above-mentioned aqueous liquid can be, for example, more than 5 μL, usually more than 10 μL is appropriate, and can be more than 20 μL. In addition, the upper limit of the amount of the above-mentioned aqueous liquid is not particularly limited. In some ways, from the perspective of improving workability, the amount of the above-mentioned aqueous liquid can be, for example, less than 10 mL, less than 5 mL, less than 1 mL, less than 0.5 mL, less than 0.1 mL, or less than 0.05 mL. By reducing the amount of the above-mentioned aqueous liquid, the operation of removing the above-mentioned aqueous liquid by drying, wiping off, etc. after stripping the adhesive sheet can be omitted or simplified.
[0444] The operation of making the aqueous liquid enter the interface between the adhesive sheet and the adherend from the outer edge of the adhesive sheet at the beginning of the peeling can be performed in the following manner: insert the front end of a tool such as a cutting knife or a needle into the interface at the outer edge of the adhesive sheet; grab the outer edge of the adhesive sheet with a hook or claw and lift it; attach a strong adhesive tape, a suction cup, etc. to the back near the outer edge of the adhesive sheet, and lift one end of the adhesive sheet; etc. By forcibly entering the above interface from the outer edge of the adhesive sheet, a state in which an aqueous liquid exists at the interface between the adherend and the above adhesive sheet can be efficiently formed. In addition, it is possible to simultaneously achieve: good water peelability after forming the peeling starting point by forcibly entering the interface with the aqueous liquid; and high water resistance reliability when the operation is not performed. It should be noted that the above-mentioned operation of forming the peeling starting point can also be used as an operation to intentionally form a state in which a part of the adhesive sheet attached to the adherend (typically a part connected to the outer edge of the adhesive sheet) floats from the adherend before supplying the aqueous liquid.
[0445] The water stripping process involved in some methods can be preferably implemented in a manner that allows the above-mentioned stripping front to move at a speed of more than 10 mm / minute. In terms of moving the stripping front at a speed of more than 10 mm / minute, for example, under the condition that the stripping angle is 180 degrees, it is equivalent to stripping the adhesive sheet at a tensile speed of more than 20 mm / minute. The speed at which the above-mentioned stripping front moves can be, for example, more than 50 mm / minute, more than 150 mm / minute, more than 300 mm / minute, or more than 500 mm / minute. According to the stripping method disclosed herein, while the above-mentioned aqueous liquid is allowed to enter the above-mentioned interface, the above-mentioned adhesive sheet is stripped from the above-mentioned adherend, thereby, even at such a faster stripping speed, good water stripping properties can be exerted. There is no particular upper limit on the speed at which the stripping front moves. The speed at which the above-mentioned stripping front moves can be, for example, less than 1000 mm / minute.
[0446] The peeling method disclosed herein can be implemented, for example, in the following manner: the peeling area of the adhesive sheet is, for example, 50 cm2 relative to the volume of 10 μL of the aqueous liquid (for example, water) used in the method. 2 Above, preferably 100cm 2 above.
[0447] The stripping method disclosed herein can be preferably applied to the stripping of an adhesive sheet attached to a non-water-absorbing smooth surface such as a glass plate, a metal plate, a resin plate, etc. In addition, the stripping method disclosed herein can be preferably used as a method for stripping an adhesive sheet from any of the above-mentioned optical components. Among them, it is suitable as a method for stripping an adhesive sheet attached to a glass plate such as a polarizing plate (which can be a polarizing plate on which a hydrophilic treatment is applied to the surface on which the adhesive sheet is attached), alkaline glass, and alkali-free glass.
[0448] <Application>
[0449] The use of the adhesive sheet disclosed herein is not particularly limited and can be used for various purposes. For example, the adhesive sheet disclosed herein can be used for fixing, joining, molding, decoration, protection, support and other purposes of components constituting various products. The material constituting at least the surface of the above-mentioned component can be, for example, glass such as alkaline glass and alkali-free glass; metal materials such as stainless steel (SUS) and aluminum; ceramic materials such as alumina and silica; resin materials such as acrylic resin, ABS resin, polycarbonate resin, polystyrene resin, transparent polyimide resin; and so on. The above-mentioned component can be, for example, a component constituting various portable devices (portable devices), automobiles, home appliances, etc. In addition, for the above-mentioned component, the surface to which the adhesive sheet is attached can be a coating surface formed by a coating of an acrylic system, a polyester system, an alkyd resin system, a melamine system, a urethane system, an acid-epoxy cross-linking system, or a composite system thereof (such as an acrylic melamine system, an alkyd resin melamine system), a galvanized steel plate, etc. The plated surface. In addition, the above-mentioned component can be any support film (for example, a resin film) exemplified as a material that can be used for a substrate. The PSA sheet disclosed herein may be a constituent element of a PSA sheet-attached member in which such a member is bonded to at least one surface of a PSA layer, for example.
[0450] As an example of preferred use, optical use can be cited. More specifically, for example, as an optical adhesive sheet used for the use of bonding optical components (optical component bonding), the manufacture of products (optical products) using the above optical components, etc., the adhesive sheet disclosed herein can be preferably used.
[0451] The above-mentioned optical component refers to a component having optical properties (for example, polarization, light refraction, light scattering, light reflectivity, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As the above-mentioned optical component, as long as it is a component with optical properties, it is not particularly limited. For example, components constituting devices (optical devices) such as display devices (image display devices) and input devices or components used by these devices can be cited. For example, polarizing plates, wavelength plates, phase difference plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coating (HC) films, impact absorption films, anti-fouling films, photochromic films, dimming films, transparent conductive films (ITO films), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates, and components stacked with them (sometimes collectively referred to as "functional films"). ) etc. It should be noted that the above-mentioned “plate” and “film” each include plate-shaped, film-shaped, sheet-shaped and the like. For example, “polarizing film” includes “polarizing plate”, “polarizer” and the like.
[0452] Examples of the display device include liquid crystal display devices, organic EL (electroluminescent) display devices, PDP (plasma display panel), electronic paper, etc., and are particularly preferably applied to foldable display devices and vehicle-mounted display devices that include expensive components. In addition, examples of the input device include touch panels, etc.
[0453] The optical component is not particularly limited, and examples thereof include components formed of glass, acrylic resin, polycarbonate, polyethylene terephthalate, metal thin film, etc. (e.g., sheet-shaped, film-shaped, plate-shaped components), etc. It should be noted that the "optical component" in this specification also includes components (design films, decorative films, surface protection films, etc.) that play a decorative and protective role while maintaining the visual recognizability of display devices and input devices.
[0454] There is no particular limitation on the method of bonding optical components using the adhesive sheet disclosed herein, and for example, it may be (1) a method of bonding optical components to each other via the adhesive sheet disclosed herein, (2) a method of bonding optical components to components other than optical components via the adhesive sheet disclosed herein, or (3) a method in which the adhesive sheet disclosed herein contains an optical component and the adhesive sheet is bonded to an optical component or a component other than an optical component. It should be noted that in the above-mentioned method (3), the adhesive sheet containing an optical component may be, for example, an adhesive sheet whose substrate is an optical component (for example, an optical film). Such an adhesive sheet containing an optical component as a substrate may also be considered as an adhesive optical component (for example, an adhesive optical film). In addition, in the case where the adhesive sheet disclosed herein is an adhesive sheet of a type having a substrate and the above-mentioned functional film is used as the above-mentioned substrate, the adhesive sheet disclosed herein may also be considered as an "adhesive functional film" having an adhesive layer disclosed herein on at least one side of the functional film.
[0455] The adhesive sheet disclosed herein can be preferably used in a manner of being attached to a non-water-absorbing smooth surface such as a glass plate, a metal plate, a resin plate, etc. Among them, the adhesive sheet is suitable for being attached to a glass plate such as a polarizing plate, an alkaline glass, an alkali-free glass, etc. The above-mentioned polarizing plate can be a polarizing plate on which a hydrophilic treatment (corona treatment, plasma treatment, formation of a hydrophilic layer, etc.) is applied to the surface to which the adhesive sheet is attached.
[0456] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are based on weight.
[0457] <Preparation of Adhesive Composition>
[0458] (Adhesive composition A-1)
[0459] 85 parts of 2EHA, 13 parts of methyl acrylate (MA), 1.2 parts of AA, 0.8 parts of MAA, 0.02 parts of 3-methacryloxypropyltrimethoxysilane (KBM-503 manufactured by Shin-Etsu Chemical Co., Ltd.), 0.048 parts of a chain transfer agent (tert-dodecyl mercaptan) and 2.0 parts of an emulsifier (LATEMUL E-118B manufactured by Kao Corporation) were mixed and emulsified in 100 parts of ion-exchanged water to prepare an aqueous emulsion of a monomer mixture (monomer emulsion).
[0460] The monomer emulsion was placed in a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device, and stirred at room temperature for more than 1 hour while introducing nitrogen. Next, the system was heated to 60°C, 0.1 parts of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate (VA-057 manufactured by Wako Pure Chemical Industries, Ltd.) was added as a polymerization initiator, and the mixture was reacted at 60°C for 6 hours to obtain an aqueous dispersion of an acrylic polymer. To the aqueous dispersion, 10 parts of a tackifier resin emulsion (SUPER ESTER E-865NT manufactured by Arakawa Chemical, an aqueous dispersion of a polymerized rosin ester having a softening point of 160°C) were added based on the solid content relative to 100 parts of the acrylic polymer in the dispersion, and 0.1 parts of n-decyltrimethoxysilane as a release regulator was further added, and the pH was adjusted to about 7.5 using 10% ammonia water, thereby preparing an emulsion-type adhesive composition A-1.
[0461] (Adhesive composition B-1)
[0462] An acrylic copolymer having a benzophenone structure in the side chain (manufactured by BASF, trade name: acResinUV3532, Tg: -60°C, Mw: 25×10 4 , BP equivalent: 10 mg / g), 60 parts of 2-ethylhexyl acrylate (2EHA), 30 parts of N-vinyl-2-pyrrolidone (NVP), 0.2 parts of 1,6-hexanediol diacrylate (HDDA), and 0.15 parts of a photoinitiator p1 (manufactured by IGM Regins, trade name: Omnirad 651) having an absorption peak in the wavelength range of 300nm to 500nm were mixed to prepare an ultraviolet curable adhesive composition B-1 for preparing a photo-crosslinkable adhesive. The viscosity of the adhesive composition B-1 (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature of 30°C) was 2.4 Pa·s, and the organic solvent content was less than 1% by weight.
[0463] (Adhesive composition B-2)
[0464] An ultraviolet curable adhesive composition B-2 for preparing a photo-crosslinkable adhesive was prepared by mixing 30 parts of an acrylic copolymer having a benzophenone structure in a side chain (manufactured by BASF, trade name: acResinUV3532), 38 parts of 2EHA, 4 parts of NVP, 28 parts of isobornyl acrylate (IBXA), 0.04 parts of HDDA, 0.08 parts of 3-acryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicone Co., Ltd., trade name: KBM-5103), and 0.2 parts of a photoinitiator p2 having an absorption peak in the wavelength range of 300 nm to 500 nm (manufactured by IGM Regins, trade name: Omnirad 184). The viscosity of the adhesive composition B-2 (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature: 30° C.) was 0.4 Pa·s, and the organic solvent content was less than 1% by weight.
[0465] (Adhesive composition B-3)
[0466] Into a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device, 60 parts of n-butyl acrylate (BA), 6 parts of cyclohexyl acrylate (CHA), 18 parts of N-vinyl-2-pyrrolidone (NVP), 1 part of isostearyl acrylate (iSTA) and 15 parts of 4-hydroxybutyl acrylate (4HBA) as monomer components, 0.085 parts of α-thioglycerol as a chain transfer agent, 122 parts of ethyl acetate as a polymerization solvent, 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and solution polymerization was carried out under a nitrogen atmosphere to obtain a solution of polymer P1. The weight average molecular weight (Mw) of polymer P1 is 300,000. The Tg of polymer P1 calculated from the composition of the above monomer components is -33°C.
[0467] To the solution of the polymer P1, 0.5 parts of 2-methacryloyloxyethyl isocyanate (MOI) and 0.0025 parts of dibutyltin dilaurate were added based on 100 parts of the polymer P1 in the solution, and the mixture was stirred at 50° C. for 7 hours in an air atmosphere to allow the polymer P1 and MOI to undergo an addition reaction, thereby obtaining a solution of a polymer P2 having a carbon-carbon double bond.
[0468] To the solution of the polymer P2, 0.2 parts (based on the solid content) of an isocyanate crosslinking agent (trimethylolpropane / xylylene diisocyanate adduct (Mitsui Chemicals, Inc., Takenate D-110N, solid content concentration of 75% by mass)), 0.01 parts of dioctyltin dilaurate, 3 parts of acetylacetone, and 0.2 parts of a photoinitiator p2 (Omnirad 184) were added relative to 100 parts of the polymer P2 in the solution, and the mixture was mixed uniformly to prepare a solvent-based adhesive composition B-3.
[0469] (Adhesive composition B-4)
[0470] Into a reaction container equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device, 64.5 parts of BA, 6 parts of cyclohexyl acrylate (CHA), 9.6 parts of NVP, 5 parts of isostearyl acrylate (ISTA) and 14.9 parts of 4-hydroxybutyl acrylate (4HBA) as monomer components, 0.07 parts of α-thioglycerol as a chain transfer agent, 122 parts of ethyl acetate as a polymerization solvent, and 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and solution polymerization was carried out under a nitrogen atmosphere, thereby obtaining a solution containing an acrylic polymer with a Mw of 600,000.
[0471] To the acrylic polymer solution obtained above, 0.09 parts (based on the solid content) of an isocyanate crosslinking agent (trimethylolpropane / xylylene diisocyanate adduct (Takenate D-110N manufactured by Mitsui Chemicals, Inc., solid content concentration of 75% by mass), 0.4 parts of an acrylic oligomer, 0.02 parts of dioctyltin dilaurate (EMBILIZER OL-1 manufactured by Tokyo Fine Chemical Co., Ltd.) as a crosslinking accelerator, 3 parts of acetylacetone as a crosslinking retarder, 2.7 parts of dipentaerythritol hexaacrylate (DPHA) as a multifunctional monomer, and 0.22 parts of a photoinitiator p2 (Omnirad 184) were added with respect to 100 parts of the monomer components used for preparing the solution, and the mixture was mixed uniformly to prepare a solvent-based adhesive composition B-4.
[0472] As the acrylic oligomer, one synthesized by the following method was used.
[0473] [Synthesis of acrylic oligomer]
[0474] 100 parts of toluene, 60 parts of dicyclopentyl methacrylate (DCPMA) (trade name: FA-513M, manufactured by Hitachi Chemical Co., Ltd.), 40 parts of methyl methacrylate (MMA), and 3.5 parts of α-thioglycerol as a chain transfer agent were placed in a four-necked flask. Then, the mixture was stirred at 70°C for 1 hour under a nitrogen atmosphere, and then 0.2 parts of (AIBN) as a thermal polymerization initiator was added, and the mixture was reacted at 70°C for 2 hours, and then at 80°C for 2 hours. Then, the reaction solution was placed in a temperature atmosphere of 130°C, and the toluene, chain transfer agent, and unreacted monomers were dried and removed, thereby obtaining a solid acrylic oligomer. The acrylic oligomer had a Tg of 144°C and a Mw of 4300.
[0475] <Preparation of adhesive sheets>
[0476] (Example 1)
[0477] The adhesive composition B-1 was applied to the release surface of a release film R1 (MRF#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm, which was used as the release surface on one side of the polyester film, and the release film R2 (MRE#38, manufactured by Mitsubishi Resins Co., Ltd.) was covered with the release surface on the other side of the polyester film to block the air. From one side of the laminate, a black light (manufactured by Toshiba Corporation, trade name FL15BL) was used at an illumination of 5 mW / cm 2 , the accumulated light intensity is 800mJ / cm 2 Thus, a photo-crosslinkable adhesive b-1, which is a cured product of the adhesive composition B-1, was obtained in the form of an adhesive layer (B layer) having a thickness of 150 μm sandwiched between the release films R1 and R2.
[0478] The illuminance of the black light lamp is a value measured by an industrial UV detector (manufactured by TOPCON, trade name: UVR-T1, light receiving unit model: UD-T36) with a peak sensitivity wavelength of about 350 nm.
[0479] Next, the release film R2 was removed from the adhesive layer, and the adhesive composition A-1 was directly applied on the exposed adhesive layer (B layer), and dried at 120°C for 3 minutes to form an adhesive layer (A layer) with a thickness of 5 μm, and the release surface of the release film R2 was attached to the surface of the A layer. As described above, a double-layer adhesive layer (adhesive sheet without substrate) in which the A layer and the B layer were directly in contact and stacked was prepared. The surfaces of the A layer side and the B layer side of the adhesive sheet without substrate were protected by the release films R2 and R1, respectively.
[0480] (Example 2)
[0481] Instead of the adhesive composition B-1, the adhesive composition B-2 was used. Except for this, the same operation as in Example 1 was carried out to obtain a photo-crosslinkable adhesive b-2 as a cured product of the adhesive composition B-2 in the form of an adhesive layer (B layer) with a thickness of 150 μm sandwiched between release films R1 and R2. The adhesive composition A-1 was directly coated on the adhesive layer (B layer), and dried at 120°C for 3 minutes to form an adhesive layer (A layer) with a thickness of 5 μm, and the release surface of the release film R2 was attached to the A layer. As described above, a double-layer adhesive layer (adhesive sheet without a substrate) in which the A layer and the B layer were directly in contact and stacked was prepared. It should be noted that the VOC emission of the B layer prepared in Examples 1 and 2 was measured by the above-mentioned method, and the results were all less than 500 μg / g.
[0482] (Example 3)
[0483] The adhesive composition B-3 was applied to the release surface of the release film R1 (MRF#38 manufactured by Mitsubishi Resins Co., Ltd.) and dried at 130°C for 2 minutes to prepare an adhesive layer with a thickness of 150 μm. The adhesive composition A-1 was directly applied to the adhesive layer (B layer) and dried at 120°C for 3 minutes to form an adhesive layer (A layer) with a thickness of 5 μm, and the release surface of the release film R2 was attached to the A layer. As described above, a double-layer adhesive layer (adhesive sheet without a substrate) in which the A layer and the B layer were directly in contact and laminated was prepared.
[0484] (Example 4)
[0485] The same operation as in Example 3 was performed except that the adhesive composition B-4 was used instead of the adhesive composition B-3 to prepare an adhesive layer with a thickness of 150 μm. The adhesive composition A-1 was directly applied on the adhesive layer (B layer) and dried at 120° C. for 3 minutes to form an adhesive layer (A layer) with a thickness of 5 μm, and the release surface of the release film R2 was attached to the A layer. As described above, an adhesive layer (adhesive sheet without a substrate) with a double-layer structure in which the A layer and the B layer were directly in contact and laminated was prepared.
[0486] <Production of laminate>
[0487] The A layer side of the substrate-free adhesive sheet involved in each example was pressed onto the corona-treated polarizing plate by moving a 2kg rubber roller back and forth once. Next, a polyethylene terephthalate (PET) film with a thickness of 25 μm and corona-treated was attached to the B layer side of the above-mentioned adhesive sheet. After being subjected to autoclave treatment (50°C, 0.5MPa, 15 minutes), ultraviolet rays were irradiated from the PET film side using a high-pressure mercury lamp (manufactured by Toshiba Corporation, trade name H3000L / 22N), thereby photo-crosslinking the B layer of the above-mentioned adhesive layer. As described above, a laminate having the structure of PET film / adhesive layer (B layer / A layer) / polarizing plate was prepared.
[0488] It should be noted that the ultraviolet irradiation conditions were as follows: in Examples 1 and 2, the illuminance was set to 300 mW / cm 2 (Industrial UV tester manufactured by TOPCON, trade name: UVR-T1, measured using light receiving unit model UD-T25), cumulative light intensity: 10000 mJ / cm 2 In Examples 3 and 4, the illumination is set to 300 mW / cm 2 (Industrial UV tester manufactured by TOPCON, trade name: UVR-T1, measured using light receiving unit model UD-T36), cumulative light intensity: 3000 mJ / cm 2 .
[0489] <Measurement and evaluation>
[0490] In the following, ultraviolet irradiation was performed using a high-pressure mercury lamp (manufactured by Toshiba Corporation, trade name H3000L / 22N). Regarding the irradiation conditions, in Examples 1 and 2, the illumination was set to 300 mW / cm2 (industrial UV detector manufactured by TOPCON Corporation, trade name: UVR-T1, measured value obtained using the light receiving unit model UD-T25), and the accumulated light intensity was set to 10,000 mJ / cm 2 In Examples 3 and 4, the illumination is set to 300 mW / cm 2 (Industrial UV tester manufactured by TOPCON, trade name: UVR-T1, measured using light receiving unit model UD-T36), cumulative light intensity: 3000 mJ / cm 2 .
[0491] In addition, as a corona-treated polarizing plate (corona-treated polarizing plate), a polarizing plate obtained by corona-treating one surface of a polarizing plate (trade name "REGQ-HC3" manufactured by Nitto Denko Corporation, with a thickness of 92 μm) is used. Specifically, the corona treatment is performed by passing the polarizing plate through a table-type surface corona treatment device (manufactured by KASUGA, device name "AGF-012") once under the conditions of an output power setting of 3 (displayed as 0.17 kW) and a stage speed scale of 20 (equivalent to a speed of 3 m / min). The water contact angle on the surface of the corona-treated polarizing plate is 6 degrees.
[0492] (1) Determination of peel strength N0
[0493] (Before saving)
[0494] The substrate-free adhesive sheet involved in each example was cut into a size of 10 mm in width and 100 mm in length to prepare a test piece. Under an environment of 23°C and 50% RH, a 2kg rubber roller was moved back and forth once to press the adhesive surface (A layer side of the adhesive layer) of the test piece onto the corona-treated polarizing plate. Next, the B layer side of the test piece was attached to a 25 μm thick PET film that had been corona-treated. After being autoclaved (50°C, 0.5 MPa, 15 minutes), ultraviolet rays were irradiated from the PET film side under the above conditions.
[0495] Then, under the environment of 23°C and 50% RH, the test piece was peeled off from the polarizing plate using a tensile tester (Minebea, universal tensile compression tester, device name "tensile compression tester, TCM-1kNB") at a tensile speed of 300 mm / min and a peeling angle of 180 degrees, and the peel strength at this time was measured. The measurement was performed 3 times, and their average values are shown in Table 1.
[0496] (After saving)
[0497] The substrate-free PSA sheets of each example were stored at 40°C for 5 days in a state where the surfaces of the A layer side and the B layer side were protected by release films R2 and R1, respectively. The substrate-free PSA sheets after storage were used to measure the peel strength N0 in the same manner as the substrate-free PSA sheets before storage. The results are shown in Table 1.
[0498] (2) Determination of peel strength N2
[0499] (Before saving)
[0500] In the measurement of the peel strength N0, 20 μL of distilled water was supplied to the portion where the test piece began to separate from the polarizing plate (peeling interface) while the adhesive sheet was peeled off from the polarizing plate, and the peel strength after the distilled water was supplied was measured. The measurement was performed separately (i.e., 3 times) when each peel strength N0 was measured, and their average values are shown in Table 1.
[0501] It should be noted that, here, the peel strength N0 and the peel strength N2 are measured continuously for each test piece, but the peel strength N0 and the peel strength N2 may be measured using different test pieces. For example, when it is difficult to prepare a test piece of a length sufficient for continuous measurement, a method of using different test pieces for measurement may be adopted.
[0502] (After saving)
[0503] The substrate-free PSA sheets of each example were stored at 40°C for 5 days in a state where the surfaces of the A layer side and the B layer side were protected by release films R2 and R1, respectively. The substrate-free PSA sheets after storage were used to measure the peel strength N2 in the same manner as the substrate-free PSA sheets before storage. The results are shown in Table 1.
[0504] (3) Determination of elastic modulus Gb' before photocrosslinking
[0505] The B layer prepared in each example was stacked in a manner to have a thickness of about 1.5 mm, and punched into a disc shape with a diameter of 7.9 mm to prepare a test sample. The test sample was clamped with parallel plates, and a shear strain with a frequency of 1 Hz was given using a viscoelasticity tester (ARES, manufactured by Rheometrics) while a dynamic viscoelasticity measurement was performed in a temperature range of -70 to 150°C and a heating rate of 5°C / min using a shear mode to obtain the shear storage elastic modulus Gb' at 80°C. The results are shown in Table 1.
[0506] (4) Determination of elastic modulus Gc' after photocrosslinking
[0507] For the B layer produced in each example, ultraviolet rays were irradiated from one side under the above conditions while sandwiched between release films R1 and R2, and after photocrosslinking, the release films R1 and R2 were removed, overlapped in a manner of about 1.5 mm, and punched into a disk shape with a diameter of 7.9 mm to produce a measurement sample. For this measurement sample, dynamic viscoelasticity measurement was performed in the same manner as the measurement of the elastic modulus Gb' before photocrosslinking, and the shear storage elastic modulus Gc' at 80°C was obtained. The results are shown in Table 1.
[0508] (5) Durability evaluation
[0509] An aluminum foil (manufactured by Mitsubishi Aluminum Foil, trade name "Nippaku Foil", thickness 12 μm) was bonded to one surface of a polarizing plate (manufactured by Nitto Denko, trade name "REGQ-HC3", thickness 92 mm) using a 15 μm thick adhesive, and the resulting product was used as an adherend to be bonded to one surface of a substrate-free pressure-sensitive adhesive sheet.
[0510] The substrate-free adhesive sheet involved in each example is cut into a size of 60 mm × 120 mm together with the release films R1 and R2, and then the release film R2 is peeled off, and the exposed adhesive surface (the A layer side of the adhesive layer) is adhered to the surface of the polarizing plate side of the above-mentioned adherend using a hand roller. Next, the release liner R1 is peeled off from the above-mentioned adhesive, and the exposed adhesive surface (the B layer side of the adhesive layer) is adhered to a glass plate (manufactured by Matsunami Glass Industries, trade name "MICRO SLIDE GLASS", product number "S", thickness of 1.3 mm, haze of 0.1%, water-polished edge). As described above, a laminate having the structure of glass plate / adhesive layer (B layer / A layer) / polarizing plate / aluminum foil is obtained.
[0511] This laminate was subjected to autoclave treatment (50° C., 0.5 MPa, 15 minutes), and then irradiated with ultraviolet rays from the glass plate side under the above-mentioned conditions. The obtained product was used as a sample for durability evaluation.
[0512] After the evaluation sample was stored at 85°C for 24 hours, the presence or absence of bubbles at the interface between layer A and the polarizing plate was visually observed at 23°C and 50% RH, and the durability was evaluated at the following two levels. The results are shown in the "Close Adhesion Durability" column of Table 1. It should be noted that, when using any of the adhesive sheets involved in the examples, no bubbles were observed immediately after the above-mentioned durability evaluation samples were prepared.
[0513] E (Excellent): No bubbles were observed (excellent adhesion durability).
[0514] P (Poor): Generation of bubbles was clearly observed (insufficient adhesion durability).
[0515] [Table 1]
[0516] Table 1
[0517]
[0518] As shown in Table 1, the shear storage modulus Gb' of the B layer can be increased by photocrosslinking in the adhesive sheets of Examples 1 to 3, showing good adhesion durability. In addition, the adhesive sheets of Examples 1 to 3 have good storage stability, and thus show excellent water releasability both before and after storage.
[0519] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes examples obtained by variously modifying and changing the specific examples described above.
[0520] Description of Reference Numerals
[0521] 1, 2 Adhesive sheet
[0522] 20 Substrate
[0523] 20A Side 1
[0524] 20B Second side (back side)
[0525] 30, 31 Release liner
[0526] 70 Optical components
[0527] 110 Adhesive layer
[0528] 110A One surface (bonding surface)
[0529] 112 Level A
[0530] 114 B-layer
[0531] 200 Components with adhesive sheets
Claims
1. An adhesive sheet having an adhesive layer, The adhesive layer has a multilayer structure including an A layer constituting one surface of the adhesive layer and a B layer disposed on the back side of the A layer. The layer A contains a hydrophilic agent, and the content of the hydrophilic agent in the layer A is 0.001 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of monomer components constituting the polymer contained in the layer A. The layer B is a photo-crosslinkable adhesive layer containing a photo-crosslinkable polymer, The B layer includes a polymer having a benzophenone structure in a side chain as the photo-crosslinkable polymer, or the B layer includes a polymer having a carbon-carbon double bond as the photo-crosslinkable polymer.
2. The adhesive sheet according to claim 1, wherein The layer B contains a polymer having a benzophenone structure in a side chain as the photo-crosslinkable polymer.
3. The adhesive sheet according to claim 1, wherein The layer B contains a polymer having a carbon-carbon double bond as the photo-crosslinkable polymer.
4. The adhesive sheet according to any one of claims 1 to 3, wherein In the layer B, the content of the polyfunctional monomer having two or more ethylenically unsaturated groups is 40 μmol / g or less.
5. The adhesive sheet according to any one of claims 1 to 3, wherein The water peel strength reduction rate calculated by the following formula from the peel strength N0 and the peel strength N2 measured by the following procedure is 40% or more. Water peeling force reduction rate [%] = (1-(N2 / N0)) × 100; [Measurement procedure of peel strength N0] The A layer side of the adhesive sheet was pressed against the corona-treated polarizing plate by making a 2 kg rubber roller reciprocate once, and after autoclave treatment, ultraviolet rays were irradiated using a high-pressure mercury lamp, and then the adhesive sheet was peeled off from the polarizing plate at a tension speed of 300 mm / min and a peeling angle of 180 degrees in an atmosphere of 25° C. The peel strength at this time was taken as the peel strength N0, and the autoclave treatment was performed under the conditions of 50° C., 0.5 MPa, and 15 minutes; [Measurement procedure of peel strength N2] In the measurement of the peel strength N0, 20 μL of distilled water was supplied to the portion where the pressure-sensitive adhesive sheet began to separate from the polarizing plate while the pressure-sensitive adhesive sheet was being peeled off from the polarizing plate, and the peel strength after supplying the distilled water was taken as the peel strength N2.
6. The adhesive sheet according to claim 5, wherein The peel strength N0 measured by the following procedure is 1.5 N / 10 mm or more. [Measurement procedure of peel strength N0] A 2 kg rubber roller was moved back and forth once to press the A layer side of the adhesive sheet onto the corona treated polarizing plate, and after autoclave treatment, ultraviolet rays were irradiated using a high pressure mercury lamp. Then, in an atmosphere of 25° C., the adhesive sheet was peeled off from the polarizing plate at a tensile speed of 300 mm / min and a peeling angle of 180 degrees. The peel strength at this time was measured and taken as the peel strength N0. The autoclave treatment was carried out at 50° C., 0.5 MPa, and 15 minutes.
7. The adhesive sheet according to any one of claims 1 to 3, wherein The adhesive layer has a thickness of 10 μm or more and 500 μm or less.
8. The adhesive sheet according to any one of claims 1 to 3, wherein The thickness of the A layer is greater than or equal to 2 μm and less than 10 μm.
9. A method for manufacturing a laminate, comprising: laminating the A layer side of the adhesive sheet according to any one of claims 1 to 8 on a member; as well as The B layer is photo-crosslinked.
Citation Information
Patent Citations
An electric motor having a drive valve
JP1974071517A
Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device
JP2007051271A
Active energy ray-curable composition and pressure-sensitive adhesive
JP2012140497A
Metal vertical roofing board and roof end structure using the same
JP2019143393A
Radiation curable pressure sensitive adhesive sheet
CN103717692A